12/15-lipoxygenase orchestrates the clearance of apoptotic cells and maintains immunologic tolerance. - Uderhardt, Stefan; Herrmann, Martin; Oskolkova, Olga V.; Aschermann, Susanne; Bicker, Wolfgang; Ipseiz, Natacha; Sarter-Zaiss, Kerstin; Frey, Benjamin; Rothe, Tobias; Voll, Reinhard; Nimmerjahn, Falk; Bochkov, Valery N.; et al. (Immunity, 2012)
Noninflammatory clearance of apoptotic cells (ACs) is crucial to maintain self-tolerance. Here, we have reported a role for the enzyme 12/15-lipoxygenase (12/15-LO) as a central factor governing the sorting of ACs into differentially activated monocyte subpopulations. During inflammation, uptake of ACs was confined to a population of 12/15-LO-expressing, alternatively activated resident macrophages (resMΦ), which blocked uptake of ACs into freshly recruited inflammatory Ly6C(hi) monocytes in a 12/15-LO-dependent manner. ResMΦ exposed 12/15-LO-derived oxidation products of phosphatidylethanolamine (oxPE) on their plasma membranes and thereby generated a sink for distinct soluble receptors for ACs such as milk fat globule-EGF factor 8, which were essential for the uptake of ACs into inflammatory monocytes. Loss of 12/15-LO activity, in turn, resulted in an aberrant phagocytosis of ACs by inflammatory monocytes, subsequent antigen presentation of AC-derived antigens, and a lupus-like autoimmune disease. Our data reveal an unexpected key role for enzymatic lipid oxidation during the maintenance of self-tolerance.

3D convolutional neural network-based autosegmentation improves brain metastases detection and quantification for brain stereotactic radiotherapy treatment planning - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmidt, Manuel; Heiß, Rafael; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

3D-Shaped Binders of Unfolded Proteins Inducing Cancer Cell-Specific Endoplasmic Reticulum Stress In Vitro and In Vivo - Klemt, Insa; Varzatskii, Oleg; Selin, Roman; Vakarov, Serhii; Kovalska, Vladyslava B.; Bila, Galyna; Bilyy, Rostyslav; Voloshin, Yan; Cossío Cuartero, Itziar; Hidalgo, Andrés; Frey, Benjamin; Becker, Ina; et al. (Journal of the American Chemical Society, 2023)
The amount of unfolded proteins is increased in cancer cells, leading to endoplasmic reticulum (ER) stress. Therefore, cancer cells are sensitive to drugs capable of further enhancing ER stress. Examples of such drugs include the clinically approved proteosome inhibitors bortezomib and carfilzomib. Unfortunately, the known ER stress inducers exhibit dose-limiting side effects that justify the search for better, more cancer-specific drugs of this type. Herein, we report on FeC 2, which binds to unfolded proteins prevents their further processing, thereby leading to ER stress and ROS increase in cancer cells, but not in normal cells. FeC 2 exhibits low micromolar toxicity toward human acute promyelocytic leukemia HL-60, Burkitt’s lymphoma BL-2, T-cell leukemia Jurkat, ovarian carcinoma A2780, lung cancer SK-MES-1, and murine lung cancer LLC1 cells. Due to the cancer-specific mode of action, 2 is not toxic in vivo up to the dose of 147 mg/kg, does not affect normal blood and bone marrow cells at the therapeutically active dose, but strongly suppresses both primary tumor growth (confirmed in Nemeth-Kellner lymphoma and LLC1 lung cancer models of murine tumor) and spreading of metastases (LLC1).

Abstracts DEGRO 2018 Low-dose irradiation has an impact on bone metabolism as well as on local and systemic immune cell-mediated inflammation - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
Created from Fastlane, Scopus look-up

Abstracts DEGRO 2019 Niedrig dosierte Röntgenstrahlung beeinflusst die Makrophagenpolarisation im Zusammenspiel mit Synovialfibroblasten auf eine anti-entzündliche Art und Weise - Deloch, Lisa; Fuchs, Jana; Rückert, Michael; Frey, Benjamin; Gaipl, Udo (2019)
Created from Fastlane, Scopus look-up

Abstracts of the 20th Annual Meeting of the German Society for Radiation Oncology (DEGRO), 3-4 July, 2014, Dusseldorf, Germany 20. Jahrestagung der Deutschen Gesellschaft für Radioonkologie - Deloch, Lisa; Derer, Anja; Rühle, Paul-Friedrich; Ott, Oliver; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2014)
Created from Fastlane, Scopus look-up

A clinician's plea to test glioma patients for CMV - Goerig, Nicole; Frey, Benjamin; Überla, Klaus; Gaipl, Udo; Fietkau, Rainer (Neuro-Oncology, 2017)
EVALuna2:32871

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease. - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea T.; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon ?2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing.Colitis was induced in C57BL/6JCrl mice (controls), mice with IEC-specific disruption of Stat1 (Stat1IEC-KO), mice with disruption of the interferon ? receptor 1 gene (Il28ra(-/-)), and mice with disruption of the interferon regulatory factor 3 gene (Irf3(-/-)), with or without disruption of Irf7 (Irf7(-/-)). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging.Lamina propria cells in colon tissues of patients with IBD, and mice with colitis, had increased expression of IL28 compared with controls; levels of IL28R were increased in the colonic epithelium of patients with IBD and mice with colitis. Administration of IL28 induced phosphorylation of STAT1 in primary human and mouse IECs, increasing with dose. Il28ra(-/-), Irf3(-/-), Irf3(-/-)Irf7(-/-), as well as Stat1IEC-KO mice, developed more severe colitis after administration of dextran sulfate sodium than control mice, with reduced epithelial restitution. Il28ra(-/-) and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing.IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD.
EVALuna2:9356

Aggregated neutrophil extracellular traps limit inflammation by degrading cytokines and chemokines - Schauer, Christine; Janko, Christina; Munoz Becerra, Luis; Zhao, Yi; Kienhöfer, Deborah; Frey, Benjamin; Lell, Michael; Manger, Bernhard; Rech, Juergen; Naschberger, Elisabeth; Holmdahl, Rikard; Krenn, Veit; et al. (Nature Medicine, 2014)
Gout is characterized by an acute inflammatory reaction and the accumulation of neutrophils in response to monosodium urate (MSU) crystals. Inflammation resolves spontaneously within a few days, although MSU crystals can still be detected in the synovial fluid and affected tissues. Here we report that neutrophils recruited to sites of inflammation undergo oxidative burst and form neutrophil extracellular traps (NETs). Under high neutrophil densities, these NETs aggregate and degrade cytokines and chemokines via serine proteases. Tophi, the pathognomonic structures of chronic gout, share characteristics with aggregated NETs, and MSU crystals can induce NETosis and aggregation of NETs. In individuals with impaired NETosis, MSU crystals induce uncontrolled production of inflammatory mediators from neutrophils and persistent inflammation. Furthermore, in models of neutrophilic inflammation, NETosis-deficient mice develop exacerbated and chronic disease that can be reduced by adoptive transfer of aggregated NETs. These findings suggest that aggregated NETs promote the resolution of neutrophilic inflammation by degrading cytokines and chemokines and disrupting neutrophil recruitment and activation.
Created from Fastlane, Scopus look-up

Analysis of antioxidant Factors in Patients' Blood with chronic Degenerative and inflammatory Diseases in the Course of Low-Dose Radiotherapy - Hehlgans, S.; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Oppermann, J.; Ott, Oliver; Weissmann, T.; Dilovic, E.; Roedel, C.; Gaipl, Udo; Fournier, C.; Roedel, F. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Analysis of the analgesic Effects of LDRT in Patients in the IMMO-LDRT01 Study - Fröhlich, Birgitta; Donaubauer, Anna-Jasmina; Weissmann, T.; Becker, Ina; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Analysis of the Expression of anti-oxidative Factors in the Blood of Patients with chronic degenerative and inflammatory Diseases before and after Low-dose Irradiation - IMMO-LDRT01 Study - Hehlgans, S.; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Ott, Oliver; Weissmann, Thomas; Fournier, C.; Gaipl, Udo; Roedel, F. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Analysis of the immune status from peripheral whole blood with a single-tube multicolor flow cytometry assay - Donaubauer, Anna-Jasmina; Becker, Ina; Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Methods in Enzymology, 2020)
Supplementation of standard cancer therapies (radiotherapy, chemotherapy, surgery) with immunotherapies has revolutionized cancer treatment. In order to include recent improvements of multimodal therapies into clinical routine, knowledge about the immune status, the immune dynamics and the detailed composition and activation of patient's immune system is required. The here presented single-tube multicolor flow cytometry assay allows the discrimination of 20 clinically relevant immune cell subsets and their activation status in peripheral whole blood. It includes 15 different antibodies and can be established on a common 3 laser and 10 color flow-cytometer. Furthermore, this assay is easy to set-up and to perform as well as fast with only 40 min of sample preparation time. Moreover, only 100 μL of whole blood are sufficient for this precise determination of the individual immune status. It is already applied in translational programs of clinical studies and trials and can further be adapted for future ones.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Immune status; Immunophenotyping; Multicolor flow-cytometry; Peripheral whole blood; Radioimmunotherapies

A novel HSP90 inhibitor with reduced hepatotoxicity synergizes with radiotherapy to induce apoptosis, abrogate clonogenic survival, and improve tumor control in models of colorectal cancer - Kinzel, Linda; Ernst, Anne; Orth, Michael; Albrecht, Valerie; Hennel, Roman; Brix, Nikko; Frey, Benjamin; Gaipl, Udo; Zuchtriegel, Gabriele; Reichel, Christoph A.; Blutke, Andreas; Schilling, Daniela; et al. (Oncotarget, 2016)
The chaperone heat shock protein 90 (HSP90) crucially supports the maturation, folding, and stability of a variety of client proteins which are of pivotal importance for the survival and proliferation of cancer cells. Consequently, targeting of HSP90 has emerged as an attractive strategy of anti-cancer therapy, and it appears to be particularly effective in the context of molecular sensitization towards radiotherapy as has been proven in preclinical models of different cancer entities. However, so far the clinical translation has largely been hampered by suboptimal pharmacological properties and serious hepatotoxicity of first- and second-generation HSP90 inhibitors. Here, we report on NW457, a novel radicicol-derived member of the pochoxime family with reduced hepatotoxicity, how it inhibits the DNA damage response and how it synergizes with ionizing irradiation to induce apoptosis, abrogate clonogenic survival, and improve tumor control in models of colorectal cancer in vitro and in vivo.
EVALuna2:32934

Antitumor immune responses induced by ionizing irradiation and further immune stimulation - Frey, Benjamin; Rubner, Yvonne; Kulzer, Lorenz; Werthmöller, Nina; Weiss, Eva-Maria; Fietkau, Rainer; Gaipl, Udo (Cancer Immunology Immunotherapy, 2014)
The therapy of cancer emerged as multimodal treatment strategy. The major mode of action of locally applied radiotherapy (RT) is the induction of DNA damage that triggers a network of events that finally leads to tumor cell cycle arrest and cell death. Along with this, RT modifies the phenotype of the tumor cells and their microenvironment. Either may contribute to the induction of specific and systemic antitumor immune responses. The latter are boosted when additional immune therapy (IT) is applied at distinct time points during RT. We will focus on therapy-induced necrotic tumor cell death that is immunogenic due to the release of damage-associated molecular patterns. Immune-mediated distant bystander (abscopal) effects of RT when combined with dendritic cell-based IT and the role of fractionation of radiation in the induction of immunogenic tumor cell death will be discussed. Autologous whole-tumor-cell-based vaccines generated by high hydrostatic pressure technology will be introduced and the influence of cytokines and the immune modulator AnnexinA5 on the ex vivo generated or in situ therapy-induced vaccine efficacy will be outlined. RT should be regarded as immune adjuvant for metastatic disease and as a tool for the generation of an in situ vaccine when applied at distinct fractionation doses or especially in combination with IT to generate immune memory against the tumor. To identify the most beneficial combination and chronology of RT with IT is presumably one of the biggest challenges of innovative tumor research and therapies.
EVALuna2:18146

Anti-tumor immune responses in primary and abscopal tumors differently depend on radiotherapy fractionation and immunotherapy modalities - Rueckert, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36507

APPA-HEALTH-21 Low doses of ionizing radiation reduce osteoclast numbers and increase osteoblast mineralization - Deloch, Lisa; Cucu, Aljona; Frey, Benjamin; Fournier, Claudia; Gaipl, Udo (2016)

APPA-HEALTH-28 The influence of ionizing radiation on differentiation and function of osteoclasts - Deloch, Lisa; Cucu, Aljona; Hoengl, N; Frey, Benjamin; Kraft, Daniela; Durante, Marco; Gaipl, Udo; Fournier, Claudia (2015)

Application of Stem Cells Shows Antiinflammatory Effect in an Irradiated Random Pattern Flap Model - Müller-Seubert, Wibke; Fuchs, Lena; Horch, Raymund E.; Distel, Luitpold; Frey, Benjamin; Renno, Isabell; Erber, Ramona; Arkudas, Andreas (Journal of Personalized Medicine, 2024)
Background: In reconstructive surgery, local flaps might develop tissue necrosis or partial flap loss especially after previous irradiation, which may be necessary in many tumor entities. The application of stem cells seems promising to improve flap perfusion and might be a possible solution to optimize flap survival. Methods: Twenty rats received harvesting of bilateral random pattern fasciocutaneous flaps. The right flaps received 20 Gy ionizing radiation 4 weeks prior to the surgery, while the left flaps served as the non-irradiated control. After flap harvest, four different stem cell mixtures (5 × 106 ASC, ASC-HUVEC, MSC, MSC-HUVEC) were applied under both right and left flaps using 1 mL fibrin glue as the delivery vehicle. Flap size and its necrotic area were examined clinically. Two weeks after the surgery, HE staining and immunohistochemical staining for CD68 and ERG, as well as PCR analysis (Interleukin 6, HIF-1α and VEGF), were performed. Results: Application of ASCs, ASCs-HUVECs and MSCs resulted in a lower number of CD68-stained cells compared to the no cell group. The expression of Hif1α was higher in the ASC group compared to those in the MSC and previously treated no cell groups. Treatment with MSCs and MSCs-HUVECs prevented shrinking of the flaps in this series. Conclusion: Application of ASCs, MSCs and ASCs-HUVECs was shown to have an antiinflammatory effect. Treatment with MSCs and MSCs-HUVECs can prevent early shrinking of the flaps.
CRIS-Team Scopus Importer:2024-07-05
Keywords: ASC; HUVEC; irradiation; MSC; random pattern flaps

Assessing Organ-at-risk Auto-contouring Solutions: Which Metrics are most predictive of clinical Time Savings? - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Lamrani, Allison; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Ott, Oliver; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Autologous whole tumor cell-based vaccines generated with high hydrostatic pressure bear immunogenic potential and act synergistically with radiotherapy to retard tumor growth - Frey, Benjamin; Seitz, C.; Weiss, E. M.; Rueckert, M.; Schlücker, Eberhard; Schaft, Niels; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32864

Basics of Radiation Biology When Treating Hyperproliferative Benign Diseases - Roedel, Franz; Fournier, Claudia; Wiedemann, Julia; Merz, Felicitas; Gaipl, Udo; Frey, Benjamin; Keilholz, Ludwig; Seegenschmiedt, M. Heinrich; Roedel, Claus; Hehlgans, Stephanie (Frontiers in Immunology, 2017)
For decades, low- and moderate-dose radiation therapy (RT) has been shown to exert a beneficial therapeutic effect in a multitude of non-malignant conditions including painful degenerative muscoloskeletal and hyperproliferative disorders. Dupuytren and Ledderhose diseases are benign fibroproliferative diseases of the hand/foot with fibrotic nodules and fascial cords, which determine debilitating contractures and deformities of fingers/toes, while keloids are exuberant scar formations following burn damage, surgery, and trauma. Although RT has become an established and effective option in the management of these diseases, experimental studies to illustrate cellular composites and factors involved remain to be elucidated. More recent findings, however, indicate the involvement of radiation-sensitive targets like mitotic fibroblasts/myofibroblasts as well as inflammatory cells. Radiation-related molecular mechanisms affecting these target cells include the production of free radicals to hamper proliferative activity and interference with growth factors and cytokines. Moreover, an impairment of activated immune cells involved in both myofibroblast proliferative and inflammatory processes may further contribute to the clinical effects. We here aim at briefly describing mechanisms contributing to a modulation of proliferative and inflammatory processes and to summarize current concepts of treating hyperproliferative diseases by low and moderate doses of ionizing radiation.
EVALuna2:32930

Benchmarking ChatGPT-4 on a radiation oncology in-training exam and Red Journal Gray Zone cases: potentials and challenges for AI-assisted medical education and decision making in radiation oncology - Huang, Yixing; Gomaa, Ahmed; Semrau, Sabine; Haderlein, Marlen; Lettmaier, Sebastian; Weissmann, Thomas; Grigo, Johanna; Ben Tkhayat, Hassen; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Maier, Andreas; et al. (Frontiers in Oncology, 2023)
Keywords: Large language model; Radiotherapy; Natural language processing; Artificial intelligence; Gray Zone; Clinical decision support (CDS)

Biocompatibility of Dextran-Coated 30 nm and 80 nm Sized SPIONs towards Monocytes, Dendritic Cells and Lymphocytes - Zschiesche, Lisa; Janko, Christina; Friedrich, Bernhard; Frey, Benjamin; Band, Julia; Lyer, Stefan; Alexiou, Christoph; Unterweger, Harald (Nanomaterials, 2023)
Dextran-coated superparamagnetic iron oxide nanoparticles (SPIONDex) of various sizes can be used as contrast agents in magnetic resonance imaging (MRI) of different tissues, e.g., liver or atherosclerotic plaques, after intravenous injection. In previous studies, the blood compatibility and the absence of immunogenicity of SPIONDex was demonstrated. The investigation of the interference of SPIONDex with stimulated immune cell activation is the aim of this study. For this purpose, sterile and endotoxin-free SPIONDex with different hydrodynamic sizes (30 and 80 nm) were investigated for their effect on monocytes, dendritic cells (DC) and lymphocytes in concentrations up to 200 µg/mL, which would be administered for use as an imaging agent. The cells were analyzed using flow cytometry and brightfield microscopy. We found that SPIONDex were hardly taken up by THP-1 monocytes and did not reduce cell viability. In the presence of SPIONDex, the phagocytosis of zymosan and E. coli by THP-1 was dose-dependently reduced. SPIONDex neither induced the maturation of DCs nor interfered with their stimulated maturation. The particles did not induce lymphocyte proliferation or interfere with lymphocyte proliferation after stimulation. Since SPIONDex rapidly distribute via the blood circulation in vivo, high concentrations were only reached locally at the injection site immediately after application and only for a very limited time. Thus, SPIONDex can be considered immune compatible in doses required for use as an MRI contrast agent.
CRIS-Team Scopus Importer:2023-01-20
Keywords: biocompatibility; immune response; magnetic resonance imaging (MRI); nanomedicine; superparamagnetic iron oxide nanoparticles (SPION)

BIOPHYSICS-08 Response of bone marrow progenitor cells to ionizing irradiation - Cucu, Aljona; Kraft, Daniela; Hirschmann, M; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; Durante, Marco; Fournier, Claudia (2014)

BIOPHYSICS-22 Time course of radiation induced chromosome aberrations in mouse bone marrow cells - Paz, Nerea; Nasonova, Elena; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; Durante, Marco; Ritter, Sylvia (2014)

Both Gender and Inflammatory Status play a Role in the low-dose Rontgen Therapy Effect on Synovial Fibroblasts - Völlings, Antonia; Piltz, Margaux; Titova, E.; Wolff, Teresa; Weissmann, Thomas; Fietkau, Rainer; Frey, Benjamin; Gaipla, U.; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Broadband microwave spiral applicator (105–125 MHz) for in vitro examinations of hyperthermia-induced tumor cell death forms–first analyses with human breast cancer cells - Walter, Jannik; Hader, Michael; Sengedorj, Azzaya; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Hyperthermia, 2023)
Purpose: Local tumor heating with microwave applicators has been used in multimodal breast cancer therapies. This hyperthermia allows to target small regions while marginally affecting healthy tissue. However, most preclinical examinations only use simplified heating methods. Microwave applicators employed for deep heating to provide the greatest depth of penetration operate in the tens to hundreds frequency. Therefore, we aimed to adapt and test a clinically often used broadband spiral applicator (105–125 MHz) for hyperthermia with clinically wanted temperatures of 41 and 44 °C in in vitro settings with human breast cancer cell lines and with simulations. Material and Methods: A clinically used spiral-microwave applicator (105–125 MHz) was the basis for the construction, simulation, and optimization of the in vitro HT set-up under stationary conditions. Microwave effects on tumor cell death of two human breast cancer cell lines (hormone-receptor positive MCF-7 and triple-negative MDA-MB-231) were compared with conventional heating in a contact-heating chamber. Cell death forms were analyzed by AnnexinV/Propidium iodide staining. Results: An in vitro spiral applicator microwave-based heating system that is effective at applying heat directly to adherent breast cancer cells in cell culture flasks with medium was developed. Simulations with COMSOL proved appropriate heat delivery and an optimal energy coupling at a frequency of 111 ± 2.5 MHz. Apoptosis and necrosis induction and significantly higher cell death rates than conventional heating at both temperatures were observed, and MCF-7 showed higher death rates than MDA-MB-231 tumor cells. Conclusions: Well-characterized in vitro heating systems are mandatory for a better understanding of the biological effects of hyperthermia in tumor therapies and to finally determine optimized clinical treatment schemes.
CRIS-Team Scopus Importer:2023-10-20
Keywords: 105–125 MHz spiral applicator; breast cancer; cell death forms; microwave frequency; Microwave hyperthermia; multimodal tumor treatment

Cancer Cell Death-Inducing Radiotherapy: Impact on Local Tumour Control, Tumour Cell Proliferation and Induction of Systemic Anti-tumour Immunity - Frey, Benjamin; Derer, Anja; Scheithauer, Heike; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo (Advances in Experimental Medicine and Biology, 2016)
Radiotherapy (RT) predominantly is aimed to induce DNA damage in tumour cells that results in reduction of their clonogenicity and finally in tumour cell death. Adaptation of RT with higher single doses has become necessary and led to a more detailed view on what kind of tumour cell death is induced and which immunological consequences result from it. RT is capable of rendering tumour cells immunogenic by modifying the tumour cell phenotype and the microenvironment. Danger signals are released as well as the senescence-associated secretory phenotype. This results in maturation of dendritic cells and priming of cytotoxic T cells as well as in activation of natural killer cells. However, RT on the other hand can also result in immune suppressive events including apoptosis induction and foster tumour cell proliferation. That's why RT is nowadays increasingly combined with selected immunotherapies.
EVALuna2:18359

Chemoradiation Increases PD-L1 Expression in Certain Melanoma and Glioblastoma Cells - Derer, Anja; Spiljar, Martina; Baeumler, Monika; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (Frontiers in Immunology, 2016)
Immunotherapy approaches currently make their way into the clinics to improve the outcome of standard radiochemotherapy (RCT). The programed cell death receptor ligand 1 (PD-L1) is one possible target that, upon blockade, allows T cell-dependent antitumor immune responses to be executed. To date, it is unclear which RCT protocol and which fractionation scheme leads to increased PD-L1 expression and thereby renders blockade of this immune suppressive pathway reasonable. We therefore investigated the impact of radiotherapy (RT), chemotherapy (CT), and RCT on PD-L1 surface expression on tumor cells of tumor entities with differing somatic mutation prevalence. Murine melanoma (B16-F10), glioblastoma (GL261-luc2), and colorectal (CT26) tumor cells were treated with dacarbazine, temozolomide, and a combination of irinotecan, oxaliplatin, and fluorouracil, respectively. Additionally, they were irradiated with a single dose [10 Gray (Gy)] or hypo-fractionated (2 × 5 Gy), respectively, norm-fractionated (5 × 2 Gy) radiation protocols were used. PD-L1 surface and intracellular interferon (IFN)-gamma expression was measured by flow cytometry, and IL-6 release was determined by ELISA. Furthermore, tumor cell death was monitored by AnnexinV-FITC/7-AAD staining. For firstin vivoanalyses, the B16-F10 mouse melanoma model was chosen. In B16-F10 and GL261-luc2 cells, particularly norm-fractionated and hypo-fractionated radiation led to a significant increase of surface PD-L1, which could not be observed in CT26 cells. Furthermore, PD-L1 expression is more pronounced on vital tumor cells and goes along with increased levels of IFN-gamma in the tumor cells. In melanoma cells CT was the main trigger for IL-6 release, while in glioblastoma cells it was norm-fractionated RT.In vivo, fractionated RT only in combination with dacarbazine induced PD-L1 expression on melanoma cells. Our results suggest a tumor cell-mediated upregulation of PD-L1 expression following in particular chemoradiation that is not only dependent on the somatic mutation prevalence of the tumor entity.
EVALuna2:32917
Keywords: fractionated radiotherapy; immunotherapy; checkpoint inhibitor; PD-L1; IFN-gamma; IL-6; melanoma; glioblastoma

Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Chromosome aberrations in lymphocytes of patients undergoing radon spa therapy: An explorative mfish study - Paz, Nerea; Hartel, Carola; Nasonova, Elena; Donaubauer, Anna-Jasmina; Frey, Benjamin; Ritter, Sylvia (International Journal of Environmental Research and Public Health, 2021)
In the present exploratory study, we aim to elucidate the action of radon in vivo and to assess the possible health risks. Chromosome aberrations were analyzed in lymphocytes of two patients (P1, P2) undergoing radon spa therapy in Bad Steben (Germany). Both patients, suffering from painful chronic degenerative disorders of the spine and joints, received nine baths (1.2 kBq/L at 34 °C) over a 3-week period. Chromosome aberrations were analyzed before and 6, 12 and 30 weeks after the start of therapy using the high-resolution multiplex fluorescence in situ hybridization (mFISH) technique. For comparison, the lymphocytes from two healthy donors (HD1, HD2) were examined. P1 had a higher baseline aberration frequency than P2 and both healthy donors (5.3 ± 1.3 vs. 2.0 ± 0.8, 1.4 ± 0.3 and 1.1 ± 0.1 aberrations/100 analyzed metaphases, respectively). Complex aberrations, biomarkers of densely ionizing radiation, were found in P1, P2 and HD1. Neither the aberration frequency nor the fraction of complex aberrations increased after radon spa treatment, i.e., based on biological dosimetry, no increased health risk was found. It is worth noting that a detailed breakpoint analysis revealed potentially clonal aberrations in both patients. Altogether, our data show pronounced inter-individual differences with respect to the number and types of aberrations, complicating the risk analysis of low doses such as those received during radon therapy.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Clonal aberrations; Complex aberrations; MFISH; Radon; T-cell receptor genes

Clinically Relevant Radiation Exposure Differentially Impacts Forms of Cell Death in Human Cells of the Innate and Adaptive Immune System - Falcke, Sylvia; Rühle, Paul-Friedrich; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (International Journal of Molecular Sciences, 2018)
In cancer treatments, especially high-dose radiotherapy (HDRT) is applied. Patients suffering from chronic inflammatory diseases benefit from low-dose radiation therapy (LDRT), but exposure to very low radiation doses can still steadily increase for diagnostic purposes. Yet, little is known about how radiation impacts on forms of cell death in human immune cells. In this study, the radiosensitivity of human immune cells of the peripheral blood was examined in a dose range from 0.01 to 60 Gy with regard to induction of apoptosis, primary necrosis, and secondary necrosis. Results showed that immune cells differed in their radiosensitivity, with monocytes being the most radioresistant. T cells mainly died by necrosis and were moderately radiosensitive. This was followed by B and natural killer (NK) cells, which died mainly by apoptosis. X-radiation had no impact on cell death in immune cells at very low doses (≤0.1 Gy). Radiation doses of LDRT (0.3⁻0.7 Gy) impacted on the more radiosensitive NK and B cells, which might contribute to attenuation of inflammation. Even single doses applied during RT of tumors did not erase the immune cells completely. These in vitro studies can be considered as the basis to optimize individual radiation therapy schemes in multimodal settings and to define suited time points for further inclusion of immunotherapies.
EVALuna2:36450

Clinically significant CMV (re)activation during or after radiotherapy/chemotherapy of the brain : Correlation with neurological deterioration and improvement upon antiviral treatment - Goerig, Nicole; Semrau, S.; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Dörfler, Arnd; Putz, Florian; Gaipl, Udo; Fietkau, Rainer (Strahlentherapie und Onkologie, 2016)
For both patients with high-grade gliomas and multiple cerebral metastases, radio(chemo)therapy is the standard therapy. Neurological decline during treatment is rarely attributed to infections of the brain but to tumor progression or side effects of radiotherapy.We present 4 cases of cytomegalovirus (CMV) viremia associated with neurological deterioration, which occurred during or shortly after radiotherapy and/or chemotherapy of the brain (brain metastases 2, high-grade glioma 1, carcinoma infiltrating brain 1). In all cases, neurological decline was sudden and unexpected, and causes such as increased intracranial pressure or tumor progression could be excluded radiologically. Treatment with dexamethasone and mannitol had no or only very short-term effects. General infections were either excluded or receding before the neurological symptoms occurred. All patients presented with decreasing levels of thrombocytes. In all cases, CMV (re)activation could be proven using blood test for CMV-DNA. The anti-CMV-IgG status suggested reactivation rather than a primary infection. One patient died within 72 h of onset of the symptoms (results of CMV tests were received postmortem). Diagnosis of 3 patients allowed successful administration of antiviral treatment, which greatly improved the general and neurological conditions of the patients within 48 h.Neurological deterioration during RT is hardly ever attributed to viral infections. These cases suggest that CMV reactivation and subsequent infection might actually be causative and has to be considered and treated.Further prospective studies verifying and investigating this observation in terms of frequency and clinical relevance seem indicated.
EVALuna2:8302

Clonogenicity-based radioresistance determines the expression of immune suppressive immune checkpoint molecules after hypofractionated irradiation of MDA-MB-231 triple-negative breast cancer cells - Gehre, Simon; Meyer, Felix; Sengedorj, Azzaya; Grottker, Fridolin; Reichardt, Clara; Alomo, Jannik; Borgmann, Kerstin; Frey, Benjamin; Fietkau, Rainer; Rückert, Michael; Gaipl, Udo (Frontiers in Oncology, 2023)
Only a subset of patients with triple-negative breast cancer (TNBC) benefits from a combination of radio- (RT) and immunotherapy. Therefore, we aimed to examine the impact of radioresistance and brain metastasizing potential on the immunological phenotype of TNBC cells following hypofractionated RT by analyzing cell death, immune checkpoint molecule (ICM) expression and activation of human monocyte-derived dendritic cells (DCs). MDA-MB-231 triple-negative breast cancer tumor cells were used as model system. Apoptosis was the dominant cell death form of brain metastasizing tumor cells, while Hsp70 release was generally significantly increased following RT and went along with necrosis induction. The ICMs PD-L1, PD-L2, HVEM, ICOS-L, CD137-L and OX40-L were found on the tumor cell surfaces and were significantly upregulated by RT with 5 x 5.2 Gy. Strikingly, the expression of immune suppressive ICMs was significantly higher on radioresistant clones compared to their respective non-radioresistant ones. Although hypofractionated RT led to significant cell death induction and release of Hsp70 in all tumor cell lines, human monocyte-derived DCs were not activated after co-incubation with RT-treated tumor cells. We conclude that radioresistance is a potent driver of immune suppressive ICM expression on the surface of TNBC MDA-MB-231 cells. This mechanism is generally known to predominantly influence the effector phase, rather than the priming phase, of anti-tumor immune responses.
CRIS-Team Scopus Importer:2023-05-19
Keywords: breast cancer; dendritic cells; immune checkpoint molecules; radioresistance; radiotherapy; tumor cell death

Combination of gas plasma and radiotherapy has immunostimulatory potential and additive toxicity in murine melanoma cells in vitro - Pasqual-Melo, Gabriella; Sagwal, Sanjeev Kumar; Freund, Eric; Gandhirajan, Rajesh Kumar; Frey, Benjamin; von Woedtke, Thomas; Gaipl, Udo; Bekeschus, Sander (International Journal of Molecular Sciences, 2020)
Despite continuous advances in therapy, malignant melanoma is still among the deadliest types of cancer. At the same time, owing to its high plasticity and immunogenicity, melanoma is regarded as a model tumor entity when testing new treatment approaches. Cold physical plasma is a novel anticancer tool that utilizes a plethora of reactive oxygen species (ROS) being deposited on the target cells and tissues. To test whether plasma treatment would enhance the toxicity of an established antitumor therapy, ionizing radiation, we combined both physical treatment modalities targeting B16F10 murine melanoma cell in vitro. Repeated rather than single radiotherapy, in combination with gas plasma-introduced ROS, induced apoptosis and cell cycle arrest in an additive fashion. In tendency, gas plasma treatment sensitized the cells to subsequent radiotherapy rather than the other way around. This was concomitant with increased levels of TNFα, IL6, and GM-CSF in supernatants. Murine JAWS dendritic cells cultured in these supernatants showed an increased expression of cell surface activation markers, such as MHCII and CD83. For PD-L1 and PD-L2, increased expression was observed. Our results are the first to suggest an additive therapeutic effect of gas plasma and radiotherapy, and translational tumor models are needed to develop this concept further.
CRIS-Team Scopus Importer:2020-02-28
Keywords: KINPen; Oncology; Plasma medicine; Reactive oxygen species; ROS

Combination of ionising radiation with hyperthermia increases the immunogenic potential of B16-F10 melanoma cells in vitro and in vivo - Werthmöller, Nina; Frey, Benjamin; Rueckert, Michael; Lotter, Michael; Fietkau, Rainer; Gaipl, Udo (International Journal of Hyperthermia, 2016)
Mild hyperthermia (HT) (41.5 °C for 30-60 min) has been shown in various cell culture systems, preclinical and clinical models to be a very potent radiosensitiser. Recent research suggests that local HT application in combination with standard tumour therapies such as radiotherapy (RT) and/or chemotherapy may not only improve local tumour control but also lead to systemic and immune mediated anti-tumour responses. Melanoma has been proven to be rather radioresistant and mostly only the addition of immunotherapy is capable of inducing beneficial anti-melanoma responses. This work therefore focuses on whether HT increases the immunogenic potential of B16-F10 mouse melanoma cells in combination with RT. The in vitro experiments revealed that combination of RT with HT resulted in an increased percentage of apoptotic and necrotic melanoma cells and an increased release of the danger signal heat shock protein 70 (Hsp70) and high mobility group box protein 1 (HMGB1). HT alone was also capable of inducing this release. We set up local irradiation and heating procedures of B16-F10 tumour-bearing C57/BL6 mice and revealed that the tumour growth of tumours treated with RT plus HT was significantly retarded compared to tumours treated only with RT. This combined treatment generated a beneficial tumour microenvironment by enhancing the infiltration of CD11c + /MHCII + /CD86+ dendritic cells, CD8+ T cells, and NK cells, and decreasing that of regulatory T cells and myeloid-derived suppressor cells. We conclude that HT in combination with RT has an immune-stimulating potential that might result in anti-tumour immunity.
EVALuna2:18340

Combinations of radiotherapy with vaccination and immune checkpoint inhibition differently affect primary and abscopal tumor growth and the tumor microenvironment - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo (Cancers, 2021)
Radiotherapy (RT) is known to have immune‐modulatory properties. We hypothesized that RT and inactivated whole tumor cell vaccines generated with high hydrostatic pressure (HHP) synergize to retard the tumor growth which can be additionally improved with anti‐PD‐1 treatment. In abscopal tumor models, we injected mice with B16‐F10 melanoma or TS/A mammary tumors. To evaluate the efficiency of RT in combination with HHP vaccines, we locally irradiated only one tumor with 2 × 8 Gy or 3 × 8 Gy. HHP vaccines further retarded the growth of locally irradiated (2 × 8 Gy) tumors. However, HHP vaccination combined with RT failed to induce abscopal anti‐tumor immune responses, namely those to non‐irradiated tumors, and even partly abrogated those which were induced with RT plus anti‐PD‐1. In the latter group, the abscopal effects were accompanied by an elevated infiltration of CD8+ T cells, monocytes/macrophages, and dendritic cells. 3 × 8 Gy failed to induce abscopal effects in association with increased expression of immunosuppressive checkpoint molecules compared to 2 × 8 Gy. We conclude that HHP vaccines induce anti‐tumor effects, but only if the tumor microenvironment was previously modulated by hypofractionated RT with not too many fractions, but failed to improve RT plus anti‐PD‐induced abscopal responses that are characterized by distinct immune alterations.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Abscopal effect; High hydrostatic pressure; Immune checkpoint inhibition; Radiotherapy; Tumor microenvironment; Tumor‐infiltrating immune cells; Vaccination

Common RUNX3 missense variant contributes to psoriatic arthritis by modifying differentiation of CD8(+) T-cells - Kerker, Iris; Löhr, Sabine; Uebe, Steffen; Popp, Bernt; Vasileiou, Georgia; Bowes, John; Kirchner, Philipp; Becker, Ina; Giardina, Emiliano; Korendowych, Eleanor; Ekici, Arif Bülent; Ho, Pauline; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2022)
CRIS-Team WoS Importer:2022-05-06

Comparative study and simulation of tumor cell inactivation by microwave and conventional heating - Rosin, Andreas; Hader, Michael; Drescher, Corinna; Suntinger, Magdalena; Gerdes, Thorsten; Willert-Porada, Monika; Gaipl, Udo; Frey, Benjamin (Compel-The International Journal For Computation and Mathematics in Electrical and Electronic Engineering, 2018)
Purpose This paper aims to investigate in a self-designed closed loop reactor process conditions for thermal inactivation of B16 melanoma cells by microwave and conventional heating. Design/methodology/approach Besides control experiments (37 degrees C), inactivation rate was determined in the range from 42 degrees C to 46 degrees C. Heating was achieved either by microwave radiation at 2.45 GHz or by warm water. To distinguish viable from dead cells, AnnexinV staining method was used and supported by field effect scanning electron microscopy (FE-SEM) imaging. Furthermore, numerical simulations were done to get a closer look into both heating devices. To investigate the thermal influence on cell inactivation and the differences between heating methods, a reaction kinetics approach was added as well. Findings Control experiments and heating at 42 degrees C resulted in low inactivation rates. Inactivation rate at 44 degrees C remained below 12% under conventional, whereas it increased to >70% under microwave heating. At 46 degrees C, inactivation rate attained 68% under conventional heating; meanwhile, even 88% were determined under microwave heating. FE-SEM images showed a porous membrane structure under microwave heating in contrast to mostly intact conventional heated cells. Numerical simulations of both heating devices and a macroscopic Arrhenius approach could not sufficiently explain the observed differences in inactivation. Originality/value A combination of thermal and electrical effects owing to microwave heating results in higher inactivation rates than conventional heating achieves. Nevertheless, it was not possible to determine the exact mechanisms of inactivation under microwave radiation.
EVALuna2:36524

Complete Remission with consecutive Pneumonitis in metastatic Bronchogenic Carcinoma after combination of Radiotherapy and Nivolumab - Immunological Correlate in peripheral Blood - Hecht, Markus; Donaubauer, Anna-Jasmina; Becker, I.; Rutzner, Sandra; Lubgan, Dorota; Lettmaier, S.; Haderlein, Marlen; Wolf, W.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Complex-valued neural networks to speed-up MR thermometry during hyperthermia using Fourier PD and PDUNet - Khatun, Rupali; Chatterjee, Soumick; Bert, Christoph; Wadepohl, Martin; Ott, Oliver; Semrau, Sabine; Fietkau, Rainer; Nürnberger, Andreas; Gaipl, Udo; Frey, Benjamin (Scientific Reports, 2025)
Hyperthermia (HT) in combination with radio- and/or chemotherapy has become an accepted cancer treatment for distinct solid tumour entities. In HT, tumour tissue is exogenously heated to temperatures between 39 and 43 °C for 60 min. Temperature monitoring can be performed non-invasively using dynamic magnetic resonance imaging (MRI). However, the slow nature of MRI leads to motion artefacts in the images due to the movements of patients during image acquisition. By discarding parts of the data, the speed of the acquisition can be increased - known as undersampling. However, due to the invalidation of the Nyquist criterion, the acquired images might be blurry and can also produce aliasing artefacts. The aim of this work was, therefore, to reconstruct highly undersampled MR thermometry acquisitions with better resolution and with fewer artefacts compared to conventional methods. The use of deep learning in the medical field has emerged in recent times, and various studies have shown that deep learning has the potential to solve inverse problems such as MR image reconstruction. However, most of the published work only focuses on the magnitude images, while the phase images are ignored, which are fundamental requirements for MR thermometry. This work, for the first time, presents deep learning-based solutions for reconstructing undersampled MR thermometry data. Two different deep learning models have been employed here, the Fourier Primal-Dual network and the Fourier Primal-Dual UNet, to reconstruct highly undersampled complex images of MR thermometry. MR images of 44 patients with different sarcoma types who received HT treatment in combination with radiotherapy and/or chemotherapy were used in this study. The method reduced the temperature difference between the undersampled MRIs and the fully sampled MRIs from 1.3 to 0.6 °C in full volume and 0.49 °C to 0.06 °C in the tumour region for a theoretical acceleration factor of 10.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Complex image; Deep learning; Hyperthermia; MR image reconstruction; MR reconstruction; MR thermometry; MRI; Undersampled; Undersampled MRI

Comprehensive Analysis of Non-coding RNAs Expression Profile and miRNA- circRNA-gene Co-expression Network in Developing Uterine Carcinosarcoma - Chen, Min Jun; Yang, Ling; Huang, Yue; Wang, Yunjia; Cai, Ying; Zhang, Chi; Jin, Su Han; Frey, Benjamin; Gaipl, Udo; Liu, Yuan; Ma, Hu; Zhou, Jian Guo (Technology in Cancer Research & Treatment, 2024)
Objectives: Uterine carcinosarcoma (UCS), often presenting at the advanced stage, is a rare, aggressive form of uterine cancer. We conduct a prospective cohort study by systematically study whole transcriptome sequencing data of uterine carcinosarcoma to gain further insights into the transcriptomic landscape and molecular mechanism of UCS. Methods: RNAs were extracted from tissue samples from five UCS patients and three corresponding non-tumorous tissues adjacent, followed by Illumina sequencing technology for high-throughput sequencing. A functional clustering analysis of differentially expressed genes was subsequently conducted. Results: We identified 1650 upregulated and 1753 downregulated circRNAs, 1632 upregulated and 460 downregulated lncRNAs. The differentially expressed genes (DEGs) mainly involve in IL-7 receptor-based signaling, MAPK signaling pathway, PD-L1 expression and PD-L1 checkpoint pathway and so on. An miRNA-circRNA-gene co-expression network reveals the top five correlated genes, miRNAs and circRNAs in developing UCS. Conclusion: In conclusion, we reveals the non-coding RNAs expression profile and a novel miRNA-circRNA-gene co-expression network shows correlated RNAs and genes in developing UCS. These profiles and correlated RNAs and genes may be potential pathways and targets in the diagnosis and treatment in developing UCS.
CRIS-Team Scopus Importer:2025-02-04
Keywords: circRNA; lncRNA; miRNA; RNA sequencing; transcriptome sequencing; uterine carcinosarcoma (UCS)

Comprehensive Multimodal Deep Learning Survival Prediction Enabled by a Transformer Architecture: A Multicenter Study in Glioblastoma - Gomaa, Ahmed; Huang, Yixing; Hagag, Amr; Schmitter, Charlotte; Höfler, Daniel; Weissmann, Thomas; Breininger, Katharina; Schmidt, Manuel; Stritzelberger, Jenny; Delev, Daniel; Coras, Roland; Dörfler, Arnd; et al. (Neuro-Oncology Advances, 2024)
Keywords: Survival prediction; deep learning; glioblastoma; MR; prognosis; multimodal data

Contribution of the immune system to bystander and non-targeted effects of ionizing radiation - Roedel, Franz; Frey, Benjamin; Multhoff, Gabriele; Gaipl, Udo (Cancer Letters, 2015)
Considerable progress has recently been achieved in the understanding of molecular mechanisms involved in cellular radiation responses and radiation mediated microenvironmental communication. In line with that, it has become more and more obvious that X-irradiation causes distinct immunological effects ranging from anti-inflammatory activities if applied at low (<1 Gy) doses to harmful inflammatory side effects, radiation-induced immune modulation or induction of anti-tumour immune responses at higher doses. Moreover, experimental and clinical evidences indicate that these effects not only originate from direct nuclear damage but also include non-(DNA) targeted mechanisms including bystander, out of field distant bystander (abscopal) effects and genomic instability. The purpose of the present review is to elucidate immune responses that are initiated or affected by ionizing radiation, with a special emphasis on anti-inflammatory and abscopal effects and the induction of stress-induced anti-tumour immunity.
EVALuna2:18184

Correction to: Innovative radiation oncology Together—Precise, Personalized, Human: Vision 2030 for radiotherapy & radiation oncology in Germany (Strahlentherapie und Onkologie, (2021), 197, 12, (1043-1048), 10.1007/s00066-021-01843-9) - Krug, David; Hecht, Markus; Ebert, Nadja; Maurer, Matthias; Fleischmann, Daniel F.; Fokas, Emmanouil; Straube, Christoph; Nicolay, Nils Henrik; Horner-Rieber, Juliane; Schmitt, Daniela; Von Neubeck, Clare; Zamboglou, Constantinos; et al. (Strahlentherapie und Onkologie, 2021)
The original version of this article unfortunately contained mistakes. The name of the author Hess was corrected. Fig. 1 contained orthographic errors. Additionally, to ensure that the hyperlinks embedded in Fig. 1 can be accessed, Fig. 1 was added as Supplement 3. A reference to Supplement 3 has been added in the description of Fig. 1 in the article. The original article has been corrected.
CRIS-Team Scopus Importer:2021-11-26

Corrigendum: Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial(Front. Immunol., (2021), 12, (740742), 10.3389/fimmu.2021.740742) - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2022)
In the original article, there was an error. The mistake is found in the sentence “While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells.” in the abstract of the article.
CRIS-Team Scopus Importer:2022-03-04
Keywords: chronic degenerative and inflammatory diseases; immune status; immunophenotyping; low dose radiation therapy (LDRT); subjective pain level; x-rays

Creation of an Electro-magnetic Heat Simulation for Planning Hyperthermia Treatments for Mice - Kahlert, B.; Bert, Christoph; Rückert, Michael; Hensel, Bernhard; Root, Konstantin; Vossiek, Martin; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

CRISPR-Cas9 Screen Identifies DYRK1A as a Target for Radiotherapy Sensitization in Pancreatic Cancer - Lan, Bin; Zeng, Siyuan; Zhang, Shuman; Ren, Xiaofan; Xing, Yuming; Kutschick, Isabella; Pfeffer, Sina; Frey, Benjamin; Britzen-Laurent, Nathalie; Grützmann, Robert; Cordes, Nils; Pilarsky, Christian (Cancers, 2022)
Although radiation therapy has recently made great advances in cancer treatment, the majority of patients diagnosed with pancreatic cancer (PC) cannot achieve satisfactory outcomes due to intrinsic and acquired radioresistance. Identifying the molecular mechanisms that impair the efficacy of radiotherapy and targeting these pathways are essential to improve the radiation response of PC patients. Our goal is to identify sensitive targets for pancreatic cancer radiotherapy (RT) using the kinome-wide CRISPR-Cas9 loss-of-function screen and enhance the therapeutic effect through the development and application of targeted inhibitors combined with radiotherapy. We transduced pancreatic cancer cells with a protein kinase library; 2D and 3D library cells were irradiated daily with a single dose of up to 2 Gy for 4 weeks for a total of 40 Gy using an X-ray generator. Sufficient DNA was collected for next-generation deep sequencing to identify candidate genes. In this study, we identified several cell cycle checkpoint kinases and DNA damage related kinases in 2D-and 3D-cultivated cells, including DYRK1A, whose loss of function sensitizes cells to radiotherapy. Additionally, we demonstrated that the harmine-targeted suppression of DYRK1A used in conjunction with radiotherapy increases DNA double-strand breaks (DSBs) and impairs homologous repair (HR), resulting in more cancer cell death. Our results support the use of CRISPR-Cas9 screening to identify new therapeutic targets, develop radiosensitizers, and provide novel strategies for overcoming the tolerance of pancreatic cancer to radiotherapy.
CRIS-Team Scopus Importer:2022-01-14
Keywords: CRISPR-Cas9; DNA damage repair; DNA double-strand break; DYRK1A; Harmine; Pancreatic cancer; Radioresistance; Radiotherapy

CtDNA release mechanisms in a therapeutic Ewing Sarcoma mouse model - Eiblwieser, Johanna; Krumbholz, Manuela; Semper, S.; Frey, Benjamin; Nagel, L.; Bäuerle, Tobias; Metzler, Markus (KLINISCHE PADIATRIE, 2022)
CRIS-Team WoS Importer:2022-07-08

Cytotoxic and immunogenic Potential of Iron (II) Clathrochelates and Irradiation on Lung Cancer Cell Lines - Becker, Ina; Denzler, M.; Heim, Lisanne; Klemt, Insa; Voloshin, Y. Z.; Selin, R.; Mokhir, Andriy; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Decrease of Markers Related to Bone Erosion in Serum of Patients with Musculoskeletal Disorders after Serial Low-Dose Radon Spa Therapy - Cucu, Aljona; Shreder, Kateryna; Kraft, Daniela; Ruhle, Paul Friedrich; Klein, Gerhart; Thiel, Gerhard; Frey, Benjamin; Gaipl, Udo; Fournier, Claudia (Frontiers in Immunology, 2017)
Musculoskeletal disorders (MSDs) are the most frequent cause of disability in Europe. Reduced mobility and quality of life of the patients are often associated with pain due to chronic inflammation. The inflammatory process, accompanied by a destruction of the cartilage and bone tissue, is discussed as a result of (A) the infiltration of immune cells into the joints, (B) an altered homeostasis of the joint cavity (synovium) with a critical role of bone remodeling cells, and (C) release of inflammatory factors including adipokines in the arthritic joint. In addition to the classical medication, low-dose radiation therapy using photons or radon spa treatments has shown to reduce pain and improve the mobility of the patients. However, the cellular and molecular mechanisms of anti-inflammatory effects of radon are yet poorly understood. We analyzed blood and serum samples from 32 patients, suffering from MSDs, who had been treated in the radon spa in Bad Steben (Germany). Before and after therapy, we measured the levels of markers related to bone metabolism (collagen fragments type-1, cartilage oligomeric matrix protein, receptor activator of NFκB ligand, and osteoprotegerin) in the serum of patients. In addition, adipokines related to inflammation (visfatin, leptin, resistin, and adiponectin) were analyzed. Some of these factors are known to correlate with disease activity. Since T cells play an important role in the progression of the disease, we further analyzed in blood samples the frequency of pro- and anti-inflammatory T cell subpopulations (CD4+IL17+T cells and CD4+FoxP3+regulatory T cells). Overall, we found a decrease of collagen fragments (CTX-I), indicating decreased bone resorption, presumably by osteoclasts, in the serum of MSD patients. We also observed reduced levels of visfatin and a consistent trend toward an increase of regulatory T cells in the peripheral blood, both indicating attenuation of inflammation. However, key proteins of bone metabolism were unchanged on a systemic level, suggesting that these factors act locally after radon spa therapy of patients with MSDs.
EVALuna2:32927

Deep Learning and Registration-Based Mapping for Analyzing the Distribution of Nodal Metastases in Head and Neck Cancer Cohorts: Informing Optimal Radiotherapy Target Volume Design - Weissmann, Thomas; Mansoorian, Sina; May, Matthias; Lettmaier, Sebastian; Höfler, Daniel; Deloch, Lisa; Speer, Stefan; Balk, Matthias; Frey, Benjamin; Gaipl, Udo; Bert, Christoph; Distel, Luitpold; et al. (Cancers, 2023)
We introduce a deep-learning- and a registration-based method for automatically analyzing the spatial distribution of nodal metastases (LNs) in head and neck (H/N) cancer cohorts to inform radiotherapy (RT) target volume design. The two methods are evaluated in a cohort of 193 H/N patients/planning CTs with a total of 449 LNs. In the deep learning method, a previously developed nnU-Net 3D/2D ensemble model is used to autosegment 20 H/N levels, with each LN subsequently being algorithmically assigned to the closest-level autosegmentation. In the nonrigid-registration-based mapping method, LNs are mapped into a calculated template CT representing the cohort-average patient anatomy, and kernel density estimation is employed to estimate the underlying average 3D-LN probability distribution allowing for analysis and visualization without prespecified level definitions. Multireader assessment by three radio-oncologists with majority voting was used to evaluate the deep learning method and obtain the ground-truth distribution. For the mapping technique, the proportion of LNs predicted by the 3D probability distribution for each level was calculated and compared to the deep learning and ground-truth distributions. As determined by a multireader review with majority voting, the deep learning method correctly categorized all 449 LNs to their respective levels. Level 2 showed the highest LN involvement (59.0%). The level involvement predicted by the mapping technique was consistent with the ground-truth distribution (p for difference 0.915). Application of the proposed methods to multicenter cohorts with selected H/N tumor subtypes for informing optimal RT target volume design is promising.<br
Keywords: deep learning; artificial intelligence; nodal metastasis; head and neck cancer; radiotherapy; target volume design; atlas; mapping; autosegmentation; lymph node level classification

Deep Learning-assisted delineation of brain metastases: a workflow focusing on AI-expert interaction - Putz, Florian; Szkitsak, Juliane; Grigo, Johanna; Masitho, Siti; Weissmann, Thomas; Frey, Benjamin; Gaipl, Udo; Fietkau, Rainer; Bert, Christoph; Huang, Yixing (Radiotherapy and Oncology, 2023)

Deep Learning-based Auto-contouring of Lymph Node Levels in Head and Neck Area - Weissmann, Thomas; Huang, Yixing; Sommer, Phillip; Roesch, Johannes; Mansoorian, Sina; Ayala, H.; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Haderlein, Marlen; Hecht, Markus; Speer, Stefan; Schweizer, Claudia; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep Learning based fully automated volumetric Progression Assessment in Patients with Brain Metastases after stereotactic Radiotherapy - Putz, Florian; Huang, Yixing; Weissmann, Thomas; Mansoorian, Sina; Sommer, P.; Fischer, S.; Srinivasan, A.; Frey, Benjamin; Gaipl, Udo; Schmidt, M.; Semrau, Sabine; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Deep learning for automatic head and neck lymph node level delineation provides expert-level accuracy - Weissmann, Thomas; Huang, Yixing; Fischer, Stefan; Roesch, Johannes; Mansoorian, Sina; Gaona, Horacio Ayala; Gostian, Antoniu-Oreste; Hecht, Markus; Lettmaier, Sebastian; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Oncology, 2023)
Background: Deep learning-based head and neck lymph node level (HN_LNL) autodelineation is of high relevance to radiotherapy research and clinical treatment planning but still underinvestigated in academic literature. In particular, there is no publicly available open-source solution for large-scale autosegmentation of HN_LNL in the research setting. Methods: An expert-delineated cohort of 35 planning CTs was used for training of an nnU-net 3D-fullres/2D-ensemble model for autosegmentation of 20 different HN_LNL. A second cohort acquired at the same institution later in time served as the test set (n = 20). In a completely blinded evaluation, 3 clinical experts rated the quality of deep learning autosegmentations in a head-to-head comparison with expert-created contours. For a subgroup of 10 cases, intraobserver variability was compared to the average deep learning autosegmentation accuracy on the original and recontoured set of expert segmentations. A postprocessing step to adjust craniocaudal boundaries of level autosegmentations to the CT slice plane was introduced and the effect of autocontour consistency with CT slice plane orientation on geometric accuracy and expert rating was investigated. Results: Blinded expert ratings for deep learning segmentations and expert-created contours were not significantly different. Deep learning segmentations with slice plane adjustment were rated numerically higher (mean, 81.0 vs. 79.6, p = 0.185) and deep learning segmentations without slice plane adjustment were rated numerically lower (77.2 vs. 79.6, p = 0.167) than manually drawn contours. In a head-to-head comparison, deep learning segmentations with CT slice plane adjustment were rated significantly better than deep learning contours without slice plane adjustment (81.0 vs. 77.2, p = 0.004). Geometric accuracy of deep learning segmentations was not different from intraobserver variability (mean Dice per level, 0.76 vs. 0.77, p = 0.307). Clinical significance of contour consistency with CT slice plane orientation was not represented by geometric accuracy metrics (volumetric Dice, 0.78 vs. 0.78, p = 0.703). Conclusions: We show that a nnU-net 3D-fullres/2D-ensemble model can be used for highly accurate autodelineation of HN_LNL using only a limited training dataset that is ideally suited for large-scale standardized autodelineation of HN_LNL in the research setting. Geometric accuracy metrics are only an imperfect surrogate for blinded expert rating. <
Keywords: Deep learning; lymph node level; segmentation

Deep learning for brain metastasis detection and segmentation in longitudinal MRI data - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Medical Physics, 2022)
Keywords: Deep learning; brain metastasis; MRI; loss function; sensitivity specificity

Defining intra-tumoral and systemic immune biomarkers for locally advanced head-and-neck cancer – detailed protocol of a prospective, observatory multicenter trial (ImmunBioKHT) and first results of the immunophenotyping of the patients’ peripheral blood - Donaubauer, Anna-Jasmina; Frey, Benjamin; Weber, Manuel; Allner, Moritz; Vogl, Christoph; Almajali, Omar; Kuczera, Lukas; Tamse, Henriette; Balk, Matthias; Müller-Hübner, Sarina Katrin Ursel; Eckstein, Markus; Zülch, Lilli; et al. (Frontiers in Oncology, 2024)
The approval and effectiveness of immune checkpoint inhibitors in head-and-neck squamous cell carcinoma (HNSCC) highlights the role of the immune system in this tumor entity. HNSCCs not only interacts with the immune system in the tumor tissue, but also induce systemic effects that may be additionally influenced by further factors such as the microbiome. Nonetheless, reliable immunological biomarkers that predict treatment response and outcome in HNSCC patients are lacking. The currently available biomarkers are mainly limited to analyses from tumor biopsies, while biomarkers from liquid biopsies, such as peripheral blood are not well-established. Thus, the here presented trial aims to identify interactions of intra-tumoral and systemic immune responses and to define prognostic immune signatures. Consequently, not only samples from the tumor tissue, but also from peripheral blood and the microbiome will be studied/are being evaluated and correlated with the clinical outcome. In this prospective, multi-center trial, 1000 HNSCC patients and 100 patients in the control cohort with non-tumor head-and-neck surgery will be enrolled. The local immune status from of the tumor and the microbiome will be sampled before treatment. In addition, the systemic immune status from peripheral blood will be analyzed before and after surgery and after the adjuvant and definitive radio-chemotherapy (RCT). Clinical baseline characteristics and outcome will additionally be collected. Data mining and modelling approaches will finally be applied to identify interactions of local and systemic immune parameters and to define prognostic immune signatures based on the evaluated immune markers. Approval from the institutional review board of the Friedrich-Alexander-Universität Erlangen-Nürnberg was granted in December 2021 (application number 21-440-B). By now, 150 patients have been enrolled in the intervention cohort. The results will be disseminated to the scientific audience and the general public via presentations at conferences and publication in peer-reviewed journal
CRIS-Team Scopus Importer:2024-10-04
Keywords: HNSCC; immune monitoring; immunological biomarker; liquid biopsy; prospective clinical trial

Defining metaniches in the oral cavity according to their microbial composition and cytokine profile - Seidel, Corinna Lesley; Gerlach, Roman; Wiedemann, Patrick; Weider, Matthias; Rodrian, Gabriele; Hader, Michael; Frey, Benjamin; Gaipl, Udo; Bozec, Aline; Cieplik, Fabian; Kirschneck, Christian; Bogdan, Christian; et al. (International Journal of Molecular Sciences, 2020)
The human oral microbiota consists of over 700 widespread taxa colonizing the oral cavity in several anatomically diverse oral niches. Lately, sequencing of the 16S rRNA genes has become an acknowledged, culture-independent method to characterize the oral microbiota. However, only a small amount of data are available concerning microbial differences between oral niches in periodontal health and disease. In the context of periodontitis, the cytokine expression in the gingival crevicular fluid has been studied in detail, whereas little is known about the cytokine profile in hard and soft tissue biofilms. In order to characterize oral niches in periodontal health, the oral microbiota and cytokine pattern were analyzed at seven different sites (plaque (P), gingival crevicular fluid (GCF), saliva (S), tongue (T), hard palate (HP), cheek (C) and sublingual area (U)) of 20 young adults using next-generation sequencing and multiplex immunoassays. Site-specific microbial compositions were detected, which clustered into three distinct metaniches (“P-GCF”, “S-T-HP” and “C-U”) and were associated with niche-/metaniche-specific cytokine profiles. Our findings allow the definition of distinct metaniches according to their microbial composition, partly reflected by their cytokine profile, and provide new insights into microenvironmental similarities between anatomical diverse oral niches.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Cytokine profile; Metaniches; Multiplex immunoassay; Next-generation sequencing; Oral biofilms and fluids; Oral microbiota; Oral niches

Definition of a new blood cell count score for early survival prediction for non-small cell lung cancer patients treated with atezolizumab: Integrated analysis of four multicenter clinical trials - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Jin, Su-Han; Tan, Fangya; Chen, Yu-Zhong; He, Si-Si; Shen, Gang; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Carr, Shamus R.; et al. (Frontiers in Immunology, 2022)
Importance: Blood cell count test (BCT) is a robust method that provides direct quantification of various types of immune cells to reveal the immune landscape to predict atezolizumab treatment outcomes for clinicians to decide the next phase of treatment. Objective: This study aims to define a new BCTscore model to predict atezolizumab treatment benefits in non-small lung cell cancer (NSCLC) patients. Design, Setting, and Participants: This study analyzed four international, multicenter clinical trials (OAK, BIRCH, POPLAR, and FIR trials) to conduct post-hoc analyses of NSCLC patients undergoing atezolizumab (anti–PD-L1) single-agent treatment (n = 1,479) or docetaxel single-agent treatment (n = 707). BCT was conducted at three time points: pre-treatment (T1), the first day of treatment cycle 3 (T2), and first day of treatment cycle 5 (T3). Univariate and multivariate Cox regression analyses were conducted to identify early BCT biomarkers to predict atezolizumab treatment outcomes in NSCLC patients. Main Outcomes and Measures: Overall survival (OS) was used as the primary end point, whereas progression-free survival (PFS) according to Response Evaluation Criteria in Solid Tumors (RECIST), clinical benefit (CB), and objective response rate (ORR) were used as secondary end points. Results: The BCT biomarkers of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) at time point T3 and neutrophil-to-monocyte ratio (NMR) at time point T2 with absolute cutoff values of NLR_T3 = 5, PLR_T3 = 180, and NMR_T2 = 6 were identified as strong predictive biomarkers for atezolizumab (Ate)–treated NSCLC patients in comparison with docetaxel (Dtx)–treated patients regarding OS (BCTscore low risk: HR Ate vs. Dtx = 1.54 (95% CI: 1.04–2.27), P = 0.031; high risk: HR Ate vs. Dtx = 0.84 (95% CI: 0.62–1.12), P = 0.235). The identified BCTscore model showed better OS AUC in the OAK (AUC12month = 0.696), BIRCH (AUC12month = 0.672) and POPLAR+FIR studies (AUC12month = 0.727) than that of each of the three single BCT biomarkers. Conclusion and Relevance: The BCTscore model is a valid predictive and prognostic biomarker for early survival prediction in atezolizumab-treated NSCLC patients.
CRIS-Team Scopus Importer:2022-09-30
Keywords: atezolizumab; biomarker; blood cell count; clinical trial; NSCLC

De-intensification of postoperative radiotherapy in head and neck cancer irrespective of human papillomavirus status—results of a prospective multicenter phase II trial (DIREKHT Trial) - Haderlein, Marlen; von der Grün, Jens; Balermpas, Panagiotis; Rödel, Claus; Hautmann, Matthias G.; Steger, Felix; Bohr, Christopher; Hehr, Thomas; Stromberger, Carmen; Budach, Volker; Schymalla, Markus; Engenhart-Cabillic, Rita; et al. (Frontiers in Oncology, 2024)
Background: Current standard treatment concepts in head and neck squamous cell carcinoma (HNSCC) are based on former studies using 2D and 3D treatment plans. However, modern radiation techniques allow for a more precise and individual dose application. Therefore, in a clearly defined patient population, de-intensified risk-adapted radiation is investigated. Methods: Patients with newly diagnosed HNSCC after surgery (with resection margins ≥1 mm and cM0) with the following tumor stages (TNM 7th Edition) were eligible for the study: oral cavity, oropharynx, or larynx: pT1–3, pN0–pN2b; hypopharynx: pT1–2, pN1. The patients should have either a low risk of local recurrence [≤pT2, resection margin ≥5 mm, no peritumoral lymphangiosis (L0), and no perineural invasion] or contralateral lymph node metastasis (≤3 ipsilateral lymph node metastases, in case of well-lateralized oropharyngeal or oral cavity cancer contralateral cN0, otherwise pN0). Patients were assigned to three different treatment regimes with reduction of the treated volume, radiation dose, or both, according to tumor stage and results of surgery performed. The primary objective was to show an LRR of <10% after 2 years. Findings: A total of 150 patients were enrolled. Tumor localizations were as follows: n = 53 (35.3%), oral cavity; n = 94 (62.7%), oropharynx (82% HPV-positive); n = 2 (1.3%), hypopharynx; and n = 1 (0.7%), larynx. A total of 61 patients (41.0%) were stage IVA, 81 (54.0%) were stage III, and 8 (5.3%) were stage II. Median follow-up was 36 months. Cumulative incidence of 2y-LRR was 5.6% (95% CI: 1.7%–9.2%) in the whole study population and 14.1% (95% CI: 3.8%–23.2%) in patients with oral cavity cancer. Cumulative incidence of 2y-LRR in non-irradiated or dose-reduced regions was 3.5% (95% CI: 0.4%–6.5%). After 2 years, disease-free survival was 92% (95% CI: 87%–96%) and overall survival was 94% (95% CI: 90%–98%) for the complete study cohort. Acute III° toxicity was as follows: dysphagia, 30%; xerostomia, 7%; mucositis, 19%; and dermatitis, 4%. Dysphagia and xerostomia decrease over time. After 27 months, late dysphagia III° and xerostomia II° were 1% and 9%, respectively. Interpretation: The study met its primary objective. De-intensification of postoperative radiotherapy irrespective of HPV status in a predefined patient population is associated with a favorable toxicity profile without compromising LRR. In an unplanned subgroup analysis, a significantly increased risk of LRR was observed in patients with oral cavity cancer. In these patients, de-intensified radiotherapy should be applied with caution.
CRIS-Team Scopus Importer:2024-09-13
Keywords: de-intensification; head and neck cancer; HPV; postoperative; radiotherapy

Detailed in vitro analyses of the impact of multimodal cancer therapy with hyperthermia and radiotherapy on the immune phenotype of human glioblastoma cells - Stoll, Eileen; Hader, Michael; Rückert, Michael; Weissmann, Thomas; Lettmaier, Sebastian; Putz, Florian; Hecht, Markus; Fietkau, Rainer; Rosin, Andreas; Frey, Benjamin; Gaipl, Udo (International Journal of Hyperthermia, 2022)
Purpose Improvements of heat-delivery systems have led to hyperthermia (HT) being increasingly recognized as an adjunct treatment modality also for brain tumors. But how HT affects the immune phenotype of glioblastoma cells is only scarcely known. Materials and Methods We therefore investigated the effect of in vitro HT, radiotherapy (RT), and the combination of both (RHT) on cell death modalities, immune checkpoint molecule (ICM) expression and release of the danger signal HSP70 of two human glioblastoma cell lines (U87 and U251) by using multicolor flow cytometry and ELISA. Hyperthermia was performed once or twice for 60-minute sessions reaching temperatures of 39 degrees C, 41 degrees C, and 44 degrees C, respectively. RT was administered with 5 x 2 Gy. Results A hyperthermia chamber for cell culture t-flasks regulating the temperature via a contact sensor was developed. While the glioblastoma cells were rather radioresistant, particularly in U251 cells, the combination of RT with HT significantly increased the percentage of apoptotic and necrotic cells for all temperatures examined and for both, single and double HT application. In line with that, an increased release of HSP 70 was seen only in U251 cells, mainly following treatment with HT at temperatures of 44 degrees C alone or in combination with RT. In contrast, immune suppressive (PD-L1, PD-L2, HVEM) and immune stimulatory (ICOS-L, CD137-L and Ox40-L) ICMs were significantly increased mostly on U87 cells, and particularly after RHT with 41 degrees C. Conclusions Individual assessment of the glioblastoma immune cell phenotype with regard to the planned treatment is mandatory to optimize multimodal radio-immunotherapy protocols including HT.
CRIS-Team WoS Importer:2022-06-24
Keywords: Hyperthermia; radiotherapy; immune checkpoint molecules; danger signals; glioblastoma; multimodal cancer therapy

Detection of Human Cytomegalovirus (HCMV) in monocytic Cells of the peripheral Blood in Glioma Patients during Radio (chemo) Therapy - Bäumler, Monika; Becker, Ina; Frey, Benjamin; Pohn, Anna; Winkler, Thomas; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Development of a flow cytometry-based whole-blood prognostic immune signature in metastatic cancer patients treated with immune checkpoint inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Eckstein, Markus; Sun, R.; Ma, H.; Schubert, Philipp; Schweizer, C.; Fietkau, Rainer; Deutsch, E.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Development of a Modular Assay for Detailed Immunophenotyping of Peripheral Human Whole Blood Samples by Multicolor Flow Cytometry - Rühle, Paul-Friedrich; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (International Journal of Molecular Sciences, 2016)
The monitoring of immune cells gained great significance in prognosis and prediction of therapy responses. For analyzing blood samples, the multicolor flow cytometry has become the method of choice as it combines high specificity on single cell level with multiple parameters and high throughput. Here, we present a modular assay for the detailed immunophenotyping of blood (DIoB) that was optimized for an easy and direct application in whole blood samples. The DIoB assay characterizes 34 immune cell subsets that circulate the peripheral blood including all major immune cells such as T cells, B cells, natural killer (NK) cells, monocytes, dendritic cells (DCs), neutrophils, eosinophils, and basophils. In addition, it evaluates their functional state and a few non-leukocytes that also have been associated with the outcome of cancer therapy. This DIoB assay allows a longitudinal and close-meshed monitoring of a detailed immune status in patients requiring only 2.0 mL of peripheral blood and it is not restricted to peripheral blood mononuclear cells. It is currently applied for the immune monitoring of patients with glioblastoma multiforme (IMMO-GLIO-01 trial, NCT02022384), pancreatic cancer (CONKO-007 trial, NCT01827553), and head and neck cancer (DIREKHT trial, NCT02528955) and might pave the way for immune biomarker identification for prediction and prognosis of therapy outcome.
EVALuna2:18363

Development of an immunological prognostic Signature in metastatic Patients who were treated with Immune Checkpoint Inhibitors as part of the ST-ICI Study - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Sun, R.; Ma, H.; Fietkau, Rainer; Deutsch, E.; Hecht, Markus; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Differences of the immune phenotype of breast cancer cells after ex vivo hyperthermia by warm-water or microwave radiation in a closed-loop system alone or in combination with radiotherapy - Hader, Michael; Savcigil, Deniz Pinar; Rosin, Andreas; Ponfick, Philipp; Gekle, Stephan; Wadepohl, Martin; Bekeschus, Sander; Fietkau, Rainer; Frey, Benjamin; Schlücker, Eberhard; Gaipl, Udo (Cancers, 2020)
The treatment of breast cancer by radiotherapy can be complemented by hyperthermia. Little is known about how the immune phenotype of tumor cells is changed thereby, also in terms of a dependence on the heating method. We developed a sterile closed-loop system, using either a warm-water bath or a microwave at 2.45 GHz to examine the impact of ex vivo hyperthermia on cell death, the release of HSP70, and the expression of immune checkpoint molecules (ICMs) on MCF-7 and MDA-MB-231 breast cancer cells by multicolor flow cytometry and ELISA. Heating was performed between 39 and 44◦C. Numerical process simulations identified temperature distributions. Additionally, irradiation with 2 × 5 Gy or 5 × 2 Gy was applied. We observed a release of HSP70 after hyperthermia at all examined temperatures and independently of the heating method, but microwave heating was more effective in cell killing, and microwave heating with and without radiotherapy increased subsequent HSP70 concentrations. Adding hyperthermia to radiotherapy, dynamically or individually, affected the expression of the ICM PD-L1, PD-L2, HVEM, ICOS-L, CD137-L, OX40-L, CD27-L, and EGFR on breast cancer cells. Well-characterized pre-clinical heating systems are mandatory to screen the immune phenotype of tumor cells in clinically relevant settings to define immune matrices for therapy adaption.
CRIS-Team Scopus Importer:2020-05-08
Keywords: Breast cancer; Danger signals; EGFR; Hyperthermia; Immune checkpoint molecules; Immunogenic cancer cell phenotype; Immunotherapy; Microwave-heating; Multimodal tumor therapies; Radiotherapy

Distinguishing Progression and Radionecrosis in large progressive Brain Metastases after Stereotaxy by integrating Radiomics, Dose Radiomics and clinical Risk Factors - Sommer, Phillip; Huang, Yixing; Srinivasan, Aishwarya Lakshmi; Fischer, Stefan; Dörfler, Arnd; Schmidt, Manuel; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

DNA as the main target in radiotherapy—a historical overview from first isolation to anti-tumour immune response - Frey, Benjamin; Borgmann, Kerstin; Jost, Tina; Greve, Burkhard; Oertel, Michael; Micke, Oliver; Eckert, Franziska (Strahlentherapie und Onkologie, 2023)
DNA damage is one of the foremost mechanisms of irradiation at the biological level. After the first isolation of DNA by Friedrich Miescher in the 19th century, the structure of DNA was described by Watson and Crick. Several Nobel Prizes have been awarded for DNA-related discoveries. This review aims to describe the historical perspective of DNA in radiation biology. Over the decades, DNA damage has been identified and quantified after irradiation. Depending on the type of sensing, different proteins are involved in sensing DNA damage and repairing the damage, if possible. For double-strand breaks, the main repair mechanisms are non-homologous end joining and homologous recombination. Additional mechanisms are the Fanconi anaemia pathway and base excision repair. Different methods have been developed for the detection of DNA double-strand breaks. Several drugs have been developed that interfere with different DNA repair mechanisms, e.g., PARP inhibitors. These drugs have been established in the standard treatment of different tumour entities and are being applied in several clinical trials in combination with radiotherapy. Over the past decades, it has become apparent that DNA damage mechanisms are also directly linked to the immune response in tumours. For example, cytosolic DNA fragments activate the innate immune system via the cGAS STING pathway.
CRIS-Team Scopus Importer:2023-09-01
Keywords: DNA double-strand breaks; DNA repair; History; Immunooncology; Radiobiology

Dose reduction to the swallowing apparatus and the salivary glands by de-intensification of postoperative radiotherapy in patients with head and neck cancer: First (treatment planning) results of the prospective multicenter DIREKHT trial - Haderlein, Marlen; Speer, Stefan; Ott, Oliver; Lettmaier, Sebastian; Hecht, Markus; Semrau, Sabine; Frey, Benjamin; Scherl, Claudia; Iro, Heinrich; Kesting, Marco Rainer; Fietkau, Rainer (Cancers, 2020)
Aim: Evaluating radiotherapy treatment plans of the prospective DIREKHT trial (ClinicalTrials.gov, NCT02528955) investigating de-intensification of radiotherapy in patients with head and neck cancer. Patients and Methods: The first 30 patients from the DIREKHT trial of the leading study centre were included in this analysis. Standard treatment plans and study treatment plans derived from the protocol were calculated for each patient. Sizes of planning target volumes (PTVs) and mean doses to organs at risk were compared using the Student’s t-test with paired samples. Results: Mean PTV3 including primary tumor region and ipsilateral elective neck up to a dose of 50 Gy in the study treatment plans was 662 mL (+/− 165 mL standard deviation (SD)) and therefore significantly smaller than those of the standard treatment plans (1166 mL (+/− 266 mL SD). In the medial and inferior constrictor muscles, cricopharyngeal muscle, glottic and supraglottic laryngeal areas, arytenoid cartilages, contralateral major salivary glands highly significant dose reductions (p < 0.0001) of more than 10 Gy were achieved in study treatment plan compared to standard treatment plan. Conclusion: De-intensification of radiotherapy led to smaller planning target volumes and clinical relevant dose reductions in the swallowing apparatus and in the contralateral salivary glands.
CRIS-Team Scopus Importer:2020-03-06
Keywords: De-intensification; Head neck cancer; Ipsilateral elective neck irradiation only; Postoperative; Radiotherapy; Salivary glands; Swallowing apparatus

Drug priming enhances radiosensitivity of adamantinomatous craniopharyngioma via downregulation of survivin - Stache, Christina; Bils, Christiane; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Stefanits, Harald; Czech, Thomas; Gaipl, Udo; Frey, Benjamin; Buslei, Rolf; Hoelsken, Annett (Neurosurgical Focus, 2016)
OBJECTIVE In this study, the authors investigated the underlying mechanisms responsible for high tumor recurrence rates of adamantinomatous craniopharyngioma (ACP) after radiotherapy and developed new targeted treatment protocols to minimize recurrence. ACPs are characterized by the activation of the receptor tyrosine kinase epidermal growth factor receptor (EGFR), known to mediate radioresistance in various tumor entities. The impact of tyrosine kinase inhibitors (TKIs) gefitinib or CUDC-101 on radiation-induced cell death and associated regulation of survivin gene expression was evaluated. METHODS The hypothesis that activated EGFR promotes radioresistance in ACP was investigated in vitro using human primary cell cultures of ACP (n = 10). The effects of radiation (12 Gy) and combined radiochemotherapy on radiosensitivity were assessed via cell death analysis using flow cytometry. Changes in target gene expression were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR). Survivin, identified in qRT-PCR to be involved in radioresistance of ACP, was manipulated by small interfering RNA (siRNA), followed by proliferation and vitality assays to further clarify its role in ACP biology. Immunohistochemically, survivin expression was assessed in patient tumors used for primary cell cultures. RESULTS In primary human ACP cultures, activation of EGFR resulted in significantly reduced cell death levels after radiotherapy. Treatment with TKIs alone and in combination with radiotherapy increased cell death response remarkably, assessed by flow cytometry. CUDC-101 was significantly more effective than gefitinib. The authors identified regulation of survivin expression after therapeutic intervention as the underlying molecular mechanism of radioresistance in ACP. EGFR activation promoting ACP cell survival and proliferation in vitro is consistent with enhanced survivin gene expression shown by qRT-PCR. TKI treatment, as well as the combination with radiotherapy, reduced survivin levels in vitro. Accordingly, ACP showed reduced cell viability and proliferation after survivin downregulation by siRNA. CONCLUSIONS These results indicate an impact of EGFR signaling on radioresistance in ACP. Inhibition of EGFR activity by means of TKI treatment acts as a radiosensitizer on ACP tumor cells, leading to increased cell death. Additionally, the results emphasize the antiapoptotic and pro-proliferative role of survivin in ACP biology and its regulation by EGFR signaling. The suppression of survivin by treatment with TKI and combined radiotherapy represents a new promising treatment strategy that will be further assessed in in vivo models of ACP.
EVALuna2:7353

EARLY BLOOD CELL COUNT TEST (BCT) FOR SURVIVAL PREDICTION FOR NON-SMALL CELL LUNG CANCER PATIENTS TREATED WITH ATEZOLIZUMAB: INTEGRATED ANALYSIS OF 4 MULTICENTER CLINICAL TRIALS - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Jin, Su-Han; Tan, Fangya; Chen, Yu-Zhong; He, Si-Si; Shen, Gang; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Shen, Bo; et al. (JOURNAL FOR IMMUNOTHERAPY OF CANCER, 2021)
Immune checkpoint inhibitor (ICI) therapy is a major breakthrough for non-small cell lung cancer (NSCLC) treatment given its high efficacy and tolerable toxicity. Although pre-treatment PD-L1 expression levels and tumor mutation burden (TMB) may serve as prognostic biomarkers for patient stratification, effective predictive biomarkers are lacking. Blood cell count test (BCT) is a routine, regular blood test conducted before and during treatment to provide a direct overview of the immune landscape based on the counts of various types of immune cells (ICs). For instance, previous studies showed that neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) both indicate poor treatment outcomes of ICI therapy of NSCLC patients.<br
CRIS-Team WoS Importer:2022-04-15

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Editorial: Community series in immunotherapy with checkpoint inhibitors for non-small cell lung cancer, colon cancer, and esophageal cancer, volume II - Li, Yueyi; Wang, Yusha; Gao, Jinsheng; Tan, Keqin; Frey, Benjamin; Gaipl, Udo; Shi, Hubing; Ma, Xuelei (Frontiers in Immunology, 2023)
CRIS-Team Scopus Importer:2023-07-28
Keywords: colorectal cancer; editorial; esophageal cancer (EC); mmune checkpoint inhibitors (ICIs); non-small cell lung cancer (NSCLC)

Editorial: Immune-Related Adverse Events for Patients With Lung Cancer - Yang, Ruoning; Wang, Haiyang; Yin, Xiaomeng; Frey, Benjamin; Gaipl, Udo; Shi, Hubing; Ma, Xuelei (Frontiers in Oncology, 2022)
CRIS-Team WoS Importer:2022-05-27

Editorial: Immune-related adverse events for patients with lung cancer-volume II - Wang, Yusha; Wang, Xia; Zhan, Cheng; Frey, Benjamin; Gaipl, Udo; Shi, Hubing; Ma, Xuelei (Frontiers in Oncology, 2023)
CRIS-Team Scopus Importer:2023-12-15
Keywords: editorial; immune checkpoint inhibitors (ICIs); immune-related adverse events (irAEs); Immunotherapy; lung cancer

Editorial: Radiation and the Immune System: Current Knowledge and Future Perspectives - Lumniczky, Katalin; Candeias, Serge M.; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2017)
EVALuna2:32926

Editorial to radiation in multimodal tumor immune therapies—mechanisms and application - Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2021)
CRIS-Team Scopus Importer:2021-07-30

Effectiveness of ablative Irradiation of all Metastases versus Irradiation of a singular Metastasis in Combination with Immunocheckpoint Inhibitors - clinical Evaluation of prospective STICI Study - Schubert, P.; Schweizer, C.; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Effect of hyperthermia and radiation therapy sequence on cell death and the immune phenotype of breast cancer cells - Sengedorj, Azzaya; Hader, Michael; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Scheidegger, S.; Barba, S. M.; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effect of Radiotherapy and Chemotherapy on the Immunophenotype of Head and Neck Cancer Cells and the consecutive Activation of dendritic Cells - Grottker, F.; Frey, Benjamin; Gehre, S.; Reichardt, Clara; Sengedorj, Azzaya; Hecht, Markus; Fietkau, Rainer; Rieckmann, T.; Gostian, Antoniu-Oreste; Gaipl, Udo; Rückert, Michael (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effects of Radiotherapy on the Kinetics of Immune Checkpoint Molecule Expression in Tumor Cells and their radioresistant Clones - Siegert, Juliane; Rückert, Michael; Meyer, F.; Borgmann, K.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Effects of Radon-Spa-Therapy on Patients with musculoskeletal Diseases - Becker, Ina; Donaubauer, Anna-Jasmina; Klein, G.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Effects of serial radon spa therapy on pain and peripheral immune status in patients suffering from musculoskeletal disorders– results from a prospective, randomized, placebo-controlled trial - Donaubauer, Anna-Jasmina; Becker, Ina; Klein, Gerhart; Voll, Reinhard E.; Weikl, Lena; Klieser, Martin; Barzangi, Shakar; Zhou, Jianguo; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2024)
In this randomized, placebo-controlled cross-over trial we aimed to investigate if radon spa therapy exerts more pain relief than exposure to warm water alone. In addition, immunological parameters were assessed in both treatment groups. In the RAD-ON02 trial, 116 patients suffering from musculoskeletal disorders (MSDs) received either serial radon spa or solely warm water baths. Pain intensity was assessed by determination of different pain parameters on a visual analogue scale and by pressure point dolorimetry at baseline and at weeks 4, 12 and 24. The longitudinal immune status of the patients was analyzed by a flow cytometry-based assay from peripheral blood at the time points of pain assessments. There were no side effects attributable to radon exposure observed. However, radon spa was superior to warm water applications at week 4 in terms of pain reduction. Pain and morning stiffness at the time of assessment were significantly reduced after radon spa (p<0.001, p<0.01) but not after warm water baths. The dolorimetry resulted in a significantly higher exerted pressure strength in patients after radon spa (p<0.001), but not after warm water applications. During the long-term follow-up, both treatment modalities reduced pain to a similar degree and pain modulation was not distorted by the participants’ intake of analgesics. No significant changes in the immune status attributable specifically to radon were found, even though the increase in regulatory T cell counts occurs earlier after radon baths than after sole warm water baths and a higher level of significance is reached after radon spa at week 24. Serial radon spa has additive pain-relieving effects. The immunological parameters assessed in our study appear not to be directly linked to the pain reduction caused by radon exposure, at least in MSD patients with predominantly degenerative diseases. Clinical trial registration: https://www.clinicaltrialsregister.eu/ctr-search/search?query=rad-on02, identifier 2016-002085-31; https://drks.de/search/de/trial, identifier DRKS00016019.
CRIS-Team Scopus Importer:2024-03-01
Keywords: chronic degenerative and inflammatory diseases; chronic pain; musculoskeletal disorders; peripheral immune status; radon spa; randomized placebo-controlled trial

Efficacy of radiotherapy combined with atezolizumab or docetaxel in patients with previously treated NSCLC - Xu, Junzhu; Wang, Haitao; Zhang, Chi; Jin, Su Han; Chen, Xiaofei; Tan, Fangya; Frey, Benjamin; Hecht, Markus; Sun, Jian Guo; Gaipl, Udo; Ma, Hu; Zhou, Jian Guo (iScience, 2024)
Radiotherapy showed synergy with immunotherapy, yet the comparative effectiveness of combining immunotherapy (iRT) or chemotherapy (CRT) after platinum therapy failure in advanced non-small cell lung cancer (NSCLC) remains unexplored. We analyzed 163 patients (iRT: n = 120 vs. CRT: n = 43) eligible for combination radiotherapy. Before matching, median overall survival (OS) was significantly longer in iRT group (7.79 vs. 4.57 months, hazard ratio [HR]: 0.62, 95% confidence interval [CI]: 0.41–0.94, p = 0.024). After 1:2 propensity score matching (PSM) and inverse probability of treatment weighting (IPTW), iRT group showed improved OS, consistent with unmatched analysis (PSM, p = 0.033 and IPTW, p = 0.035). Exploratory analysis suggested that PD1+, central memory PD1+, and effector memory PD-L1+ CD4+ T cells were strong predictive biomarkers for iRT-treated patients (POS = 0.025, POS = 0.002, POS = 0.010, respectively). Proliferative CD4+ T celllow was a prognostic (POS = 0.008) and predictive biomarker for iRT (POS < 0.001). Our work revealed iRT was prolonged OS in previously treated advanced NSCLC patients. Additionally, proliferative CD4+ T cell served as prognostic and predictive biomarkers.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Cancer; Public health

Electrothermic effects of microwave heating on B16 melanoma cells - examinations with a semi-continuous plug flow-like reactor - Drescher, C.; Derer, Anja; Rosin, A.; Gerdes, T.; Willert-Porada, M.; Wadepohl, M.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32880

Elucidation of the Application of Blood Test Biomarkers to Predict Immune-Related Adverse Events in Atezolizumab-Treated NSCLC Patients Using Machine Learning Methods - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Tan, Fangya; Chen, Xiaofei; Jin, Su-Han; He, Si-Si; Shen, Gang; Wang, Yun-Jia; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; et al. (Frontiers in Immunology, 2022)
BackgroundDevelopment of severe immune-related adverse events (irAEs) is a major predicament to stop treatment with immune checkpoint inhibitors, even though tumor progression is suppressed. However, no effective early phase biomarker has been established to predict irAE until now. MethodThis study retrospectively used the data of four international, multi-center clinical trials to investigate the application of blood test biomarkers to predict irAEs in atezolizumab-treated advanced non-small cell lung cancer (NSCLC) patients. Seven machine learning methods were exploited to dissect the importance score of 21 blood test biomarkers after 1,000 simulations by the training cohort consisting of 80%, 70%, and 60% of the combined cohort with 1,320 eligible patients. ResultsXGBoost and LASSO exhibited the best performance in this study with relatively higher consistency between the training and test cohorts. The best area under the curve (AUC) was obtained by a 10-biomarker panel using the XGBoost method for the 8:2 training:test cohort ratio (training cohort AUC = 0.692, test cohort AUC = 0.681). This panel could be further narrowed down to a three-biomarker panel consisting of C-reactive protein (CRP), platelet-to-lymphocyte ratio (PLR), and thyroid-stimulating hormone (TSH) with a small median AUC difference using the XGBoost method [for the 8:2 training:test cohort ratio, training cohort AUC difference = -0.035 (p < 0.0001), and test cohort AUC difference = 0.001 (p=0.965)]. ConclusionBlood test biomarkers currently do not have sufficient predictive power to predict irAE development in atezolizumab-treated advanced NSCLC patients. Nevertheless, biomarkers related to adaptive immunity and liver or thyroid dysfunction warrant further investigation.
CRIS-Team WoS Importer:2022-07-29

Erratum to: Primary glioblastoma multiforme tumors and recurrence: comparative analysis of the danger signals HMGB1, HSP70, and calreticulin - Muth, Carolin; Rubner, Yvonne; Semrau, Sabine; Rühle, Paul-Friedrich; Frey, Benjamin; Strnad, Annedore; Buslei, Rolf; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2016)
EVALuna2:7315

Establishment of a FACS Assay for Screening of (TEMRA) Cells in Glioblastoma Patients - Scheer, I.; Becker, Ina; Donaubauer, Anna-Jasmina; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Establishment of a Multicolor Flow Cytometry Assay for Screening the NK Cells in Cancer Patients - Becker, Ina; Donaubauer, Anna-Jasmina; Multhoff, G.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Ex vivo heat treatment of B16 melanoma and MCF-7 breast cancer cells by warm-water or microwave radiation in a closed-loop reactor - Hader, M.; Rosin, A.; Blank, T.; Wadepohl, M.; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36520

Ex vivo Hyperthermia of B16 Melanoma and MCF-7/MDA-MB-231 Breast Cancer Cells by Hot Water or Microwave Irradiation in a Circulatory Process - Hader, Michael; Rosin, A.; Gekle, S.; Wadepohl, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Fibroblast-like Synoviocytes show Gender and Inflammatory Status-specific Responses on the Treatment with low-dose X-ray Therapy - Deloch, Lisa; Rueckert, M.; Piltz, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Flow cytometry-based monitoring of myeloid-derived suppressor cells in the peripheral blood of patients with solid tumors - Donaubauer, Anna-Jasmina; Scheer, Ilka; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Academic Press Inc., 2025)
Myeloid-derived suppressor cells (MDSCs) ameliorate inflammation by inhibiting T cell responses. In pathological conditions, such as autoimmunity, chronic infections or cancer they accumulate in the periphery. In cancer, MDSCs can also be part of the tumor microenvironment and are associated with a worse prognosis and limited response to immunotherapy. Nowadays attempts are made to specifically target MDSCs in cancer therapy. Still, the role of MDSCs in standard cancer treatment modalities, such as radiotherapy remains mostly elusive. Here, we describe a flow cytometry-based method to determine and monitor monocytic and granulocytic-derived MDSCs directly from whole blood in an easy, fast and reliable assay. As specific surface markers for MDSCs are lacking, the assay follows a gating strategy that excludes successively the main immune cells types and analyzes the remaining events for a set of molecules that are expressed on MDSCs. This assay is especially appropriate for longitudinal analyses and clinical trials and is suitable for being integrated into more complex immunophenotyping panels to generate a comprehensive immune status.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Flow cytometry; Immune monitoring; Immune status; Immunophenotyping; Myeloid-derived suppressor cells

Fractionated radiotherapy is the main stimulus for the induction of cell death and of Hsp70 release of p53 mutated glioblastoma cell lines - Rubner, Yvonne; Muth, Carolin; Strnad, Annedore; Derer, Anja; Sieber, Renate; Buslei, Rolf; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Radiation Oncology, 2014)
Glioblastoma multiforme (GBM) is the most common primary brain tumor in adults. Despite a multimodal therapy consisting of resection followed by fractionated radiotherapy (RT) combined with the chemotherapeutic agent (CT) temozolomide (TMZ), its recurrence is almost inevitable. Since the immune system is capable of eliminating small tumor masses, a therapy should also aim to stimulate anti-tumor immune responses by induction of immunogenic cell death forms. The histone deacetylase inhibitor valproic acid (VPA) might foster this.Reflecting therapy standards, we applied in our in vitro model fractionated RT with a single dose of 2Gy and clinically relevant concentrations of CT. Not only the impact of RT and/or CT with TMZ and/or VPA on the clonogenic potential and cell cycle of the glioblastoma cell lines T98G, U251MG, and U87MG was analyzed, but also the resulting cell death forms and release of danger signals such as heat-shock protein70 (Hsp70) and high-mobility group protein B1 (HMGB1).The clonogenic assays revealed that T98G and U251MG, having mutated tumor suppressor protein p53, are more resistant to RT and CT than U87MG with wild type (WT) p53. In all glioblastoma cells lines, fractionated RT induced a G2 cell cycle arrest, but only in the case of U87MG, TMZ and/or VPA alone resulted in this cell cycle block. Further, fractionated RT significantly increased the number of apoptotic and necrotic tumor cells in all three cell lines. However, only in U87MG, the treatment with TMZ and/or VPA alone, or in combination with fractionated RT, induced significantly more cell death compared to untreated or irradiated controls. While necrotic glioblastoma cells were present after VPA, TMZ especially led to significantly increased amounts of U87MG cells in the radiosensitive G2 cell cycle phase. While CT did not impact on the release of Hsp70, fractionated RT resulted in significantly increased extracellular concentrations of Hsp70 in p53 mutated and WT glioblastoma cells.Our results indicate that fractionated RT is the main stimulus for induction of glioblastoma cell death forms with immunogenic potential. The generated tumor cell microenvironment might be beneficial to include immune therapies for GBM in the future.
EVALuna2:7235

Frequent occurrence of therapeutically reversible CMV-associated encephalopathy during radiotherapy of the brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Ruehle, Paul F.; Putz, Florian; Semrau, Sabine; et al. (Neuro-Oncology, 2016)
Neurological decline during radio(chemo)therapy of the brain is often attributed to disease progression or side effects of radiotherapy. Diagnosis of opportunistic neurotropic infections such as cytomegalovirus (CMV) infections is uncommon, even though high-grade gliomas and some brain metastases are known to contain CMV particles. We prospectively examined the frequency of CMV encephalopathy during radiotherapy of the brain.Fifty patients requiring whole-brain radiotherapy for brain metastases (n = 27) or local radio(chemo)therapy of the brain for high-grade gliomas (n = 23) were observed in the prospective observational GLIO-CMV-01 study. MRIs and blood samples were obtained before, halfway through, and at the end of radiotherapy. MRIs were screened for disease progression or increased intracranial pressure. Blood was tested for anti-CMV immunoglobulin (Ig)M, anti-CMV IgG, and CMV DNA.Thirty-two of 50 (64%) patients were positive for anti-CMV IgG before radio(chemo)therapy. Fifteen of those 32 (48%) developed viremia during or up to 28 days after treatment. Thirteen of those 15 (87%) required treatment for CMV-associated encephalopathy. MRIs were negative for disease progression, edema, or bleeding. None of the patients negative for anti-CMV IgG developed viremia, suggesting a reactivation rather than a primary infection.In the group at risk consisting of anti-CMV IgG+ patients, age >65 (P = .004) and the amount of dexamethasone taken during radio(chemo)therapy (P = .004) were associated with an increased risk for CMV-associated encephalopathy. One hundred and fifty days after the start of radio(chemo)therapy, survival was 74% (14/19) (no encephalopathy) versus 54% (7/13) (encephalopathy) (odds ratio, 0.42; 95% CI, 0.03-1.86; P = .25).CMV reactivation frequently causes encephalopathy during radio(chemo)therapy of the brain. The unexpected high incidence of this infection makes it highly clinically relevant for every treating physician.
EVALuna2:8306

FSRT vs. SRS in Brain Metastases—Differences in Local Control and Radiation Necrosis—A Volumetric Study - Putz, Florian; Weissmann, Thomas; Oft, Dominik; Schmidt, Manuel; Roesch, Johannes; Siavooshhaghighi, Hadi; Filimonova, Irina; Schmitter, Charlotte; Mengling, Veit; Bert, Christoph; Frey, Benjamin; Lettmaier, Sebastian; et al. (Frontiers in Oncology, 2020)
Background: While the role of stereotactic radiotherapy for brain metastases is increasing, evidence on the comparative efficacy and safety of fractionated stereotactic radiotherapy (FSRT) and single-session radiosurgery (SRS) is scarce. Methods: Longitudinal volumetric analysis was performed in a consecutive cohort of 120 patients and 190 brain metastases (>0.065 cm3 in volume / > 5 mm in diameter) treated exclusively with FSRT (n = 98) and SRS (n = 92), respectively. A total of 972 tumor segmentations was used, averaging 5.1 time points per metastasis. Progression was defined using a volumetric extension of the RANO-BM criteria. Local control and radionecrosis were compared for lesions treated with FSRT and SRS, respectively. Results: Metastases treated with FSRT were significantly larger at baseline (mean, 4.66 vs. 0.40 cm3, p < 0.001). Biologically effective dose (BED) for metastases (α/β = 12, linear-quadratic-cubic model) was significantly associated with local control, whereas BED for normal brain (α/β = 2, linear-quadratic model) was significantly associated with radionecrosis. Median time to local progression was 22.9 months in the FSRT group compared to 14.5 months in the SRS group (p = 0.022). Overall radionecrosis rate at 12 months was 3.4% for FSRT and 14.8% for SRS (p = 0.010). Radionecrosis °IV requiring resection with histologic proof of radiation necrosis also was significantly reduced in the FSRT group (FSRT 0.0% vs. SRS 3.9%, p = 0.041). In multivariate analysis, FSRT was associated with reduced risk of progression (HR 0.47, p = 0.015) and reduced risk of radionecrosis (HR 0.18, p = 0.045). Conclusions: This volumetric study provides initial evidence that the improvements in therapeutic ratio expected for FSRT in larger brain metastases, might equally extend into the domain of smaller metastases, traditionally less considered for fractionated treatment. FSRT might constitute an important tool to further increase local control and reduce radionecrosis risk in stereotactic radiotherapy for brain metastases, that should be assessed in randomized intervention trials.
CRIS-Team Scopus Importer:2020-10-30
Keywords: brain metastases; fractionated stereotactic radiotherapy; radiobiological aspects; segmentation; stereotactic radiosurgery (SRS); stereotactic radiotherapy (SRT); volumetric analysis

Full Length Interleukin 33 Aggravates Radiation-Induced Skin Reaction - Kurow, Olga; Frey, Benjamin; Schuster, Louis; Schmitt, Verena; Adam, Susanne; Hahn, Madelaine; Gilchrist, Derek; Mcinnes, Iain B.; Wirtz, Stefan; Gaipl, Udo; Krönke, Gerhard; Schett, Georg; et al. (Frontiers in Immunology, 2017)
The interleukin (IL)-1 family member IL-33 has been described as intracellular alarmin with broad roles in wound healing, skin inflammation but also autoimmunity. Its dichotomy between full length (fl) IL-33 and the mature (m) form of IL-33 and its release by necrosis is still not fully understood. Here, we compare functional consequences of both forms in the skin in vivo, and therefore generated two lines of transgenic mice which selectively overexpress mmIL-33 and flmIL-33 in basal keratinocytes. Transgene mRNA was expressed at high level in skin of both lines but not in organs due to the specific K14 promoter. We could demonstrate that transgenic overexpression of mmIL-33 in murine keratinocytes leads to a spontaneous skin inflammation as opposed to flmIL-33. K14-mmIL-33 mice synthesize and secrete high amounts of mmIL-33 along with massive cutaneous manifestations, like increased epidermis and dermis thickness, infiltration of mast cells in the epidermis and dermis layers and marked hyperkeratosis. Using skin inflammation models such as IL-23 administration, imiquimod treatment, or mechanical irritation did not lead to exacerbated inflammation in the K14-flmIL-33 strain. As radiation induces a strong dermatitis due to apoptosis and necrosis, we determined the effect of fractionated radiation (12 Gy, 4 times). In comparison to wild-type mice, an increase in ear thickness in flmIL-33 transgenic mice was observed 25 days after irradiation. Macroscopic examination showed more severe skin symptoms in irradiated ears compared to controls. In summary, secreted mmIL-33 itself has a potent capacity in skin inflammation whereas fl IL-33 is limited due to its intracellular retention. During tissue damage, fl IL-33 exacerbated radiation-induced skin reaction.
EVALuna2:13432

Genomic EWSR1 Fusion Sequence as Highly Sensitive and Dynamic Plasma Tumor Marker in Ewing Sarcoma - Krumbholz, Manuela; Hellberg, Julia; Steif, Benedikt; Bäuerle, Tobias; Gillmann, Clarissa; Fritscher, Torsten; Agaimy, Abbas; Frey, Benjamin; Juengert, Joerg; Wardelmann, Eva; Hartmann, Wolfgang; Juergens, Heribert; et al. (Clinical Cancer Research, 2016)
The application of the tumor-specific genomic fusion sequence as noninvasive biomarker for therapy monitoring in Ewing sarcoma (EwS) has been evaluated.EwS xenograft mouse models were used to explore detectability in small plasma volumes and correlation of genomic EWSR1-FLI1 copy numbers with tumor burden. Furthermore, 234 blood samples from 20 EwS patients were analyzed before and during multimodal treatment. EWSR1 fusion sequence levels in patients' plasma were quantified using droplet digital PCR and compared with tumor volumes calculated from MRI or CT imaging studies.Kinetics of EWSR1 fusion sequence copy numbers in the plasma are correlated with changes of the tumor volume in patients with localized and metastatic disease. The majority of patients showed a fast reduction of cell-free tumor DNA (ctDNA) during initial chemotherapy. Recurrence of increasing ctDNA levels signalized relapse development.Genomic fusion sequences represent promising noninvasive biomarkers for improved therapy monitoring in EwS. Until now, response assessment is largely based on MRI and CT imaging, implying restrictions on closely repeated performance and limitations on the differentiation between vital tumor and reactive stromal tissue. Particularly in patients with prognostic unfavorable disseminated disease, ctDNA is a valuable addition for the assessment of therapy response. Clin Cancer Res; 22(17); 4356-65. ©2016 AACR.
EVALuna2:6851

GLIO-CMV-01: Identification of immune biomarkers for CMV-related encephalitis during radiotherapy of the brain - Donaubauer, Anna-Jasmina; Becker, I.; Rühle, Paul-Friedrich; Goerig, Nicole; Pohn, A.; Winkler, Thomas; Korn, Klaus; Überla, Klaus; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36498

GLIO-CMV-01: Identification of immune biomarkers for CMV related encephalitis during standard brain radiotherapy - Rühle, Paul-Friedrich; Goerig, Nicole; Korn, Klaus; Überla, Klaus; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32892

Graphene-Induced Hyperthermia (GIHT) Combined With Radiotherapy Fosters Immunogenic Cell Death - Podolska, Malgorzata; Shan, Xiaomei; Janko, Christina; Boukherroub, Rabah; Gaipl, Udo; Szunerits, Sabine; Frey, Benjamin; Munoz, Luis Enrique (Frontiers in Oncology, 2021)
Radiotherapy and chemotherapy are the standard interventions for cancer patients, although cancer cells often develop radio- and/or chemoresistance. Hyperthermia reduces tumor resistance and induces immune responses resulting in a better prognosis. We have previously described a method to induce tumor cell death by local hyperthermia employing pegylated reduced graphene oxide nanosheets and near infrared light (graphene-induced hyperthermia, GIHT). The spatiotemporal exposure/release of heat shock proteins (HSP), high group mobility box 1 protein (HMGB1), and adenosine triphosphate (ATP) are reported key inducers of immunogenic cell death (ICD). We hypothesize that GIHT decisively contributes to induce ICD in irradiated melanoma B16F10 cells, especially in combination with radiotherapy. Therefore, we investigated the immunogenicity of GIHT alone or in combination with radiotherapy in melanoma B16F10 cells. Tumor cell death in vitro revealed features of apoptosis that is progressing fast into secondary necrosis. Both HSP70 and HMGB1/DNA complexes were detected 18 hours post GIHT treatment, whereas the simultaneous release of ATP and HMGB1/DNA was observed only 24 hours post combined treatment. We further confirmed the adjuvant potential of these released DAMPs by immunization/challenge experiments. The inoculation of supernatants of cells exposed to sole GIHT resulted in tumor growth at the site of inoculation. The immunization with cells exposed to sole radiotherapy rather fostered the growth of secondary tumors in vivo. Contrarily, a discreet reduction of secondary tumor volumes was observed in mice immunized with a single dose of cells and supernatants treated with the combination of GIHT and irradiation. We propose the simultaneous release of several DAMPs as a potential mechanism fostering anti-tumor immunity against previously irradiated cancer cells.
CRIS-Team Scopus Importer:2021-09-17
Keywords: hyperthermia; immunogenic cell death; melanoma; multimodal; radiotherapy; reduced graphene oxide

Graphene Oxide Nanosheets for Localized Hyperthermia-Physicochemical Characterization, Biocompatibility, and Induction of Tumor Cell Death - Podolska, Malgorzata; Barras, Alexandre; Alexiou, Christoph; Frey, Benjamin; Gaipl, Udo; Boukherroub, Rabah; Szunerits, Sabine; Janko, Christina; Munoz, Luis Enrique (Cells, 2020)
Background: The main goals of cancer treatment are not only to eradicate the tumor itself but also to elicit a specific immune response that overcomes the resistance of tumor cells against chemo- and radiotherapies. Hyperthermia was demonstrated to chemo- and radio-sensitize cancerous cells. Many reports have confirmed the immunostimulatory effect of such multi-modal routines. Methods: We evaluated the interaction of graphene oxide (GO) nanosheets; its derivatives reduced GO and PEGylated rGO, with components of peripheral blood and evaluated its thermal conductivity to induce cell death by localized hyperthermia. Results: We confirmed the sterility and biocompatibility of the graphene nanomaterials and demonstrated that hyperthermia applied alone or in the combination with radiotherapy induced much more cell death in tumor cells than irradiation alone. Cell death was confirmed by the release of lactate dehydrogenase from dead and dying tumor cells. Conclusion: Biocompatible GO and its derivatives can be successfully used in graphene-induced hyperthermia to elicit tumor cell death.
CRIS-Team WoS Importer:2020-05-15

Head and neck tumor cells treated with hypofractionated irradiation die via apoptosis and are better taken up by M1-like macrophages - Wedekind, Hanna; Walz, Kristina; Buchbender, Mayte; Rieckmann, Thorsten; Strasser, Erwin; Grottker, Fridolin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Rückert, Michael (Strahlentherapie und Onkologie, 2021)
Purpose: The incidence of head and neck squamous cell carcinomas (HNSCC) is increasing worldwide, especially when triggered by the human papilloma virus (HPV). Radiotherapy has immune-modulatory properties, but the role of macrophages present in HNSCC and having contact with irradiated tumor cells remains unclear. The influence of irradiated (2 × 5Gy) HNSCC cells on the (re-)polarization and phagocytosis of human macrophages, either non-polarized or with a more M1 or M2 phenotype, was therefore investigated. Methods: Human monocytes were differentiated with the hematopoietic growth factors M‑CSF (m) or GM-CSF (g) and additionally pre-polarized with either interleukin (IL)-4 and IL-10 or interferon (IFN)-γ and lipopolysaccharides (LPS), respectively. Subsequently, they were added to previously irradiated (2 × 5Gy) and mock-treated HPV-positive (UD-SCC-2) and HPV-negative (Cal33) HNSCC cells including their supernatants. Results: The HNSCC cells treated with hypofractionated irradiation died via apoptosis and were strongly phagocytosed by M0m and M2 macrophages. M0g and M1 macrophages phagocytosed the tumor cells to a lesser extent. Irradiated HNSCC cells were better phagocytosed by M1 macrophages compared to mock-treated controls. The polarization status of the macrophages was not significantly changed, except for the expression of CD206 on M2 macrophages, which was reduced after phagocytosis of irradiated HPV-negative cells. Further, a significant increase in the uptake of irradiated HPV-positive cells by M0g macrophages when compared to HPV-negative cells was observed. Conclusion: HNSCC cells treated with hypofractionated irradiation foster phagocytosis by anti-tumorigenic M1 macrophages. The data provide the first evidence on the impact of the HPV status of HNSCC cells on the modulation of the macrophage response to irradiated tumor cells.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Head and neck cancer; Human papilloma virus; Macrophage polarization; Phagocytosis; Radiotherapy

High Detection Accuracy of an optimized 3D Convolutional Neural Network for Auto Detection and Auto Segmentation of Brain Metastases - Putz, Florian; Weissmann, Thomas; Mansoorian, Sina; Schmitter, Charlotte; Semrau, Sabine; Lettmaier, Sebastian; Masitho, Siti; Grigo, Johanna; Schmidt, Manuel; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Hydrostatic High Pressure generated Whole Cell Tumor Vaccines in combination with Radiotherapy produce an immunogenic Tumor Microenvironment - Rueckert, M.; Seitz, C.; Weiss, E. -M; Utz, S.; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Hyperthermia with 44 degrees C enhances danger signal-mediated activation of dendritic cells, while immune cell infiltration into tumors is particularly fostered by hyperthermia with lower temperatures - Vogl, P.; Frey, Benjamin; Rueckert, M.; Maueröder, Christian; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (2017)
EVALuna2:32897

Hypofractionated Irradiation Has Immune Stimulatory Potential and Induces a Timely Restricted Infiltration of Immune Cells in Colon Cancer Tumors - Frey, Benjamin; Rueckert, Michael; Weber, Julia; Mayr, Xaver; Derer, Anja; Lotter, Michael; Bert, Christoph; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo (Frontiers in Immunology, 2017)
In addition to locally controlling the tumor, hypofractionated radiotherapy (RT) particularly aims to activate immune cells in the RT-modified microenvironment. Therefore, we examined whether hypofractionated RT can activate dendritic cells (DCs), induce immune cell infiltration in tumors, and how the chronology of immune cell migration into tumors occurs to gain knowledge for future definition of radiation breaks and inclusion of immunotherapy. Colorectal cancer treatments offer only limited survival benefit, and immunobiological principles for additional therapies need to be explored with preclinical models. The impact of hypofractionated RT on CT26 colon cancer tumor cell death, migration of DCs toward supernatants (SN) of tumor cells, and activation of DCs by SN were analyzed. The subcutaneous tumor of a BALB/c-CT26 mouse model was locally irradiated with 2 × 5 Gy, the tumor volume was monitored, and the infiltration of immune cells in the tumor was determined by flow cytometry daily. Hypofractionated RT induced a mixture of apoptotic and necrotic CT26 cells, which is known to be in particular immunogenic. DCs that migrated toward SN of CT26 cells particularly upregulated the activation markers CD80 and CD86 when in contact with SN of irradiated tumor cells. After hypofractionated RT, the tumor outgrowth was significantly retarded and in the irradiated tumors an increased infiltration of macrophages (CD11bhigh/F4-80+) and DCs (MHC-II+), but only between day 5 and 10 after the first irradiation, takes place. While CD4+T cells migrated into non-irradiated and irradiated tumors, CD8+T cells were only found in tumors that had been irradiated and they were highly increased at day 8 after the first irradiation. Myeloid-derived suppressor cells and regulatory T cells show regular turnover in irradiated and non-irradiated tumors. Tumor cell-specific anti-IgM antibodies were enhanced in the serum of animals with irradiated tumors. We conclude that hypofractionated RT suffices to activate DCs and to induce infiltration of innate and adaptive immune cells into solid colorectal tumors. However, the presence of immune cells in the tumor which are beneficial for antitumor immune responses is timely restricted. These findings should be considered when innovative multimodal tumor treatment protocols of distinct RT with immune therapies are designed and clinically implemented.
EVALuna2:32906

Hypofractionated Radiotherapy Upregulates Several Immune Checkpoint Molecules in Head and Neck Squamous Cell Carcinoma Cells Independently of the HPV Status While ICOS-L Is Upregulated Only on HPV-Positive Cells - Wimmer, Sebastian; Deloch, Lisa; Hader, Michael; Derer, Anja; Grottker, Fridolin; Weissmann, Thomas; Hecht, Markus; Gostian, Antoniu-Oreste; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2021)
While the treatment of squamous cell carcinoma of the head and neck (HNSCC) with radiotherapy (RT) is complemented more and more by immunotherapy in clinical trials, little is known about the impact of the human papillomavirus (HPV) status or the applied RT scheme on the immune phenotype of the tumor cells. Therefore, we aimed to examine the impact of the HPV status of four human HNSCC cell lines on cell death and the expression of immune checkpoint molecules (ICMs) after RT with either hypofractionation irradiation (5x3.0Gy) or a high single dose (1x19.3Gy) via multicolor flow cytometry and quantitative PCR at an early time point after therapy. In our study, 5x3.0Gy RT induced high numbers of early and late apoptotic cells independent of the HPV status, but necrosis was only increased in the HPV-positive UM-Scc-47 cells. Generally, the immune stimulatory ICMs (CD70, CD137-L, ICOS-L) were less affected by RT compared to the immune suppressive ones (PD-L1, PD-L2, and the herpesvirus entry mediator (HVEM)). A significant higher surface expression of the analyzed ICMs was found after hypofractionated RT compared to a single high dose; however, regardless of the HPV status, with the exception of ICOS-L. Here, HPV-positive HNSCC tumor cells showed a stronger response to 5x3.0Gy than HPV-negative ones. On the RNA level, only minor alterations of ICMs were observed following RT, with the exception of the HPV negative cell line CAL33 treated with 5x3.0Gy, where PD-L2, HVEM and CD70 were significantly increased. We conclude that the HPV status may not distinctly predict immunological responses following RT, and thus cannot be used as a single predictive marker for therapy responses in HNSCC. In contrast, the patient-specific individual expression of ICMs following RT is preferable for the targeted patient selection for immune therapy directed against distinct ICM.
CRIS-Team WoS Importer:2021-09-17

Identification and characterization of circular RNAs as novel putative biomarkers to predict anti-PD-1 monotherapy response in metastatic melanoma patients – Knowledge from two independent international studies - Zhou, Jian Guo; Liang, Rui; Wang, Hai Tao; Jin, Su Han; Hu, Wei; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Gaipl, Udo (Neoplasia, 2023)
Melanoma is the most aggressive skin malignancy with high morbidity. Anti-programmed cell death protein 1 (PD-1) monotherapy has been applied in metastatic melanoma. However, still most of the patients do not respond to anti-PD-1 and the availability of the present approved biomarkers therefore is limited. Here we combined the transcriptomic and clinical data of 163 advanced melanoma patients receiving anti-PD-1 from NIH Melanoma Genome Sequencing Project (phs000452, 122 patients) as the training and internal validation cohort, and Melanoma Institute Australia cohort (PRJEB23709, 41 patients) as the external validation cohort, respectively. Circular RNAs (circRNAs) are an evolutionarily conserved novel class of noncoding endogenous RNAs (ncRNAs) found in the eukaryotic transcriptome and were used based on RNAseq data for our analyses. 74,243 circular RNAs (circRNAs) were identified with NCLscan and CIRCexplorer2. Thereof, 70 circRNAs significantly associated with progression-free survival and overall survival. Further, a prognostic circRNAs signature consisting of HSA_CIRCpedia_1497, HSA_CIRCpedia_12559, HSA_CIRCpedia_43640, HSA_CIRCpedia_43070, and HSA_CIRCpedia_21660 could be determined with LASSO regression. This signature was a prognostic factor of overall survival and progression-free survival among the analyzed advanced melanoma patients. The concordance indexes (C-index of OStraining: 0.61, C-index of PFStraining: 0.68) also confirmed its credibility and accuracy. First enrichment analysis indicated that immune response and pathways related to tumor immune microenvironment were enriched. In conclusion, we succeeded to construct and validate novel prognostic circRNAs signature for advanced melanoma patients treated with anti-PD-1 immunotherapy.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Advanced melanoma; Anti-PD-1; circRNAs; Predictor; Survival benefit

Identification of 15 lncRNAs Signature for Predicting Survival Benefit of Advanced Melanoma Patients Treated with Anti-PD-1 Monotherapy - Zhou, Jian Guo; Liang, Bo; Liu, Jian Guo; Jin, Su Han; He, Si Si; Frey, Benjamin; Gu, Ning; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Gaipl, Udo (Cells, 2021)
The blockade of programmed cell death protein 1 (PD-1) as monotherapy has been widely used in melanoma, but to identify melanoma patients with survival benefit from anti-PD-1 monotherapy is still a big challenge. There is an urgent need for prognostic signatures improving the prediction of immunotherapy responses of these patients. We analyzed transcriptomic data of pre-treatment tumor biopsies and clinical profiles in advanced melanoma patients receiving only anti-PD-1 monotherapy (nivolumab or pembrolizumab) from the PRJNA356761 and PRJEB23709 data sets as the training and validation cohort, respectively. Weighted gene co-expression network analysis was used to identify the key module, then least absolute shrinkage and selection operator was conducted to determine prognostic-related long noncoding RNAs (lncRNAs). Subsequently, the differentially expressed genes between different clusters were identified, and their function and pathway annotation were performed. In this investigation, 92 melanoma patients with complete survival information (51 from training cohort and 41 from validation cohort) were included in our analyses. We initiallyidentified the key module (skyblue) by weighted gene co-expression network analysis, and then identified a 15 predictive lncRNAs (AC010904.2, LINC01126, AC012360.1, AC024933.1, AL442128.2, AC022211.4, AC022211.2, AC127496.5, NARF-AS1, AP000919.3, AP005329.2, AC023983.1, AC023983.2, AC139100.1, and AC012615.4) signature in melanoma patients treated with anti-PD-1 monotherapy by least absolute shrinkage and selection operator in the training cohort. These results were then validated in the validation cohort. Finally, enrichment analysis showed that the functions of differentially expressed genes between two consensus clusters were mainly related to the immune process and treatment. In summary, the 15 lncRNAs signature is a novel effective predictor for prognosis in advanced melanoma patients treated with anti-PD-1 monotherapy.
CRIS-Team Scopus Importer:2021-05-28
Keywords: advanced melanoma; immune checkpoint inhibitor; LASSO; lncRNA; PD-1; predictor; survival benefit; WGCNA

Identification of an endogenous retroviral signature to predict anti-PD1 response in advanced clear cell renal cell carcinoma: an integrated analysis of three clinical trials - Zhou, Jianguo; Zeng, Yu; Wang, Haitao; Jin, Su-Han; Wang, Yun-Jia; He, Sisi; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Ma, Hu; Zhang, Wenchuan; Gaipl, Udo (Therapeutic Advances in Medical Oncology, 2022)
Background: Endogenous retrovirus (ERV) elements are genomic footprints of ancestral retroviral infections within the human genome. Previous studies have demonstrated that dysregulated ERV transcription level is associated with immune cell infiltration in cancers, but the association between ERV expression and programmed cell death protein 1 (PD-1) blockade response is currently unraveled for solid cancers, such as advanced clear cell renal cell carcinoma (ccRCC). Methods: ERV mRNA profiles were obtained from three clinical trials of ccRCC where the patients were treated with anti-PD-1 (CM-009, CM-010, CM-025, and TCGA-KIRC data). Patients treated with nivolumab were divided into training and test cohort, while the TCGA-KIRC cohort was used as an external validation. Univariate Cox regression analysis and least absolute shrinkage and selection operator regression were used to establish the signature. Immune cell infiltration analysis and gene set enrichment analysis were performed to explore potential biological mechanisms. Results: An ERV signature was established based on nine ERV expression patterns. In the training cohort, the median overall survival in the low- and high-risk group was 45.2 and 19.6 months [hazard ratio (HR) = 0.49, 0.32-0.75, p < 0.001], respectively. The results were confirmed in the test (HR = 0.41, 0.20-0.83, p = 0.013), and in the TCGA-KIRC cohort (HR = 0.55, 0.34-0.90, p = 0.017). Moreover, in the CM-025 cohort, the low-risk group that received nivolumab had a more favorable survival compared with those that received the mTOR inhibitor everolimus, while no significant differences were observed in the high-risk group. CD8+ T cells were enriched in the low-risk group, while immune suppressive pathways were suppressed. Conclusion: The newly identified ERV signature is not only a prognostic, but also a predictive biomarker for advanced ccRCC patients who received anti-PD-1 therapy, which can guide personalized treatment in cancer patients in the future.
CRIS-Team WoS Importer:2022-10-14

Identification of High-risk Metastases in MRI Follow-up after Stereotaxic by using Radiomics and Delta Radiomics - Sommer, Phillip; Huang, Yixing; Fischer, Stefan; Srinivasan, Aishwarya Lakshmi; Dörfler, Arnd; Schmidt, M.; Frey, Benjamin; Maier, Andreas; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

IMMO-LDRT01: Immunophenotyping of patients suffering from chronic degenerative joint diseases and receiving local low-dose radiation therapy - Harrer, A.; Rühle, Paul-Friedrich; Gryc, Thomas; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2017)
EVALuna2:32884

IMMO-LDRT01 TRIAL: IMMUNOMODULATORY EFFECTS OF LOW DOSE RADIATION THERAPY OF CHRONIC DEGENERATIVE AND INFLAMMATORY DISEASES - Donaubauer, Anna-Jasmina; Gryc, Thomas; Becker, I.; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Immune biological rationales for the design of combined radio- and immunotherapies - Hader, Michael; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Gaipl, Udo (Cancer Immunology, Immunotherapy, 2020)
Cancer immunotherapies are promising treatments for many forms of cancer. Nevertheless, the response rates to, e.g., immune checkpoint inhibitors (ICI), are still in low double-digit percentage. This calls for further therapy optimization that should take into account combination of immunotherapies with classical tumor therapies such as radiotherapy. By designing multimodal approaches, immune modulatory properties of certain radiation schemes, additional immune modulation by immunotherapy with ICI and hyperthermia, as well as patient stratification based on genetic and immune constitutions have to be considered. In this context, both the tumor and its microenvironment including cells of the innate and adaptive immune system have to be viewed in synopsis. Knowledge of immune activation and immune suppression by radiation is the basis for well-elaborated addition of certain immunotherapies. In this review, the focus is set on additional immune stimulation by hyperthermia and restoration of an immune response by ICI. The impact of radiation dose and fractionation on immune modulation in multimodal settings has to be considered, as the dynamics of the immune response and the timing between radiotherapy and immunotherapy. Another big challenge is the patient stratification that should be based on matrices of biomarkers, taking into account genetics, proteomics, radiomics, and "immunomics". One key aim is to turn immunological "cold" tumors into "hot" tumors, and to eliminate barriers of immune-suppressed or immune-excluded tumors. Comprehensive knowledge of immune alterations induced by radiation and immunotherapy when being applied together should be utilized for patient-adapted treatment planning and testing of innovative tumor therapies within clinical trials.
CRIS-Team WoS Importer:2020-01-31

Immune-modulating properties of ionizing radiation: rationale for the treatment of cancer by combination radiotherapy and immune checkpoint inhibitors - Derer, Anja; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (Cancer Immunology Immunotherapy, 2016)
Radiotherapy (RT) utilizes the DNA-damaging properties of ionizing radiation to control tumor growth and ultimately kill tumor cells. By modifying the tumor cell phenotype and the tumor microenvironment, it may also modulate the immune system. However, out-of-field reactions of RT mostly assume further immune activation. Here, the sequence of the applications of RT and immunotherapy is crucial, just as the dose and fractionation may be. Lower single doses may impact on tumor vascularization and immune cell infiltration in particular, while higher doses may impact on intratumoral induction and production of type I interferons. The induction of immunogenic cancer cell death seems in turn to be a common mechanism for most RT schemes. Dendritic cells (DCs) are activated by the released danger signals and by taking up tumor peptides derived from irradiated cells. DCs subsequently activate T cells, a process that has to be tightly controlled to ensure tolerance. Inhibitory pathways known as immune checkpoints exist for this purpose and are exploited by tumors to inhibit immune responses. Cytotoxic T lymphocyte antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1) on T cells are two major checkpoints. The biological concepts behind the findings that RT in combination with anti-CTLA-4 and/or anti-PD-L1 blockade stimulates CD8+ T cell-mediated anti-tumor immunity are reviewed in detail. On this basis, we suggest clinically significant combinations and sequences of RT and immune checkpoint inhibition. We conclude that RT and immune therapies complement one another.
EVALuna2:18336

Immune modulation by low dose radiation therapy-results from 70 patients followed up in the IMMO-LDRT01 study - Donaubauer, Anna-Jasmina; Gryc, Thomas; Becker, I.; Harrer, A.; Rühle, Paul-Friedrich; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36497

Immune modulatory effects of radiotherapy as basis for well-reasoned radioimmunotherapies - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Hecht, Markus; Gaipl, Udo; Deloch, Lisa (Strahlentherapie und Onkologie, 2018)
BACKGROUND: Radiotherapy (RT) has been known for decades as a local treatment modality for malign and benign disease. In order to efficiently exploit the therapeutic potential of RT, an understanding of the immune modulatory properties of ionizing radiation is mandatory. These should be used for improvement of radioimmunotherapies for cancer in particular. METHODS: We here summarize the latest research and review articles about immune modulatory properties of RT, with focus on radiation dose and on combination of RT with selected immunotherapies. Based on the knowledge of the manifold immune mechanisms that are triggered by RT, thought-provoking impulse for multimodal radioimmunotherapies is provided. RESULTS: It has become obvious that ionizing radiation induces various forms of cell death and associated processes via DNA damage initiation and triggering of cellular stress responses. Immunogenic cell death (ICD) is of special interest since it activates the immune system via release of danger signals and via direct activation of immune cells. While RT with higher single doses in particular induces ICD, RT with a lower dose is mainly responsible for immune cell recruitment and for attenuation of an existing inflammation. The counteracting immunosuppression emanating from tumor cells can be overcome by combining RT with selected immunotherapies such as immune checkpoint inhibition, TGF-β inhibitors, and boosting of immunity with vaccination. CONCLUSION: In order to exploit the full power of RT and thereby develop efficient radioimmunotherapies, the dose per fraction used in RT protocols, the fractionation, the quality, and the quantity of certain immunotherapies need to be qualitatively and chronologically well-matched to the individual immune status of the patient.
EVALuna2:36465

Immune suppressive properties of Glioblastoma cells might result in part from radiation-induced increased expression of inhibitory immune checkpoint molecules - Langenfelder, E.; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36504

Immunological basis of abscopal antitumor responses induced with radio-immunotherapy - Rueckert, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32891

Immunological basis of local and abscopal antitumor responses induced with radio-immunotherapy - Rueckert, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32863

Immunomodulation by ionizing radiation-impact for design of radio-immunotherapies and for treatment of inflammatory diseases - Frey, Benjamin; Rueckert, Michael; Rühle, Paul-Friedrich; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Immunological Reviews, 2017)
Ionizing radiation is often regarded as an element of danger. But, danger responses on the cellular and molecular level are often beneficial with regard to the induction of anti-tumor immunity and for amelioration of inflammation. We outline how in dependence of radiation dose and fraction, radiation itself-and especially in combination with immune modulators-impacts on the innate and adaptive immune system. Focus is set on radiation-induced changes of the tumor cell phenotype and the cellular microenvironment including immunogenic cancer cell death. Mechanisms how anti-tumor immune responses are triggered by radiotherapy in combination with hyperthermia, inhibition of apoptosis, the adjuvant AnnexinA5, or vaccination with high hydrostatic pressure-killed autologous tumor cells are discussed. Building on this, feasible multimodal radio-immunotherapy concepts are reviewed including overcoming immune suppression by immune checkpoint inhibitors and by targeting TGF-β. Since radiation-induced tissue damage, inflammation, and anti-tumor immune responses are interconnected, the impact of lower doses of radiation on amelioration of inflammation is outlined. Closely meshed immune monitoring concepts based on the liquid biopsy blood are suggested for prognosis and prediction of cancer and non-cancer inflammatory diseases. Finally, challenges and visions for the design of cancer radio-immunotherapies and for treatment of benign inflammatory diseases are given.
EVALuna2:32867

Immunomodulatory and analgesic Effects of serial Radon-Baths in Patients with musculoskeletal Diseases: Investigations in the RAD-ON02 Study - Donaubauer, Anna-Jasmina; Becker, Ina; Weikl, Lena; Klein, Gerhart; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Strahlentherapie und Onkologie, 2021)
CRIS-Team WoS Importer:2021-07-16

Immunophanotype modulating Properties of Ferrous Clathrochelates and Irradiation in Lung Cancer Cells - Alomo, Jannik; Becker, I.; Roessel, T.; Denzler, M.; Heim, L.; Mokhir, Andriy; Klemt, Insa; Voloshin, Y.; Selin, R.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Impact of hypo- and normofractionated radiation on cell death and senescence of HNSCC-cells of different HPV-Status - Wild, Kristina; Peitz, L.; Rieckmann, T.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36510

Impact of radio(chemo)therapy on expression of immune checkpoint ligands PD-L1 and PD-L2 on murine and human melanoma cells - Riegel, Dania; Bäumler, Monika; Spiljar, Martina; Rückert, Michael; Frey, Benjamin; Fietkau, Rainer; Derer, Anja; Gaipl, Udo (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32890

Impact of radiotherapy and chemotherapy on PD-L1 and EGF-R expression in melanoma and glioblastoma cells - Bäumler, Monika; Spiljar, Martina; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (DEGRO - Deutsche Gesellschaft dür Radioonkologie e.V., 2016)

Impact of radon and combinatory radon/carbon dioxide spa on pain and hypertension: Results from the explorative RAD-ON01 study - Rühle, Paul-Friedrich; Klein, Gerhart; Rung, Tatiana; Phan, Hong Tiep; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Modern Rheumatology, 2019)
OBJECTIVES: Therapies with low doses of radon have beneficial effects on patients suffering from chronic painful degenerative and inflammatory diseases. We already showed that this is accompanied by systemic immune modulations. We here focus on pain-reducing effects of very low doses of radon by adding carbon dioxide water and its impact on heart rate variability (HRV), blood pressure and free radicals. METHODS: 97 of 103 patients receiving radon spa (1.200 Bq/l at 34 °C or 600 Bq/l, 1 g/l CO2 at 34 °C) were monitored before and at three different time points after therapy. Individual pain perception was analyzed and the capability to process radicals. At each time point, the hypertensive patients (n = 46) were examined over 24 h for blood pressure and HRV. RESULTS: Long-term pain reduction was observed in the majority of patients. A modulation of superoxide dismutase was identified, presumably representing a priming effect for lowering radiation stress. Further, lowering of blood pressure, especially in those patients who additionally received carbon dioxide, was seen. Radon did in particular impact on HRV implying lasting relaxation effects. CONCLUSION: Radon/carbon dioxide spa efficiently reduces pain. In particular, patients simultaneously suffering from painful and cardiovascular diseases should be treated by combination of radon and CO2.
EVALuna2:36466

IMPACT OF RADON SPA ON PAIN AND THE IMMUNE SYSTEM OF PATIENTS WITH MUSCULOSKELETAL DISORDERS - Becker, I.; Donaubauer, Anna-Jasmina; Klein, G.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Implementation of double immune checkpoint blockade increases response rate to induction chemotherapy in head and neck cancer - Semrau, Sabine; Gostian, Antoniu Oreste; Traxdorf, Maximilian; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Tamaskovics, Bálint; et al. (Cancers, 2021)
To determine whether a single dose of double immune checkpoint blockade (induction chemoimmunotherapy (ICIT)) adds benefit to induction single-cycle platinum doublet (induction chemotherapy (IC)) in locally advanced head and neck squamous cell carcinoma (HNSCC), patients treated with cisplatin 30 mg/m2 d1-3 and docetaxel 75 mg/m2 d1 combined with durvalumab 1500 mg fixed dose d5 and tremelimumab 75 mg fixed dose d5 (ICIT) within the CheckRad-CD8 trial were compared with a retrospective cohort receiving the same chemotherapy (IC) without immunotherapy. The endpoint of this analysis was the complete response rate (CR). A total of 53 patients were treated with ICIT and 104 patients with IC only. CR rates were 60.3% for ICIT and 40.3% for IC (p = 0.018). In the total population (n = 157), the most important predictor to achieve a CR was treatment type (OR: 2.21 for ICIT vs. IC; p = 0.038, multivariate analysis). The most diverse effects in CR rates between ICIT and IC were observed in younger (age ≤ 60) patients with HPV-positive OPSCCs (82% vs. 33%, p = 0.176), while there was no difference in older patients without HPV-positive OPSCCs (53% vs. 48%). The analysis provides initial evidence that ICIT could result in higher CR rates than IC. Young patients with HPV-positive OPSCCs may have the greatest benefit from additional immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Combined modality therapy; Double immune checkpoint inhibition; Head and neck neoplasms; HPV-positive OPSCC; Immunotherapy; Induction therapy; Organ preservation

Improvement of Deep Learning-based Auto-detection of Brain Metastases by Integrating previous MRI Images - Dörfler, Arnd; Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Maier, Andreas; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Individual Radiation Sensitivity and Biomarkers: Molecular Radiation Biology - Ainsbury, Elizabeth A.; Abrantes, Ana Margarida; Baatout, Sarah; Baeyens, Ans; Botelho, Maria Filomena; Frey, Benjamin; Foray, Nicolas; Georgakilas, Alexandros G.; Lyng, Fiona M.; Marques, Inês Alexandra; Meade, Aidan D.; Milic, Mirta; et al. (Springer International Publishing, 2023)
In recent years, scientific understanding of the changes radiation makes to the various tissues of the body has vastly increased. Identification of biological markers of radiation exposure and response has become a wide field with an increasing interest across the radiation research community. This chapter introduces the concepts of individual radiosensitivity, radiosusceptibility, and radiodegeneration, which are the key factors to classify radiation responses. Biomarkers are then introduced, and their key characteristics as well as classification are explained, with a particular focus on those biomarkers which have been identified for use in epidemiological studies of radiation risk-as this is a crucial topic of current interest within radiation protection. Brief information on collection of samples is followed by a detailed presentation of predictive assays in use in different settings including clinical applications with responses assessed chiefly in tissue biopsy or blood samples. The sections toward the end of this chapter then discuss the evidence associated with the relationship between age and separately sex, and radiosensitivity, as well as some genetic syndromes associated with radiosensitivity. The final section of this chapter provides a brief summary of how our current knowledge can further support individual, personalized, uses of radiation, particularly in clinical settings.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Biomarkers; Genetic syndromes; Personalized treatment; Radiation sensitivity; Radiation therapy; Sex

Induction chemoimmunotherapy followed by CD8+ immune cell-based patient selection for chemotherapy-free radioimmunotherapy in locally advanced head and neck cancer - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias Günther; Brunner, Thomas B.; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Purpose The first aim of the trial is to study feasibility of combined programmed death protein ligand 1/cytotoxic T-lymphocyte-associated protein 4 inhibition concomitant to radiotherapy. In addition, efficacy of the entire treatment scheme consisting of induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy (RIT) after intratumoral CD8 +immune cell-based patient selection will be analyzed. Methods Patients with stage III-IVB head and neck squamous cell carcinoma were eligible for this multicenter phase II trial. Treatment consisted of a single cycle of cisplatin 30 mg/m² days 1-3, docetaxel 75 mg/m² day 1, durvalumab 1500 mg fix dose day 5 and tremelimumab 75 mg fix dose day 5. Patients with increased intratumoral CD8 +immune cell density or pathological complete response (pCR) in the rebiopsy entered RIT up to a total dose of 70 Gy. Patients received further three cycles of durvalumab/tremelimumab followed by eight cycles of durvalumab mono (every 4 weeks). The intended treatment for patients not meeting these criteria was standard radiochemotherapy outside the trial. Primary endpoint was a feasibility rate of patients entering RIT to receive treatment until at least cycle 6 of immunotherapy of ≥80%. Results Between September 2018 and May 2020, 80 patients were enrolled (one excluded). Out of these, 23 patients had human papilloma virus (HPV)-positive oropharyngeal cancer. Median follow-up was 17.2 months. After induction chemoimmunotherapy 41 patients had pCR and 31 had increased intratumoral CD8 +immune cells. Of 60 patients entering RIT (primary endpoint cohort), 10 experienced imiting toxic (mainly hepatitis) and four discontinued for other reasons, resulting in a feasibility rate of 82%. The RIT cohort (n=60) had a progression-free survival (PFS) rate at one and 2 years of 78% and 72%, respectively, and an overall survival rate at one and 2 years of 90% and 84%, respectively. Patients with HPV-positive oropharyngeal cancers had greater benefit from RIT with a 2-year PFS rate of 94% compared with 64% for HPV-negative oropharyngeal cancers and other locations. In the entire study cohort (n=79) the 2-year PFS rate was 68% (91% for HPV-positive oropharynx vs 59% for others). Toxicity grade 3-4 mainly consisted of dysphagia (53%), leukopenia (52%) and infections (32%). Conclusions The trial met the primary endpoint feasibility of RIT. Induction chemo-immunotherapy followed by chemotherapy-free RIT after intratumoral CD8 +immune cell-based patient selection has promising PFS. Trial registration number The trial was registered with ClinicalTrials.gov (identifier: NCT03426657). The trial was conducted as investigator-sponsored trial (IST).
CRIS-Team Scopus Importer:2022-02-11
Keywords: radioimmunotherapy

Influence and mechanistic principles of radio(chemo) therapy on PD-L1 and EGF-R expression on melanoma and glioblastoma cells - Baeumler, M.; Spiljar, M.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Derer, Anja (DEGRO - Deutsche Gesellschaft für Radioonkologie e.V., 2017)
EVALuna2:32877

Influence of alectinib and crizotinib on ionizing radiation - in vitro analysis of ALK/ROS1-wildtype lung tissue cells - Jost, Tina; Schultz, Ann Kristin; Frey, Benjamin; Vu, Jennifer; Fietkau, Rainer; Distel, Luitpold; Hecht, Markus (Neoplasia, 2022)
(1) Background: Just little is known about the interaction of ALK/ROS1-targeting kinase inhibitors with ionizing radiation (IR), particularly regarding side effects. We investigated the toxicity in two different lung cell lines both ALK/ROS1 wildtype (healthy and tumor origin) as representatives for normal lung tissue; (2) Methods: Human lung cell line BEAS-2B and malignant A549 lung cancer cells (ALK/ROS1 wt) were treated with alectinib or crizotinib, 2 Gy irradiation or a combination of KI and IR. Cell toxicity was analyzed by cell death (Annexin, 7AAD), colony forming, migration assay and live-cell imaging (TMRM, DRAQ7, Caspase3/7). Cell cycle (Hoechst) were analyzed by flow cytometry; (3) Results: Crizotinib led to higher cell death rates than alectinib, when cells were treated with 10 µM KI. Alectinib induced a more intense growth inhibition of colonies. Both inhibitors showed additive effects in combination with irradiation. Combination treatment (IR + KI) does not lead to synergistic effect on neither cell death nor colony forming; (4) Conclusions: The influence of simultaneous KI and IR was studied in non-mutated ALK/ROS1 cell lines. Both KIs seems to be well tolerated in combination with thoracic radiotherapy and lacked synergistic reinforcement in cellular toxicity. This supports the feasibility of ALK/ROS1 inhibition in combination with thoracic irradiation in future clinical trials.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Alectinib; Crizotinib; Lung cells; Normal tissue; Radiotherapy; Side effects

Influence of ex vivo Hyperthermia caused by Warm Water or Microwave Irradiation in a Circulatory System and/or Irradiation on the immunogenic Potential of B16 Melanoma and MCF-7 / MDA-MB-231 Breast Cancer Cells - Hader, Michael; Savcigil, D. P.; Rosin, A.; Gekle, S.; Wadepohl, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of fractional Radio(chemo)therapy on the Expression Patterns of immunocheckpoint Molecules on Glioblastoma Cell Lines - Ladinig, A.; Schatz, Johannes; Fischer, R.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Derer, Anja (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Influence of radiotherapy-induced reactive oxygen species on the immunogenic potential of HPV+ in comparison to HPV- HNSCC - Peitz, L.; Frey, Benjamin; Rieckmann, T.; Fietkau, Rainer; Gaipl, Udo (2017)
EVALuna2:32888

Influence of radiotherapy-induced reactive oxygen species on the immunogenic potential of HPV plus in comparison to HPV-HNSCC - Peitz, L.; Frey, Benjamin; Rieckmann, T.; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36505

Inhibition of ATM or ATR in combination with hypo-fractionated radiotherapy leads to a different immunophenotype on transcript and protein level in HNSCC - Meidenbauer, Julia; Wachter, Matthias; Schulz, Sebastian; Mostafa, Nada; Zülch, Lilli; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Jost, Tina (Frontiers in Oncology, 2024)
Background: The treatment of head and neck tumors remains a challenge due to their reduced radiosensitivity. Small molecule kinase inhibitors (smKI) that inhibit the DNA damage response, may increase the radiosensitivity of tumor cells. However, little is known about how the immunophenotype of the tumor cells is modulated thereby. Therefore, we investigated whether the combination of ATM or ATR inhibitors with hypo-fractionated radiotherapy (RT) has a different impact on the expression of immune checkpoint markers (extrinsic), the release of cytokines or the transcriptome (intrinsic) of head and neck squamous cell carcinoma (HNSCC) cells. Methods: The toxic and immunogenic effects of the smKI AZD0156 (ATMi) and VE-822 (ATRi) in combination with a hypo-fractionated scheme of 2x5Gy RT on HPV-negative (HSC4, Cal-33) and HPV-positive (UM-SCC-47, UD-SCC-2) HNSCC cell lines were analyzed as follows: cell death (necrosis, apoptosis; detected by AnxV/PI), expression of immunostimulatory (ICOS-L, OX40-L, TNFSFR9, CD70) and immunosuppressive (PD-L1, PD-L2, HVEM) checkpoint marker using flow cytometry; the release of cytokines using multiplex ELISA and the gene expression of Cal-33 on mRNA level 48 h post-RT. Results: Cell death was mainly induced by the combination of RT with both inhibitors, but stronger with ATRi. Further, the immune phenotype of cancer cells, not dying from combination therapy itself, is altered predominantly by RT+ATRi in an immune-stimulatory manner by the up-regulation of ICOS-L. However, the analysis of secreted cytokines after treatment of HNSCC cell lines revealed an ambivalent influence of both inhibitors, as we observed the intensified secretion of IL-6 and IL-8 after RT+ATRi. These findings were confirmed by RNAseq analysis and further the stronger immune-suppressive character of RT+ATMi was enlightened. We detected the down-regulation of a central protein of cytoplasmatic sensing pathways of nucleic acids, RIG-1, and found one immune-suppressive target, EDIL3, strongly up-regulated by RT+ATMi. Conclusion: Independent of a restrictive toxicity, the combination of RT + either ATMi or ATRi leads to comprehensive and immune-modulating alterations in HNSCC. This includes pro-inflammatory signaling induced by RT + ATRi but also anti-inflammatory signals. These findings were confirmed by RNAseq analysis, which further highlighted the immune-suppressive nature of RT + ATMi.
CRIS-Team Scopus Importer:2024-10-25
Keywords: ATM inhibition; ATR inhibition; DNA damage repair; HNSCC; immunomodulation; kinase inhibitors

Innovative radiation oncology Together - Precise, Personalized, Human Vision 2030 for radiotherapy & radiation oncology in Germany - Krug, David; Hecht, Markus; Ebert, Nadja; Maeurer, Matthias; Fleischmann, Daniel F.; Fokas, Emmanouil; Straube, Christoph; Nicolay, Nils Henrik; Hoerner-Rieber, Juliane; Schmitt, Daniela; Von Neubeck, Clare; Zamboglou, Constantinos; et al. (Strahlentherapie und Onkologie, 2021)
Purpose Scientific and clinical achievements in radiation, medical, and surgical oncology are changing the landscape of interdisciplinary oncology. The German Society for Radiation Oncology (DEGRO) working group of young clinicians and scientists (yDEGRO) and the DEGRO representation of associate and full professors (AKRO) are aware of the essential role of radiation oncology in multidisciplinary treatment approaches. Together, yDEGRO and AKRO endorsed developing a German radiotherapy & radiation oncology vision 2030 to address future challenges in patient care, research, and education. The vision 2030 aims to identify priorities and goals for the next decade in the field of radiation oncology. Methods The vision development comprised three phases. During the first phase, areas of interest, objectives, and the process of vision development were defined jointly by the yDEGRO, AKRO, and the DEGRO board. In the second phase, a one-day strategy retreat was held to develop AKRO and yDEGRO representatives' final vision from medicine, biology, and physics. The third phase was dedicated to vision interpretation and program development by yDEGRO representatives. Results The strategy retreat's development process resulted in conception of the final vision "Innovative radiation oncology Together - Precise, Personalized, Human." The first term "Innovative radiation oncology" comprises the promotion of preclinical research and clinical trials and highlights the development of a national committee for strategic development in radiation oncology research. The term "together" underpins collaborations within radiation oncology departments as well as with other partners in the clinical and scientific setting. "Precise" mainly covers technological precision in radiotherapy as well as targeted oncologic therapeutics. "Personalized" emphasizes biology-directed individualization of radiation treatment. Finally, "Human" underlines the patient-centered approach and points towards the need for individual longer-term career curricula for clinicians and researchers in the field. Conclusion The vision 2030 balances the ambition of physical, technological, and biological innovation as well as a comprehensive, patient-centered, and collaborative approach towards radiotherapy & radiation oncology in Germany.
CRIS-Team WoS Importer:2021-09-24

Insights into the infiltrative behavior of adamantinomatous craniopharyngioma in a new xenotransplant mouse model - Stache, Christina; Hoelsken, Annett; Schlaffer, Sven-Martin; Heß, Andreas; Metzler, Markus; Frey, Benjamin; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Buslei, Rolf (Brain Pathology, 2015)
Adamantinomatous craniopharyngiomas (adaCP) cause hypothalamic pituitary dysfunction. Elucidation of pathomechanisms underlying tumor progression is essential for the development of targeted chemotherapeutic treatment options. In order to study the mechanisms of tumor outgrowth, we implanted human primary adaCP tissue from three different surgical specimens stereotactically into the brain of immunodeficient mice (n = 20). Three months after tumor inoculation, magnetic resonance imaging and histology confirmed tumor engraftment in all 20 mice (100%) that obtained tissue transplants. The lesions invaded adjoining brain tissue with micro finger-shaped protrusions. Immunohistochemical comparison of the primary tumor and xenotransplants revealed a similar amount of proliferation (Mib-1) and cytokeratin expression pattern (KL-1). Whole tumor reconstruction using serial sections confirmed whirl-like cell clusters with nuclear ?-catenin accumulations at the tumor brain border. These whirls were surrounded by a belt of Claudin-1 expressing cells, showed an activated epidermal growth factor receptor (EGFR) and distinct CD133 as well as p21(WAF1/Cip1) positivity, indicating a tumor stem cell phenotype. Consistent with our previous in vitro studies, intracranial xenotransplants of adaCP confirmed cells with nuclear ?-catenin and activated EGFR being the driving force of tumor outgrowth. This model provides the possibility to study in vivo tumor cell migration and to test novel treatment regimens targeting this tumor stem cell niche.
EVALuna2:7210

'In situ' high pressure confocal Ca2+-fluorescence microscopy in skeletal muscle: A new method to study pressure limits in mammalian cells - Friedrich, Oliver; von Wegner, Frederic; Hartmann, M.; Frey, Benjamin; Sommer, Karl; Ludwig, Horst; Fink, Rainer (Undersea & Hyperbaric Medicine, 2006)
We combined 'in situ' high pressure microscopy with confocal laser scanning microscopy to directly study Ca2+ homeostasis in intact mammalian (murine) skeletal muscle fibres during high pressure exposure up to 35 MPa. Cytosolic Fluo-4 and mitochondrial Rhod-2 Ca2+ fluorescence were simultaneously monitored. To separate changes in Ca2+ and direct/indirect effects of pressure on the dye, experiments in permeabilized ('skinned') muscle fibres were performed at a fixed Ca2+ concentration. Normalized Fluo-4 fluorescence sharply declined up to 10 MPa but showed a plateau between 10 MPa and -35 MPa. In the intact fibre, Fluo-4 fluorescence exponentially decreased during pressurization to 35 MPa with a pressure constant of pi-5 MPa whereas mitochondrial Rhod-2 fluorescence exponentially increased with a four-fold larger pi. Holding the pressure at 35 MPa almost did not change Fluo-4 fluorescence. However, Rhod-2 fluorescence started to decrease after -40 min. Upon decompression, Rhod-2 and Fluo-4 fluorescence increased exponentially with similar pi. However, initial Fluo-4 fluorescence values were not restored. Our results are in agreement with pressure induced Ca2+ leakage from the sarcoplasmic reticulum. Ca2+ might then be taken up in large amounts by mitochondria preventing cytosolic increase in Ca2+. Prolonged pressure applications (-40 min at 35 MPa) seem to destabilize mitochondrial function with release of Ca2+ from mitochondria back into the cytosol and eventually mechanical activation resulting in irreversible contractures. The pressure induced disturbance of Ca2+ homeostasis might have important implications for the pressure exposure limits and/or dive profiles of deep sea mammal

Interaction of Radiotherapy and Hyperthermia with the Immune System: a Brief Current Overview - Sengedorj, Azzaya; Hader, Michael; Frey, Benjamin; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Rückert, Michael (Current Stem Cell Reports, 2022)
Purpose of Review This review focuses on the opposing effects on the immune system of radiotherapy (RT) and the consequences for combined cancer treatment strategies of RT with immunotherapies, including hyperthermia (HT). How RT and HT might affect cancer stem cell populations is also briefly outlined in this context.
CRIS-Team WoS Importer:2022-07-29

Interactions between radiotherapy and immunotherapy - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Onkologe, 2017)
Background. Radiotherapy (RT) acts not only locally on cells but is also capable of inducing systemic reactions. What are the immunological foundations for radiation-induced systemic reactions and how can this knowledge be exploited for the design of multimodal radioimmunotherapy? Ionizing radiation can induce many forms of tumor cell death via DNA damage responses, which have different influences on the immune system. Immunogenic cancer cell death (ICD) is mainly characterized by the release of immune-activating danger signals. Particularly RT with higher single doses induces ICD and thereby triggers anti-tumor immune responses. Lower doses of ionizing radiation foster immune cell infiltration into the tumor; however, RT also ameliorates inflammation and has immune suppressive properties in that the release of transforming growth factor beta (TGF-beta) is increased after RT and immune checkpoint molecules, such as PD-L1 are upregulated. This calls for additional immunotherapies to exploit the properties of RT to act as an in situ vaccine and to subsequently induce local and systemic, abscopal, anti-tumor immune reactions. For the development of efficient radioimmunotherapies, a timely well-reasoned combination of the individual therapies based on knowledge of the immune-modulating modes of action of ionizing radiation has to be worked out. It might be inevitable in the future to develop radiation concepts with differing single doses in one therapy setting to exploit the maximum anti-tumor effect of the immune system.
EVALuna2:32869

Interaktionen von Strahlen- und Immuntherapie - Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; et al. (Onkologe, 2017)
Background: Radiotherapy (RT) acts not only locally on cells but is also capable of inducing systemic reactions. Objective: What are the immunological foundations for radiation-induced systemic reactions and how can this knowledge be exploited for the design of multimodal radioimmunotherapy? Results: Ionizing radiation can induce many forms of tumor cell death via DNA damage responses, which have different influences on the immune system. Immunogenic cancer cell death (ICD) is mainly characterized by the release of immune-activating danger signals. Particularly RT with higher single doses induces ICD and thereby triggers anti-tumor immune responses. Lower doses of ionizing radiation foster immune cell infiltration into the tumor; however, RT also ameliorates inflammation and has immune suppressive properties in that the release of transforming growth factor β (TGF-β) is increased after RT and immune checkpoint molecules, such as PD-L1 are upregulated. This calls for additional immunotherapies to exploit the properties of RT to act as an in situ vaccine and to subsequently induce local and systemic, abscopal, anti-tumor immune reactions. Conclusion: For the development of efficient radioimmunotherapies, a timely well-reasoned combination of the individual therapies based on knowledge of the immune-modulating modes of action of ionizing radiation has to be worked out. It might be inevitable in the future to develop radiation concepts with differing single doses in one therapy setting to exploit the maximum anti-tumor effect of the immune system.
Created from Fastlane, Scopus look-up
Keywords: Immune checkpoint inhibition; Immunogenic cancer cell death; In situ vaccine; Inflammation; Radioimmunotherapy

Interconnection between DNA damage, senescence, inflammation, and cancer - Wunderlich, Roland; Rühle, Paul-Friedrich; Unger, Kristian; Hess, Julia; Zitzelsberger, Horst; Lauber, Kirsten; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Frontiers in Bioscience, 2017)
In order to deal with endogenous and exogenous factors, including radiation or pathogens, cells evolved different strategies. This includes highly complex processes such as DNA damage response, senescence, cell death, and inflammatory reactions. Recent research indicates an interconnection between the mentioned cellular pathways whilst all of them seem to play a role in induction and progression, but also the prevention of cancerous diseases and therefore qualify for potential prevention and treatment strategies. On the basis of their pivotal functions in cancer biology in general, each of the cellular processes represents promising single therapeutic targets. Further, due to their strong interconnection, targeting all of them in a multimodal approach could be another promising strategy to treat cancer. We, therefore, review the mechanisms of DNA damage induction, detection and repair as well as the induction of cell death. Further, features of senescence and mechanism of inflammation induction and abrogation are outlined. A special focus is set on how senescence and inflammation are related to diseases and how targeting them could contribute to improvement of cancer therapies.
EVALuna2:33313

Intra-and Early Postoperative Evaluation of Malperfused Areas in an Irradiated Random Pattern Skin Flap Model Using Indocyanine Green Angiography and Near-Infrared Reflectance-Based Imaging and Infrared Thermography - Müller-Seubert, Wibke; Ostermaier, Patrick; Horch, Raymund E.; Distel, Luitpold; Frey, Benjamin; Cai, Aijia; Arkudas, Andreas (Journal of Personalized Medicine, 2022)
Background: Assessment of tissue perfusion after irradiation of random pattern flaps still remains a challenge. Methods: Twenty-five rats received harvesting of bilateral random pattern fasciocutaneous flaps. Group 1 served as nonirradiated control group. The right flaps of the groups 2–5 were irradiated with 20 Gy postoperatively (group 2), 3 × 12 Gy postoperatively (group 3), 20 Gy preoperatively (group 4) and 3 × 12 Gy preoperatively (group 5). Imaging with infrared thermography, indocyanine green angiography and near-infrared reflectance-based imaging were performed to detect necrotic areas of the flaps. Results: Analysis of the percentage of the necrotic area of the irradiated flaps showed a statistically significant increase from day 1 to 14 only in group 5 (p < 0.05). Indocyanine green angiography showed no differences (p > 0.05) of the percentage of the nonperfused area between all days in group 1 and 3, but a decrease in group 2 in both the left and the right flaps. Infrared thermography and near-infrared reflectance-based imaging did not show evaluable differences. Conclusion: Indocyanine green angiography is more precise in prediction of necrotic areas in random pattern skin flaps when compared to hyperspectral imaging, thermography or clinical impression. Preoperative fractional irradiation with a lower individual dose but a higher total dose has a more negative impact on flap perfusion compared to higher single stage irradiation.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Imaging; Irradiation; Malperfusion

In Vitro Examinations of Cell Death Induction and the Immune Phenotype of Cancer Cells Following Radiative-Based Hyperthermia with 915 MHz in Combination with Radiotherapy - Hader, Michael; Streit, Simon; Rosin, Andreas; Gerdes, Thorsten; Wadepohl, Martin; Bekeschus, Sander; Fietkau, Rainer; Frey, Benjamin; Schlücker, Eberhard; Gekle, Stephan; Gaipl, Udo (Cells, 2021)
Multimodal tumor treatment settings consisting of radiotherapy and immunomodulating agents such as immune checkpoint inhibitors are more and more commonly applied in clinics. In this context, the immune phenotype of tumor cells has a major influence on the anti-tumor immune response as well as the composition of the tumor microenvironment. A promising approach to further boost anti-tumor immune responses is to add hyperthermia (HT), i.e., heating the tumor tissue between 39 degrees C to 45 degrees C for 60 min. One key technique is the use of radiative hyperthermia systems. However, knowledge is limited as to how the frequency of the used radiative systems affects the immune phenotype of the treated tumor cells. By using our self-designed in vitro hyperthermia system, we compared cell death induction and expression of immune checkpoint molecules (ICM) on the tumor cell surface of murine B16 melanoma and human MDA-MB-231 and MCF-7 breast cancer cells following HT treatment with clinically relevant microwaves at 915 MHz or 2.45 GHz alone, radiotherapy (RT; 2 x 5 Gy or 5 x 2 Gy) alone or in combination (RHT). At 44 degrees C, HT alone was the dominant cell death inductor with inactivation rates of around 70% for B16, 45% for MDA-MB-231 and 35% for MCF-7 at 915 MHz and 80%, 60% and 50% at 2.45 GHz, respectively. Additional RT resulted in 5-15% higher levels of dead cells. The expression of ICM on tumor cells showed time-, treatment-, cell line- and frequency-dependent effects and was highest for RHT. Computer simulations of an exemplary spherical cell revealed frequency-dependent local energy absorption. The frequency of hyperthermia systems is a newly identified parameter that could also affect the immune phenotype of tumor cells and consequently the immunogenicity of tumors.
CRIS-Team WoS Importer:2021-07-09

IONISING RADIATION INHIBITS INFLAMMATION IN PATIENTS WITH MUSCULOSKELETAL DISEASES: RADON TREATMENT VS LOW-DOSE RADIATION THERAPY - Shreder, K.; Cucu, A.; Kraft, D.; Lehrian, S.; Kondol, J.; Klein, G.; Frey, Benjamin; Gaipl, Udo; Fournier, C. (2018)
EVALuna2:36523

Ionizing radiation reduces the capacity of activated macrophages to induce T-cell proliferation, but does not trigger dendritic cell-mediated non-targeted effects - Wunderlich, Roland; Rühle, Paul-Friedrich; Roedel, Franz; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (International Journal of Radiation Biology, 2019)
PURPOSE: Previous investigations revealed influences of irradiation up to 2Gy on the cytokine secretion profile of inflammatory and peritoneal mouse macrophages (pMФ). This raised the question if those alterations impact on dendritic cells and consecutive T-cell responses. Further, the impact of irradiation directly on pMФ capacity to induce T-cell responses was analyzed. MATERIALS AND METHODS: pMФ were LPS-activated, irradiated and the expression of activation markers was assessed. Treated pMФ were co-incubated with T-cells to investigate proliferation. To verify modulating properties of pMФ supernatants isolated 24 h after irradiation, bone marrow-derived dendritic cells (BMDC) were co-incubated with supernatants and activation markers as well as the BMDC-induced proliferation of T-cells were measured. RESULTS: pMФ showed a highly significantly decreased major histocompatibility complexII (MHCII) expression within a dose range from 0.7-2Gy. Further, the proliferation rate of cluster of differentiation 4+ (CD4+) T-cells was decreased after co-incubation particularly with 2 Gy irradiated pMФ. The co-incubation of BMDC with supernatants of activated, irradiated pMФ significantly reduced the CD40 expression, but did not impact on the BMDC-derived induction of T-cell proliferation. CONCLUSIONS: Inflammatory macrophages being exposed to irradiation have the potential to modulate consecutive adaptive immune reactions. But supernatants of irradiated macrophages do not influence the dendritic cells (DC)-mediated induction of T cell proliferation.
EVALuna2:36459

Irradiated HPV+ head and neck cancer cells induce an interferon related gene expression in various innate immune cell subtypes - Wunderlich, R.; Unger, K.; Hess, J.; Lauber, K.; Frey, Benjamin; Gaipl, Udo; Zitzelsberger, H. (2017)
EVALuna2:32929

Kill and spread the word: stimulation of antitumor immune responses in the context of radiotherapy - Gaipl, Udo; Multhoff, Gabriele; Scheithauer, Heike; Lauber, Kirsten; Hehlgans, Stefanie; Frey, Benjamin; Roedel, Franz (Immunotherapy, 2014)
Besides the direct, targeted effects of ionizing irradiation (x-ray) on cancer cells, namely DNA damage and cell death induction, indirect, nontargeted ones exist, which are mediated in large part by the immune system. Immunogenic forms of tumor cell death induced by x-ray, including immune modulating danger signals like the heat shock protein 70, adenosine triphosphate, and high-mobility group box 1 protein are presented. Further, antitumor effects exerted by cells of the innate (natural killer cells) as well as adaptive immune system (T cells activated by dendritic cells) are outlined. Tumor cell death inhibiting molecules such as survivin are introduced as suitable target for molecularly tailored therapies in combination with x-ray. Finally, reasonable combinations of immune therapies with radiotherapy are discussed.
EVALuna2:18189

LDRT induces long-lasting Pain and Immunomodulating Effects in chronic degenerative and inflammatory Diseases - Results from the IMMO-LDRT01 Study - Donaubauer, Anna-Jasmina; Weissmann, Thomas; Fröhlich, Birgitta; Becker, Ina; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

LOCAL LOW DOSE RADIATION INDUCES SYSTEMIC IMMUNE ALTERATIONS IN TWO EXPERIMENTAL MODELS OF INFLAMMATORY ARTHRITIS - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (ANNALS OF THE RHEUMATIC DISEASES, 2019)
CRIS-Team WoS Importer:2019-05-17

Local X-ray Therapy induces systemic Immune Modulations in an experimental Model of rheumatoid Arthritis - Deloch, Lisa; Rueckert, M.; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-09-25

Longitudinal C-reactive protein (CRP) as an individualized dynamic predictor for metastatic cancer patients treated with immune checkpoint inhibitors: Findings from the prospective ST-ICI cohort. - Zhou, Jian-Guo; Ma, Hu; Gaipl, Udo; Frey, Benjamin; Hecht, Markus; Fietkau, Rainer (CANCER RESEARCH, 2021)
CRIS-Team WoS Importer:2021-09-03

Longitudinal Spread Analysis of Patients with Glioblastoma: high Prevalence of discontinuous Tumor Foci with no strong Relation to the Fibrous Tract System - Schmitter, Charlotte; Weissmann, Thomas; Mansoorian, Sina; Lettmaier, Sebastian; Semrau, Sabine; Schmidt, Manfred; Heiß, Rafael; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low and moderate doses of ionizing radiation up to 2 Gy modulate transmigration and chemotaxis of activated macrophages, provoke an anti-inflammatory cytokine milieu, but do not impact upon viability and phagocytic function - Wunderlich, Roland; Ernst, A.; Roedel, F.; Fietkau, Rainer; Ott, O.; Lauber, K.; Frey, Benjamin; Gaipl, Udo (Clinical and Experimental Immunology, 2015)
Benign painful and inflammatory diseases have been treated for decades with low/moderate doses of ionizing radiation (LD-X-irradiation). Tissue macrophages regulate initiation and resolution of inflammation by the secretion of cytokines and by acting as professional phagocytes. Having these pivotal functions, we were interested in how activated macrophages are modulated by LD-X-irradiation, also with regard to radiation protection issues and carcinogenesis. We set up an ex-vivo model in which lipopolysaccharide pre-activated peritoneal macrophages (pM?) of radiosensitive BALB/c mice, mimicking activated macrophages under inflammatory conditions, were exposed to X-irradiation from 0·01 Gy up to 2 Gy. Afterwards, the viability of the pM?, their transmigration and chemotaxis, the phagocytic behaviour, the secretion of inflammatory cytokines and underlying signalling pathways were determined. Exposure of pM? up to a single dose of 2 Gy did not influence their viability and phagocytic function, an important fact regarding radiation protection. However, significantly reduced migration, but increased chemotaxis of pM? after exposure to 0·1 or 0·5 Gy, was detected. Both might relate to the resolution of inflammation. Cytokine analyses revealed that, in particular, the moderate dose of 0·5 Gy applied in low-dose radiotherapy for inflammatory diseases results in an anti-inflammatory cytokine microenvironment of pM?, as the secretion of the proinflammatory cytokine interleukin (IL)-1? was reduced and that of the anti-inflammatory cytokine transforming growth factor (TGF)-? increased. Further, the reduced secretion of IL-1? correlated with reduced nuclear translocation of nuclear factor (NF)-?B p65, starting at exposure of pM? to 0·5 Gy of X-irradiation. We conclude that inflammation is modulated by LD-X-irradiation via changing the inflammatory phenotype of macrophages.
EVALuna2:18185

LOW-DOSE IONISING RADIATION INHIBITS ADIPOKINE INDUCED INFLAMMATION IN RHEUMATOID ARTHRITIS - Shreder, K.; Cucu, A.; Deloch, Lisa; Frey, Benjamin; Gaipl, Udo; Durante, M.; Fournier, C. (2016)
EVALuna2:32936

Low dose ionising radiation leads to a NF-?B dependent decreased secretion of active IL-1? by activated macrophages with a discontinuous dose-dependency - Lödermann, Barbara; Wunderlich, Roland; Frey, Silke; Schorn, Christine; Stangl, Sonja; Roedel, Franz; Keilholz, Ludwig; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (International Journal of Radiation Biology, 2012)
Therapy with low doses of ionising radiation (X-rays) exerts anti-inflammatory effects. Little is known about whether and how low doses of X-ray treatment modulate the inflammatory phenotype of macrophages, especially the secretion of Interleukin-1beta (IL-1?).Macrophages were differentiated from human THP-1 monocytes, activated with lipopolysaccharide (LPS), treated with distinct low doses of X-rays, and co-activated with monosodium urate crystals (MSU) to induce inflammasome activation. Secretion of IL-1? was analysed by an enzyme-linked immunosorbent assay (ELISA) and Western blot. Furthermore, we analysed the intracellular amounts of the serine/threonine protein kinase B (named: Akt), mitogen-activated protein kinase p38 (p38), the v-rel reticuloendotheliosis viral oncogene homolog A (RelA), and pro- and cleaved IL-1?.Low dose X-rays led to decreased secretion of active IL-1? in a manner discontinuous with dose which was most pronounced after 0.5 or 0.7 Gy. Passive release of lactate dehydrogenase (LDH) was not influenced by X-rays. The decreased secretion of IL-1? correlated with reduced translocation of RelA, being part of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-?B) complex, into the nucleus. After 0.5 or 0.7 Gy of X-rays, the intracellular protein amounts of up (p38) and downstream molecules (Akt) of NF-?B were reduced in activated macrophages, as were the pro- and cleaved forms of IL-1?.Distinct low doses of X-rays induce an anti-inflammatory phenotype of activated macrophages by lowering the amount of secreted IL-1? in a NF-?B dependent manner.
EVALuna2:12777

Low-Dose Irradiation Differentially Impacts Macrophage Phenotype in Dependence of Fibroblast-Like Synoviocytes and Radiation Dose - Fuchs, Jana; Rueckert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (Journal of Immunology Research, 2019)
Rheumatoid arthritis (RA) is a multifactorial autoimmune disease whose main hallmark is inflammation and destruction of the joints. Two cell types within the synovium that play an important role in RA are fibroblast-like synoviocytes (FLS) and macrophages. The latter innate immune cells show a high plasticity in their phenotype and are central in inflammatory processes. Low-dose radiotherapy (LD-RT) with particularly a single dose of 0.5 Gy has been demonstrated to have a positive impact on pain, inflammation, and bone in inflamed joints. We now examined for the first time how LD-RT influences FLS and bone marrow-derived macrophages in co-culture systems of an experimental model of RA to reveal further mechanisms of immune modulatory effects of low and intermediate dose of ionizing radiation. For this, the bone marrow of hTNF-alpha tg mice was differentiated either with cytokines to obtain key macrophage phenotypes (M0, M1, and M2) or with supernatants (SN) of untreated or irradiated FLS. Flow cytometry analyses were used to analyse the impact of radiation (0.1, 0.5, 1.0, and 2.0 Gy) on the phenotype of macrophages in the presence or absence of SN of FLS. LD-RT had no impact on cytokine-mediated macrophage polarization in M0, M1, or M2 macrophages. However, SN of irradiated FLS particularly reduced CD206 expression on macrophages. Macrophage phenotype was stable when being in contact with SN of nonirradiated FLS, but significantly increased surface expression of CD206 and slightly decreased CD80 and CD86 expression were observed when macrophage themselves were irradiated with 0.5 Gy under these microenvironmental conditions, again highlighting discontinuous dose dependencies in the low and intermediate dose range. One can conclude that FLS-dependent microenvironmental conditions have a slight influence on the modulation of macrophage phenotype under radiation exposure conditions. Future studies are needed to reveal the impact of radiation exposure on the functions of treated macrophages under such microenvironmental conditions.
CRIS-Team WoS Importer:2019-09-13

Low-dose irradiation has an impact on bone metabolism as well as on local and systemic immune cell-mediated inflammation - Deloch, Lisa; Rückert, Michael; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36495

Low-dose irradiation reduces fibroblast-like synoviocytes and impacts on bone metabolism in dependence of the inflammatory state - Liberg, J.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32878

Low-dose irradiation shifts macrophages to a more immune suppressive phenotype in a clinically relevant setting together with inflammatory fibroblast-like synoviocytes - Liberg, J.; Rueckert, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32887

Low dose radiation alters the inflammatory phenotype of fibroblast-like synoviocytes and impacts on bone metabolism - Frey, Benjamin; Liberg, J.; Derer, Anja; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32862

LOW DOSE RADIATION ALTERS THE INFLAMMATORY PHENOTYPE OF FIBROBLAST-LIKE SYNOVIOCYTES AND MACROPHAGES AND STIMULATES OSTEOBLASTS - Deloch, Lisa; Liberg, Jana; Rückert, Michael; Hueber, Axel; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2017)
EVALuna2:32907

LOW DOSE RADIATION HAS A POSITIVE IMPACT ON BONE METABOLISM IN AN EXPERIMENTAL MODEL OF INFLAMMATORY ARTHRITIS - Deloch, Lisa; Rückert, Michael; Hueber, Axel; Herrmann, Martin; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36516

Low Dose Radiation Therapy Induces Long-Lasting Reduction of Pain and Immune Modulations in the Peripheral Blood - Interim Analysis of the IMMO-LDRT01 Trial - Donaubauer, Anna-Jasmina; Becker, Ina; Weissmann, Thomas; Fröhlich, Birgitta; Munoz, Luis Enrique; Gryc, Thomas; Denzler, Manuel; Ott, Oliver; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Frontiers in Immunology, 2021)
The treatment of chronic inflammatory and degenerative diseases by low dose radiation therapy (LDRT) is promising especially for patients who were refractory for classical therapies. LDRT aims to reduce pain of patients and to increase their mobility. Although LDRT has been applied since the late 19th century, the immunological mechanisms remain elusive. Within the prospective IMMO-LDRT01 trial (NCT02653079) the effects of LDRT on the peripheral blood immune status, as well as on pain and life quality of patients have been analyzed. Blood is taken before and after every serial irradiation with a single dose per fraction of 0.5Gy, as well as during follow-up appointments in order to determine a detailed longitudinal immune status by multicolor flow cytometry. Here, we report the results of an interim analysis of 125 patients, representing half the number of patients to be recruited. LDRT significantly improved patients' pain levels and induced distinct systemic immune modulations. While the total number of leukocytes remained unchanged in the peripheral blood, LDRT induced a slight reduction of eosinophils, basophils and plasmacytoid dendritic cells and an increase of B cells. Furthermore, activated immune cells were decreased following LDRT. Especially cells of the monocytic lineage correlated to LDRT-induced improvements of clinical symptoms, qualifying these immune cells as predictive biomarkers for the therapeutic success. We conclude that LDRT improves pain of the patients by inducing systemic immune modulations and that immune biomarkers could be defined for prediction by improved patient stratification in the future.
CRIS-Team WoS Importer:2021-11-12

Low dose radiation therapy, particularly with 0.5 gy, improves pain in degenerative joint disease of the fingers: Results of a retrospective analysis - Donaubauer, Anna-Jasmina; Zhou, Jianguo; Ott, Oliver J.; Putz, Florian; Fietkau, Rainer; Keilholz, Ludwig; Gaipl, Udo; Frey, Benjamin; Weissmann, Thomas (International Journal of Molecular Sciences, 2020)
Low-dose radiation therapy (LDRT) has been successfully established for decades as an alternative analgesic treatment option for patients suffering from chronic degenerative and inflammatory diseases. In this study, 483 patients were undergoing LDRT for degenerative joint disease of the fingers and thumb at the University Hospital Erlangen between 2004 and 2019. Radiotherapy was applied according to the German guidelines for LDRT. Several impact factors on therapeutic success, such as the age and gender, the number of affected fingers, the single and cumulative dose, as well as the number of series, were investigated. In summary, 70% of the patients showed an improvement of their pain following LDRT. No significant impact was found for the factors age, gender, the number of series or the cumulative dosage. Patients with an involvement of the thumb showed a significantly worse outcome compared to patients with an isolated affection of the fingers. In this cohort, patients receiving a single dose of 0.5 Gy reported a significantly better outcome than patients receiving 1.0 Gy, strongly suggesting a reduction in the total dose. In summary, LDRT is a good alternative treatment option for patients suffering from degenerative and inflammatory joint disease of the fingers.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Chronic degenerative and inflammatory diseases; Degenerative joint disease of the fingers; LDRT; Low-dose radiation therapy; Osteoarthritis; Subjective pain level

Low-Dose Radiotherapy Ameliorates Advanced Arthritis in hTNF-α tg Mice by Particularly Positively Impacting on Bone Metabolism - Deloch, Lisa; Derer, Anja; Hueber, Axel; Herrmann, Martin; Schett, Georg; Wölfelschneider, Jens; Hahn, Jonas; Rühle, Paul-Friedrich; Stillkrieg, Willy; Fuchs, Jana; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2018)
Inflammation and bone erosion are central in rheumatoid arthritis (RA). Even though effective medications for control and treatment of RA are available, remission is only seen in a subset of patients. Treatment with low-dose radiotherapy (LD-RT) which has been already successfully used for amelioration of symptoms in benign diseases should be a promising approach to reduce pain, inflammation, and particularly bone erosion in patients with RA. Even though anti-inflammatory effects of LD-RT are already described with non-linear dose response relationships, and pain-reducing effects have been clinically observed, the underlying mechanisms are widely unknown. Besides immune cells many other cell types, such as fibroblast-like synoviocytes (FLS), osteoclasts, and osteoblast are present in the affected joint and might be modulated by LD-RT. For this study, these cell types were obtained from human tumor necrosis factor-α transgenic (hTNF-α tg) mice and were consecutively exposed to different doses of ionizing radiation (0.1, 0.5, 1.0, and 2.0 Gy, respectively) in vitro. In order to study the in vivo effects of LD-RT within the arthritic joint, hind paws of arthritic hTNF-α tg mice were locally irradiated with 0.5 Gy, a single dose per fraction that is known for good clinical responses. Starting at a dose of 0.5 Gy, proliferation of FLS was reduced and apoptosis significantly enhanced with no changes in necrosis. Further, expression of RANK-L was slightly reduced following irradiation with particularly 0.5 Gy. Starting from 0.5 Gy, the numbers of differentiated osteoclasts were significantly reduced, and a lower bone resorbing activity of treated osteoclasts was also observed, as monitored via pit formation and Cross Laps presence. LD-RT had further a positive effect on osteoblast-induced mineralization in a discontinuous dose response relationship with 0.5 Gy being most efficient. An increase of the gene expression ratio of OPG/RANK-L at 0.1 and 0.5 Gy and of production of OPG at 0.5 and 1.0 Gy was observed. In vivo, LD-RT resulted in less severe arthritis in arthritic hTNF-α tg mice and in significant reduction of inflammatory and erosive area with reduced osteoclasts and neutrophils. Locally applied LD-RT can, therefore, induce a beneficial micro-environment within arthritic joints by predominantly positively impacting on bone metabolism.
EVALuna2:34663
Keywords: rheumatoid arthritis; inflammation; low-dose radiotherapy; bone metabolism; synovial-like fibroblasts; osteoclasts; osteoblasts

Low-dose Radiotherapy for painful Finger Joint Arthrosis - Weissmann, T.; Ott, Oliver; Putz, Florian; Becker, Ina; Fietkau, Rainer; Donaubauer, Anna-Jasmina; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-09-25

Low-Dose Radiotherapy Has No Harmful Effects on Key Cells of Healthy Non-Inflamed Joints - Deloch, Lisa; Rückert, Michael; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (International Journal of Molecular Sciences, 2018)
Low-dose radiotherapy (LD-RT) for benign inflammatory and/or bone destructive diseases has been used long. Therefore, mechanistic investigations on cells being present in joints are mostly made in an inflammatory setting. This raises the question whether similar effects of LD-RT are also seen in healthy tissue and thus might cause possible harmful effects. We performed examinations on the functionality and phenotype of key cells within the joint, namely on fibroblast-like synoviocytes (FLS), osteoclasts and osteoblasts, as well as on immune cells. Low doses of ionizing radiation showed only a minor impact on cytokine release by healthy FLS as well as on molecules involved in cartilage and bone destruction and had no significant impact on cell death and migration properties. The bone resorbing abilities of healthy osteoclasts was slightly reduced following LD-RT and a positive impact on bone formation of healthy osteoblasts was observed after in particular exposure to 0.5 Gray (Gy). Cell death rates of bone-marrow cells were only marginally increased and immune cell composition of the bone marrow showed a slight shift from CD8⁺ to CD4⁺ T cell subsets. Taken together, our results indicate that LD-RT with particularly a single dose of 0.5 Gy has no harmful effects on cells of healthy joints.
EVALuna2:36453

Low-Dose Radiotherapy is highly effective in the Treatment of painful Finger Polyarthrosis - Weissmann, Thomas; Gaipl, Udo; Putz, Florian; Hecht, Markus; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Fietkau, Rainer; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-dose Radiotherapy is highly effective in the Treatment of Patients with painful Ankle Arthrosis - Weissmann, Thomas; Putz, Florian; Hecht, Markus; Zhou, Jianguo; Donaubauer, Anna-Jasmina; Fietkau, Rainer; Gaipl, Udo; Ott, Oliver; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Low-Dose Radiotherapy Leads to a Systemic Anti-Inflammatory Shift in the Pre-Clinical K/BxN Serum Transfer Model and Reduces Osteoarthritic Pain in Patients - Weissmann, Thomas; Rückert, Michael; Zhou, Jianguo; Seeling, Michaela; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Nimmerjahn, Falk; Ott, Oliver; Hecht, Markus; Putz, Florian; Fietkau, Rainer; Frey, Benjamin; et al. (Frontiers in Immunology, 2022)
Osteoarthritis (OA) is the leading degenerative joint disease in the western world and leads, if left untreated, to a progressive deterioration of joint functionality, ultimately reducing quality of life. Recent data has shown, that especially OA of the ankle and foot are among the most frequently affected regions. Current research in OA points towards a complex involvement of various cell and tissue types, often accompanied by inflammation. Low-dose radiotherapy (LDRT) is widely used for the treatment of degenerative and inflammatory diseases. While the reported analgesic effects are well known, the underlying molecular mechanisms are only poorly understood. We therefore correlated a clinical approach, looking at pain reduction in 196 patients treated with LDRT with a pre-clinical approach, utilizing the K/BxN serum transfer mouse model using flow cytometry and multiplex ELISA for analysis. While an improvement of symptoms in the majority of patients was found, patients suffering from symptoms within the tarsi transversa show a significantly lower level of improvement. Further, a significant impact of therapy success was detected depending on whether only one or both feet were affected. Further, patients of younger age showed a significantly better outcome than older ones while needing fewer treatment series. When looking on a cellular level within the mouse model, a systemic alteration of immune cells namely a shift from CD8+ to CD4+ T cells and reduced numbers of DCs was observed. A general reduction of inflammatory cytokines was detected, with significant alterations in IL-4 and IL-17 levels, all of which could potentially be responsible for the highly effective clinical improvement in patients. Taken together our data indicate that LDRT can be regarded as a highly effective treatment option for patients suffering from OA of the foot and ankle, in terms of analgesic effects, especially in younger patients. Furthermore, the observed effects are mediated by an interplay of cellular and soluble immune factors, as observed in the K/BxN serum transfer model. With this interdisciplinary approach we aim to encourage the usage of LDRT as an additive treatment strategy not only as a last resort, but also earlier in the course of disease.
CRIS-Team Scopus Importer:2022-01-28
Keywords: foot; K/BxN serum transfer; low-dose radiotherapy; mouse model; osteoarthritis; pain; rheumatoid arthritis; X-rays

Low-dose radiotherapy: Mayday, mayday. We've been hit! - Ott, Oliver J.; Micke, Oliver; Muecke, Ralph; Niewald, Marcus; Roedel, Franz; Schaefer, Ulrich; Seegenschmiedt, M. H.; Arenas, Meritxell; Frey, Benjamin; Gaipl, Udo (Strahlentherapie und Onkologie, 2019)
CRIS-Team WoS Importer:2019-04-09

Low-dose radiotherapy of osteoarthritis: from biological findings to clinical effects-challenges for future studies - Weissmann, Thomas; Rückert, Michael; Putz, Florian; Donaubauer, Anna-Jasmina; Hecht, Markus; Schnellhardt, Sören; Schubert, Philipp; Roesch, Johannes; Höfler, Daniel; Ott, Oliver; Haderlein, Marlen; Lettmaier, Sebastian; et al. (Strahlentherapie und Onkologie, 2023)

Low-dose Radiotherapy with X-rays and Radon leads to different immunological Changes in a Mouse Model for Rheumatoid Arthritis - Deloch, Lisa; Rückert, Michael; Maier, A.; Hinrichs, A.; Weissmann, T.; Seeling, Michaela; Nimmerjahn, Falk; Flohr, A. -S.; Eckert, D.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Low-dose X-Rays influence the Macrophage Polarization interacting with Synovial Fibroblasts in an anti-inflammatory Manner - Fuchs, J.; Rueckert, M.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Low- vs. high-dose radiotherapy in Graves’ ophthalmopathy: a retrospective comparison of long-term results - Weissmann, Thomas; Lettmaier, Sebastian; Donaubauer, Anna-Jasmina; Bert, Christoph; Schmidt, Manfred; Kruse, Friedrich; Ott, Oliver; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Putz, Florian (Strahlentherapie und Onkologie, 2021)
Purpose: Radiotherapy represents an effective treatment option in Graves’ ophthalmopathy (GO), leading to palliation of clinical symptoms. However, there are only a limited number of trials comparing the effectiveness of low- vs. high-dose radiotherapy. Methods: We analyzed 127 patients treated with radiotherapy for stage 3/4 GO (NOSPECS classification). Patients were treated with single doses of 2.0 Gy (cumulative dose 20 Gy) until 2007, afterwards a single dose of 0.8 Gy (cumulative dose 4.8 Gy) was applied. With a median follow-up-time of 9.0 years, the treatment efficacy (overall improvement, sense of eye pressure, lid edema, ocular motility, exophthalmos, subjective vision, and diplopia) and adverse effects were analyzed by a standardized survey. Results: Overall, 63.8% described improvement of symptoms after radiotherapy. No significant differences in overall treatment response and improvement of main outcome measures between low- or high-dose radiotherapy treatments are detectable, while low-dose radiotherapy leads significantly more often to retreatment (13.1% vs. 1.7%, p = 0.016). The main independent predictor of treatment response is the presence of lid edema (odds ratio, OR, 3.53; p = 0.006). Conclusion: At long-term follow-up, the majority of patients reported palliation of symptoms with limited adverse effects, suggesting clinical effectiveness of radiotherapy for amelioration of GO symptoms independent of low- or high-dose radiotherapy.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Exophthalmos; Graves’ ophthalmopathy; Low dose radiation therapy; Radiotherapy; Thyroid eye disease

Machine Learning-assisted immunophenotyping of peripheral blood identifies innate immune cells as best predictor of response to induction chemo-immunotherapy in head and neck squamous cell carcinoma – knowledge obtained from the CheckRad-CD8 trial - Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Tianyu, Xie; Eckstein, Markus; Donaubauer, Anna-Jasmina; Klautke, Gunther; Illmer, Thomas; Fleischmann, Maximilian; Laban, Simon; Hautmann, Matthias G.; Tamaskovics, Bálint; et al. (Neoplasia, 2024)
Purpose: Individual prediction of treatment response is crucial for personalized treatment in multimodal approaches against head-and-neck squamous cell carcinoma (HNSCC). So far, no reliable predictive parameters for treatment schemes containing immunotherapy have been identified. This study aims to predict treatment response to induction chemo-immunotherapy based on the peripheral blood immune status in patients with locally advanced HNSCC. Methods: The peripheral blood immune phenotype was assessed in whole blood samples in patients treated in the phase II CheckRad-CD8 trial as part of the pre-planned translational research program. Blood samples were analyzed by multicolor flow cytometry before (T1) and after (T2) induction chemo-immunotherapy with cisplatin/docetaxel/durvalumab/tremelimumab. Machine Learning techniques were used to predict pathological complete response (pCR) after induction therapy. Results: The tested classifier methods (LDA, SVM, LR, RF, DT, and XGBoost) allowed a distinct prediction of pCR. Highest accuracy was achieved with a low number of features represented as principal components. Immune parameters obtained from the absolute difference (lT2-T1l) allowed the best prediction of pCR. In general, less than 30 parameters and at most 10 principal components were needed for highly accurate predictions. Across several datasets, cells of the innate immune system such as polymorphonuclear cells, monocytes, and plasmacytoid dendritic cells are most prominent. Conclusions: Our analyses imply that alterations of the innate immune cell distribution in the peripheral blood following induction chemo-immuno-therapy is highly predictive for pCR in HNSCC.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chemotherapy; HNSCC; Immune phenotyping; Immunotherapy; Induction therapy

Machine learning based on blood test biomarkers predicts fast progression in advanced NSCLC patients treated with immunotherapy - Zhou, Jian Guo; Yang, Jie; Wang, Haitao; Wong, Ada Hang Heng; Tan, Fangya; Chen, Xiaofei; He, Si Si; Shen, Gang; Wang, Yun Jia; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; et al. (BMJ Oncology, 2024)
Objective Fast progression (FP) represents a desperate situation for advanced non-small cell lung cancer (NSCLC) patients undergoing immune checkpoint inhibitor therapy. We aimed to develop a predictive framework based on machine learning (ML) methods to identify FP in advanced NSCLC patients using blood test biomarkers. Methods and analysis We extracted data of 1546 atezolizumab-treated patients from four multicentre clinical trials. In this study, patients from the OAK trial were taken for model training, whereas patients from the other trials were used for independent validations. The FP prediction model was developed using 21 pretreatment blood test variables in seven ML approaches. Prediction performance was evaluated by the receiver operating characteristic (ROC) curve. Results The prevalence of FP was 7.6% (118 of 1546) in all atezolizumab-treated patients. The most important variables for the prediction model were: C reactive protein, neutrophil count, lactate dehydrogenase and alanine transaminase. The Support Vector Machine (SVM) algorithm applied to these four blood test parameters demonstrated good performance: the area under the ROC curve obtained from the training cohort (OAK), validation cohort 1 (BIRCH) and cohort 2 (merged POPLAR and FIR) were 0.908, 0.666 and 0.776, respectively. In addition, the absolute difference in median survival between the SVM-predicted FP and non-FP groups was significant in both progression-free survival and overall survival (p<0.001). Conclusion SVM trained using a 4-biomarker panel has good performance in predicting the occurrence of FP regardless of programmed cell death ligand 1 expression, hence providing evidence for decision-making in single-agent atezolizumab immunotherapy for patients with advanced NSCLC.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Biomarkers; Immunotherapy; Lung cancer (non-small cell)

Magnetic Resonance thermometry images of hyperthermia treatments of sarcomas for prediction of therapy responses-need of data reprocessing and cleaning - Khatun, Rupali; Hader, Michael; Schmidt, Manfred; Bert, Christoph; Wadepohl, Martin; Fietkau, Rainer; Ott, Jessica; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Measuring the systemic immune-modulating effects of radiation - Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:36521

Mitoxantrone-loaded nanoparticles for magnetically controlled tumor therapy–induction of tumor cell death, release of danger signals and activation of immune cells - Ratschker, Teresa; Egenberger, Laura; Alev, Magdalena; Zschiesche, Lisa; Band, Julia; Schreiber, Eveline; Frey, Benjamin; Derer, Anja; Alexiou, Christoph; Janko, Christina (Pharmaceutics, 2020)
Stimulating the patient`s immune system represents a promising therapeutic strategy to fight cancer. However, low immunogenicity of the tumor cells within an immune suppressive milieu often leads to weak anti-tumor immune responses. Additionally, the immune system may be impaired by accompanying aggressive chemotherapies. We show that mitoxantrone, bound to superparamagnetic iron oxide nanoparticles (SPIONs) as the transport system, can be magnetically accumulated in adherent HT-29 colon carcinoma cells, thereby inducing the same cell death phenotype as its soluble counterpart, a chemotherapeutic agent and prototypic inductor of immunogenic cell death. The nanoparticle-loaded drug induces cell cycle stop, apoptosis and secondary necrosis in a dose-and time-dependent manner comparable to the free drug. Cell death was accompanied by the release of interleukin-8 and damage-associated molecular patterns (DAMPs) such as HSP70 and ATP, which fostered chemotactic migration of monocytes and maturation of dendritic cells. We furthermore ensured absence of endotoxin contaminations and compatibility with erythrocytes and platelets and investigated the influence on plasma coagulation in vitro. Summarizing, with magnetic enrichment, mitoxantrone can be accumulated at the desired place, sparing healthy peripheral cells and tissues, such as immune cells. Conserving immune competence in cancer patients in the future might allow combined therapeutic approaches with immune therapies (e.g. checkpoint inhibitors).
CRIS-Team Scopus Importer:2020-10-09
Keywords: Cell death; Chemotherapy; Iron oxide nanoparticles; Magnetic drug targeting; Nanomedicine

Modern Radiotherapy Concepts and the Impact of Radiation on Immune Activation - Derer, Anja; Hartmann, Josefin; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (Frontiers in Oncology, 2016)
Even though there is extensive research carried out in radiation oncology, most of the clinical studies focus on the effects of radiation on the local tumor tissue and deal with normal tissue side effects. The influence of dose fractionation and timing particularly with regard to immune activation is not satisfactorily investigated so far. This review, therefore, summarizes current knowledge on concepts of modern radiotherapy (RT) and evaluates the potential of RT for immune activation. Focus is set on radiation-induced forms of tumor cell death and consecutively the immunogenicity of the tumor cells. The so-called non-targeted, abscopal effects can contribute to anti-tumor responses in a specific and systemic manner and possess the ability to target relapsing tumor cells as well as metastases. The impact of distinct RT concepts on immune activation is outlined and pre-clinical evidence and clinical observations on RT-induced immunity will be discussed. Knowledge on the radiosensitivity of immune cells as well as clinical evidence for enhanced immunity after RT will be considered. While stereotactic ablative body radiotherapy seem to have a beneficial outcome over classical RT fractionation in pre-clinical animal models, in vitro model systems suggest an advantage for classical fractionated RT for immune activation. Furthermore, the optimal approach may differ based on the tumor site and/or genetic signature. These facts highlight that clinical trials are urgently needed to identify whether high-dose RT is superior to induce anti-tumor immune responses compared to classical fractionated RT and in particular how the outcome is when RT is combined with immunotherapy in selected tumor entities.
EVALuna2:18361

Modulation of Differentiation and Bone Resorbing Activity of Human (Pre-) Osteoclasts After X-Ray Exposure - Eckert, Denise; Rapp, Felicitas; Tsedeke, Ayele Taddese; Kraft, Daniela; Wente, Isabell; Molendowska, Jessica; Basheer, Sidra; Langhans, Markus; Meckel, Tobias; Friedrich, Thomas; Donaubauer, Anna-Jasmina; Becker, Ina; et al. (Frontiers in Immunology, 2022)
Low-dose radiotherapy (LD-RT) is a local treatment option for patients with chronic degenerative and inflammatory diseases, in particular musculoskeletal diseases. Despite reported analgesic and anti-inflammatory effects, cellular and molecular mechanisms related to osteoimmunological effects are still elusive. Here we test the hypothesis that X-irradiation inhibits the differentiation of precursor osteoclasts into mature osteoclasts (mOC) and their bone resorbing activity. Circulating monocytes from healthy donors were isolated and irradiated after attachment with single or fractionated X-ray doses, comparable to an LD-RT treatment scheme. Then monocytes underwent ex vivo differentiation into OC during cultivation up to 21 days, under conditions mimicking the physiological microenvironment of OC on bone. After irradiation, apoptotic frequencies were low, but the total number of OC precursors and mOC decreased up to the end of the cultivation period. On top, we observed an impairment of terminal differentiation, i.e. a smaller fraction of mOC, reduced resorbing activity on bone, and release of collagen fragments. We further analyzed the effect of X-irradiation on multinucleation, resulting from the fusion of precursor OC, which occurs late during OC differentiation. At 21 days after exposure, the observation of smaller cellular areas and a reduced number of nuclei per mOC suggest an impaired fusion of OC precursors to form mOC. Before, at 14 days, the nuclear translocation of Nuclear Factor Of Activated T Cells 1 (NFATc1), a master regulator of osteoclast differentiation and fusion, was decreased. In first results, obtained in the frame of a longitudinal LD-RT study, we previously reported a pain-relieving effect in patients. However, in a subgroup of patients suffering from Calcaneodynia or Achillodynia, we did not observe a consistent decrease of established blood markers for resorption and formation of bone, or modified T cell subtypes involved in regulating these processes. To assess the relevance of changes in bone metabolism for other diseases treated with LD-RT will be subject of further studies. Taken together, we observed that in vitro X-irradiation of monocytes results in an inhibition of the differentiation into bone-resorbing OC and a concomitant reduction of resorbing activity. The detected reduced NFATc1 signaling could be one underlying mechanism.
CRIS-Team WoS Importer:2022-06-03

Modulation of inflammation by low and high doses of ionizing radiation: Implications for benign and malign diseases - Frey, Benjamin; Hehlgans, Stephanie; Rödel, Franz; Gaipl, Udo (Cancer Letters, 2015)
Inflammation is a homeostatic mechanism aiming to maintain tissue integrity. The underlying immunological mechanisms and the interrelationship between ionizing radiation and inflammation are complex and multifactorial on cellular and chemical levels. On the one hand, radiation with single doses exceeding 1 Gy might initiate inflammatory reactions and thereby impact on tumor development. On the other hand, radiation is capable of attenuating an established inflammatory process, which is clinically used for the treatment of inflammatory and degenerative diseases with low-dose radiotherapy (single dose <1 Gy). At higher doses, ionizing radiation, especially in combination with additional immune stimulation, fosters the induction of immunogenic forms of tumor cell death and shifts the tumor microenvironment as well as the infiltration of immune cells from an anti- to a pro-inflammatory state. Distinct tumor infiltrating immune cells predict the response to radiochemotherapy in a multitude of tumor entities. While a high tumor infiltration of these adaptive immune cells mostly predicts a favorable disease outcome, a high infiltration of tumor-associated macrophages predicts an unfavorable response. Pro-inflammatory events should dominate over anti-inflammatory ones in this scenario. This review focuses on how ionizing radiation modulates inflammatory events in benign inflammatory and in malign diseases. A special focus is set on the role of tumor infiltrating lymphocytes and macrophages as biomarkers to predict treatment response and anti-tumor immunity and on mechanisms implicated in the anti-inflammatory effects of low-dose radiation therapy.
EVALuna2:18301

Modulation of the peripheral immune system after low-dose radon spa therapy: Detailed longitudinal immune monitoring of patients within the RAD-ON01 study - Rühle, Paul-Friedrich; Wunderlich, Roland; Fournier, Claudia; Maier, Andreas; Klein, Gerhart; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (Autoimmunity, 2017)
The pain-relieving effects of low-dose radon therapies on patients suffering from chronic painful inflammatory diseases have been described for centuries. Even though it has been suggested that low doses of radiation may attenuate chronic inflammation, the underlying mechanisms remain elusive. Thus, the RAD-ON01 study was initiated to examine the effects of radon spa therapy and its low doses of alpha radiation on the human immune system. In addition to an evaluation of pain parameters, blood was drawn from 100 patients suffering from chronic painful degenerative musculoskeletal diseases before as well as 6, 12, 18, and 30 weeks after the start of therapy. We verified significant long-term pain reduction for the majority of patients which was accompanied by modulations of the peripheral immune cells. Detailed immune monitoring was performed using a multicolor flow cytometry-based whole blood assay. After therapy, the major immune cells were only marginally affected. Nevertheless, a small but long-lasting increase in T cells and monocytes was observed. Moreover, neutrophils, eosinophils and, in particular, dendritic cells were temporarily modulated after therapy. Regarding the immune cell subsets, cytotoxic T and NK cells, in particular, were altered. However, the most prominent effects were identified in a strong reduction of the activation marker CD69 on T, B, and NK cells. Simultaneously, the percentage of HLA-DR+T cells was elevated after therapy. The RAD-ON01 study showed for the first time a modulation of the peripheral immune cells following standard radon spa therapy. These modulations are in line with attenuation of inflammation.
EVALuna2:32908

Modulations in the Peripheral Immune System of Glioblastoma Patient Is Connected to Therapy and Tumor Progression-A Case Report from the IMMO-GLIO-01 Trial - Rühle, Paul-Friedrich; Goerig, Nicole; Wunderlich, Roland; Fietkau, Rainer; Gaipl, Udo; Strnad, Annedore; Frey, Benjamin (Frontiers in Neurology, 2017)
Immune responses are important for efficient tumor elimination, also in immune privileged organs such as the brain. Fostering antitumor immunity has therefore become an important challenge in cancer therapy. This cannot only be achieved by immunotherapies as already standard treatments such as radiotherapy and chemotherapy modify the immune system. Consequently, the understanding of how the tumor, the tumor microenvironment, and immune system are modulated by cancer therapy is required for prognosis, prediction, and therapy adaption. The prospective, explorative, and observational IMMO-GLIO-01 trial was initiated to examine the detailed immune status and its modulation of about 50 patients suffering from primary glioblastoma multiforme (GBM) or anaplastic astrocytoma during standard therapy. Prior to the study, a flow cytometry-based assay was established allowing the analysis of 34 immune cell subsets and their activation state. Here, we present the case of the first and longest accompanied patient, a 53-year-old woman suffering from GBM in the front left lobe. In context of tumor progression and therapy, we describe the modulation of the peripheral immune status over 17 months. Distinct immune modulations that were connected to therapy response or tumor progression were identified.Inter alia, a shift of CD4:CD8 ratio was observed that correlated with tumor progression. Twice we observed a unique composition of peripheral immune cells that correlated with tumor progression. Thus, following up these immune modulations in a closely-meshed manner is of high prognostic and predictive relevance for supporting personalized therapy and increasing therapy success.Clinical Trial registration: ClinicalTrials.gov, identifier NCT02022384 (registered retrospectively on 13th of December, 2013).
EVALuna2:32874

Mucosal tumor vaccination delivering endogenous tumor antigens protects against pulmonary breast cancer metastases - Oltmanns, Friederike; Vieira Antao, Ana Isabel; Irrgang, Pascal; Viherlehto, Vera; Jörg, Leticia; Schmidt, Anna; Wagner, Jannik; Rückert, Michael; Flohr, Ann-Sophie; Geppert, Carol-Immanuel; Frey, Benjamin; Bayer, Wibke; et al. (Journal for ImmunoTherapy of Cancer, 2024)
Background Generally, early-stage breast cancer has a good prognosis. However, if it spreads systemically, especially with pulmonary involvement, prospects worsen dramatically. Importantly, tumor-infiltrating T cells contribute to tumor control, particularly intratumoral T cells with a tissue-resident memory phenotype are associated with an improved clinical outcome. Methods Here, we use an adenoviral vector vaccine encoding endogenous tumor-associated antigens adjuvanted with interleukin-1β to induce tumor-specific tissue-resident memory T cells (TRM) in the lung for the prevention and treatment of pulmonary metastases in the murine 4T1 breast cancer model. Results The mucosal delivery of the vaccine was highly efficient in establishing tumor-specific TRM in the lung. Concomitantly, a single mucosal vaccination reduced the growth of pulmonary metastases and improved the survival in a prophylactic treatment. Vaccine-induced TRM contributed to these protective effects. In a therapeutic setting, the vaccination induced a pronounced T cell infiltration into metastases but resulted in only a minor restriction of the disease progression. However, in combination with stereotactic radiotherapy, the vaccine increased the survival time and rate of tumor-bearing mice. Conclusion In summary, our study demonstrates that mucosal vaccination is a promising strategy to harness the power of antitumor TRM and its potential combination with state-of-the-art treatments.
CRIS-Team Scopus Importer:2024-03-22

Myeloperoxidase Modulates Inflammation in Generalized Pustular Psoriasis and Additional Rare Pustular Skin Diseases - Haskamp, Stefan; Bruns, Heiko; Hahn, Madelaine; Hoffmann, Markus; Gregor, Anne; Löhr, Sabine; Hahn, Jonas; Ringer, Mark; Flamann, Cindy; Frey, Benjamin; Lesner, Adam; Thiel, Christian; et al. (American Journal of Human Genetics, 2020)
Generalized pustular psoriasis (GPP) is a severe multi-systemic inflammatory disease characterized by neutrophilic pustulosis and triggered by pro-inflammatory IL-36 cytokines in skin. While 19%–41% of affected individuals harbor bi-allelic mutations in IL36RN, the genetic cause is not known in most cases. To identify and characterize new pathways involved in the pathogenesis of GPP, we performed whole-exome sequencing in 31 individuals with GPP and demonstrated effects of mutations in MPO encoding the neutrophilic enzyme myeloperoxidase (MPO). We discovered eight MPO mutations resulting in MPO -deficiency in neutrophils and monocytes. MPO mutations, primarily those resulting in complete MPO deficiency, cumulatively associated with GPP (p = 1.85E−08; OR = 6.47). The number of mutant MPO alleles significantly differed between 82 affected individuals and >4,900 control subjects (p = 1.04E−09); this effect was stronger when including IL36RN mutations (1.48E−13) and correlated with a younger age of onset (p = 0.0018). The activity of four proteases, previously implicated as activating enzymes of IL-36 precursors, correlated with MPO deficiency. Phorbol-myristate-acetate-induced formation of neutrophil extracellular traps (NETs) was reduced in affected cells (p = 0.015), and phagocytosis assays in MPO-deficient mice and human cells revealed altered neutrophil function and impaired clearance of neutrophils by monocytes (efferocytosis) allowing prolonged neutrophil persistence in inflammatory skin. MPO mutations contribute significantly to GPP's pathogenesis. We implicate MPO as an inflammatory modulator in humans that regulates protease activity and NET formation and modifies efferocytosis. Our findings indicate possible implications for the application of MPO inhibitors in cardiovascular diseases. MPO and affected pathways represent attractive targets for inducing resolution of inflammation in neutrophil-mediated skin diseases.
CRIS-Team Scopus Importer:2020-09-11
Keywords: ACH; acrodermatitis continua suppurativa Hallopeau; activation of IL-36 precursors; acute generalized 4 exanthematous pustulosis; AGEP; efferocytosis; generalized pustular psoriasis; GPP; impaired NETosis; MPO deficiency; myeloperoxidase; oligogenic inheritance

Neutrophils seeking new neighbors: radiotherapy affects the cellular framework and the spatial organization in a murine breast cancer model - Reichardt, Clara; Munoz Becerra, Marco; Rius Rigau, Aleix Rius; Rückert, Michael; Fietkau, Rainer; Schett, Georg; Gaipl, Udo; Frey, Benjamin; Munoz Becerra, Luis (Cancer Immunology, Immunotherapy, 2024)
Neutrophils are known to contribute in many aspects of tumor progression and metastasis. The presence of neutrophils or neutrophil-derived mediators in the tumor microenvironment has been associated with poor prognosis in several types of solid tumors. However, the effects of classical cancer treatments such as radiation therapy on neutrophils are poorly understood. Furthermore, the cellular composition and distribution of immune cells in the tumor is of increasing interest in cancer research and new imaging technologies allow to perform more complex spatial analyses within tumor tissues. Therefore, we aim to offer novel insight into intra-tumoral formation of cellular neighborhoods and communities in murine breast cancer. To address this question, we performed image mass cytometry on tumors of the TS/A breast cancer tumor model, performed spatial neighborhood analyses of the tumor microenvironment and quantified neutrophil-extracellular trap degradation products in serum of the mice. We show that irradiation with 2 × 8 Gy significantly alters the cellular composition and spatial organization in the tumor, especially regarding neutrophils and other cells of the myeloid lineage. Locally applied radiotherapy further affects neutrophils in a systemic manner by decreasing the serum neutrophil extracellular trap concentrations which correlates positively with survival. In addition, the intercellular cohesion is maintained due to radiotherapy as shown by E-Cadherin expression. Radiotherapy, therefore, might affect the epithelial–mesenchymal plasticity in tumors and thus prevent metastasis. Our findings underscore the growing importance of the spatial organization of the tumor microenvironment, particularly with respect to radiotherapy, and provide insight into potential mechanisms by which radiotherapy affects epithelial–mesenchymal plasticity and tumor metastasis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cancer; Cellular neighborhood; Image mass cytometry; Neutrophil; Radiotherapy

Norm- and hypo-fractionated radiotherapy is capable of activating human dendritic cells - Kulzer, Lorenz; Rubner, Yvonne; Deloch, Lisa; Allgäuer, Andrea; Frey, Benjamin; Fietkau, Rainer; Dörrie, Jan; Schaft, Niels; Gaipl, Udo (Journal of Immunotoxicology, 2014)
Abstract Despite the transient immunosuppressive properties of local radiotherapy (RT), this classical treatment modality of solid tumors is capable of inducing immunostimulatory forms of tumor-cell death. The resulting 'immunotoxicity' in the tumor, but not in healthy tissues, may finally lead to immune-mediated destruction of the tumor. However, little is known about the best irradiation scheme in this setting. This study examines the immunological effects of differently irradiated human colorectal tumor cells on human monocyte-derived dendritic cells (DC). Human SW480 tumor cells were irradiated with a norm-fractionation scheme (5 × 2 Gy), a hypo-fractionated protocol (3 × 5 Gy), and with a high single irradiation dose (radiosurgery; 1 × 15 Gy). Subsequently, human immature DC (iDC) were co-incubated with supernatants (SN) of these differently treated tumor cells. Afterwards, DC were analyzed regarding the expression of maturation markers, the release of cytokines, and the potential to stimulate CD4(+) T-cells. The co-incubation of iDC with SN of tumor cells exposed to norm- or hypo-fractionated RT resulted in a significantly increased secretion of the immune activating cytokines IL-12p70, IL-8, IL-6, and TNF?, compared to iDC co-incubated with SN of tumor cells that received a high single irradiation dose or were not irradiated. In addition, DC-maturation markers CD80, CD83, and CD25 were also exclusively elevated after co-incubation with the SN of fractionated irradiated tumor cells. Furthermore, the SN of tumor cells that were irradiated with norm- or hypo-fractionated RT triggered iDC to stimulate CD4(+) T-cells not only in an allogenic, but also in an antigen-specific manner like mature DC. Collectively, these results demonstrate that norm- and hypo-fractionated RT induces a fast human colorectal tumor-cell death with immunogenic potential that can trigger DC maturation and activation in vitro. Such findings may contribute to the improvement of irradiation protocols for the most beneficial induction of anti-tumor immunity.
EVALuna2:18178

Normofractionated irradiation and not temozolomide modulates the immunogenic and oncogenic phenotype of human glioblastoma cell lines - Schatz, Julia; Ladinig, Alexandra; Fietkau, Rainer; Putz, Florian; Gaipl, Udo; Frey, Benjamin; Derer, Anja (Strahlentherapie und Onkologie, 2022)
Purpose Glioblastoma multiforme (GBM) is the most aggressive primary brain tumor, with an overall poor prognosis after diagnosis. Conventional treatment includes resection, chemotherapy with temozolomide (TMZ), and concomitant radiotherapy (RT). The recent success of immunotherapy approaches in other tumor entities, particularly with immune checkpoint inhibitors, could not be clinically transferred to GBM treatment so far. Therefore, preclinical analyses of the expression of both immune-suppressive and immune-stimulatory checkpoint molecules following treatment of human glioblastoma cells with RT and/or temozolomide is needed to design feasible radio(chemo)immunotherapy trials for GBM in the future. Methods Five human glioblastoma cell lines (H4, HROG-06, U118, U138, U251) were analyzed regarding their clonogenic survival and cell death forms after chemotherapy (CT) with TMZ and/or normofractionated RT (5 x 2 Gy) via multicolor flow cytometry. Further, the tumor cell surface expression of immune-activating (OX40L, CD137L, CD70, and ICOSL) and immune-suppressive (PD-L1, PD-L2, HVEM) checkpoint molecules and of an oncogenic molecule (EGFR) were measured via multicolor flow cytometry after CT and RT alone or after RCT. Results Normofractionated RT and not TMZ was the trigger of induction of predominantly necrosis in the glioblastoma cells. Notably, clonogenicity did not correlate with cell death induction by RT. The basal expression level of immune-suppressive PD-L1, PD-L2, and HVEM varied in the analyzed glioblastoma cells. RT, but not TMZ, resulted in a significant upregulation of PD-L1 and PD-L2 in all tumor cells investigated. Also, the expression of HVEM was increased after RT in most of the GBM cell lines. In contrast, normofractionated RT individually modulated expression of the stimulating immune checkpoint molecules CD70, CD137L, OX40L, and ICOSL1. The oncogenic factor EGFR was significantly increased by irradiation in all examined cell lines, albeit to a different extent. None of the investigated molecules were downregulated after the treatments. Conclusion Normofractionated radiotherapy modulates the immunogenic as well as the oncogenic phenotype of glioblastoma cells, partly individually. Therefore, not only PD-L1 and PD-L2, but also other immunogenic molecules expressed on the surface of glioblastoma cells could serve as targets for immune checkpoint blockade in combination with RT in the future.
CRIS-Team WoS Importer:2022-12-23

Novel technique for high-precision stereotactic irradiation of mouse brains - Hartmann, Josefin; Wölfelschneider, Jens; Stache, Christina; Buslei, R.; Derer, Anja; Schwarz, Martin; Bäuerle, Tobias; Fietkau, Rainer; Gaipl, Udo; Bert, Christoph; Hoelsken, A.; Frey, Benjamin (Strahlentherapie und Onkologie, 2016)
Small animal irradiation systems were developed for preclinical evaluation of tumor therapy closely resembling the clinical situation. Mostly only clinical LINACs are available, so protocols for small animal partial body irradiation using a conventional clinical system are essential. This study defines a protocol for conformal brain tumor irradiations in mice.CT and MRI images were used to demarcate the target volume and organs at risk. Three 6 MV photon beams were planned for a total dose of 10 fractions of 1.8 Gy. The mouse position in a dedicated applicator was verified by an X-ray patient positioning system before each irradiation. Dosimetric verifications (using ionization chambers and films) were performed. Irradiation-induced DNA damage was analyzed to verify the treatment effects on the cellular level.The defined treatment protocol and the applied fractionation scheme were feasible. The in-house developed applicator was suitable for individual positioning at submillimeter accuracy of anesthetized mice during irradiation, altogether performed in less than 10 min. All mice tolerated the treatment well. Measured dose values perfectly matched the nominal values from treatment planning. Cellular response was restricted to the target volume.Clinical LINAC-based irradiations of mice offer the potential to treat orthotopic tumors conformably. Especially with respect to lateral penumbra, dedicated small animal irradiation systems exceed the clinical LINAC solution.
EVALuna2:7317

Olanzapine combined with 5-hydroxytryptamine type 3 receptor antagonist (5-HT3 RA) plus dexamethasone for prevention and treatment of chemotherapy-induced nausea and vomiting in high and moderate emetogenic chemotherapy: a systematic review and meta-analysis of randomised controlled trials - Zhou, Jian Guo; Huang, Lang; Jin, Su Han; Xu, Cheng; Frey, Benjamin; Ma, Hu; Gaipl, Udo (ESMO Open, 2020)
We performed a pooled analysis to evaluate the efficacy and adverse events (AEs) of olanzapine combined with dexamethasone plus 5-hydroxytryptamine type 3 receptor antagonist (5-HT3 RA) compared with 5-HT3 RA plus dexamethasone for the prevention and treatment of chemotherapy-induced nausea and vomiting (CINV) in high and moderate emetogenic chemotherapy based on randomised controlled trials (RCTs). PubMed, EMBASE, Web of Science, the Cochrane Library, China Biomedical Literature database (CBM), WanFang Database, China National Knowledge Infrastructure (CNKI), and Chinese Science and Technology Periodical Database (VIP) (from their inception to April 2019) were searched to capture relevant articles. Relative risk with 95% confidence intervals for CINV and AEs were all extracted or calculated. Eleven studies with 1107 cancer patients were involved in this review. The pooled RR of delayed CINV (RR 0.50, 95% CI 0.38 to 0.66; p<0.01) were significantly decreased in the olanzapine group. The occurrence of insomnia was also statistically decreased, as was the rate of acute CINV (RR 0.60, 95% CI 0.48 to 0.75; p<0.01). However, only the percentages of CINV III and CINV IV were significantly decreased in the acute and delayed phases. Subgroup analysis demonstrated that the efficacy was not statistically significantly different between 5 mg and 10 mg olanzapine. Olanzapine significantly decreased the occurrence of CINV III and IV and insomnia in high and moderately emetogenic chemotherapy. Compared with 10 mg per day, 5 mg oral olanzapine may be more appropriate for patients with cancer.
CRIS-Team Scopus Importer:2020-03-06
Keywords: 5-HT3 RA; chemotherapy-induced nausea and Vomiting; dexamethasone; meta-analysis; olanzapine

Oligometastatic head and neck cancer: Which patients benefit from radical local treatment of all tumour sites? - Weissmann, Thomas; Höfler, Daniel; Hecht, Markus; Semrau, Sabine; Haderlein, Marlen; Filimonova, Irina; Frey, Benjamin; Bert, Christoph; Lettmaier, Sebastian; Mantsopoulos, Konstantinos; Iro, Heinrich; Fietkau, Rainer; et al. (Radiation Oncology, 2021)
Background: There is a large lack of evidence for optimal treatment in oligometastatic head and neck cancer and it is especially unclear which patients benefit from radical local treatment of all tumour sites. Methods: 40 patients with newly diagnosed oligometastatic head and neck cancer received radical local treatment of all tumour sites from 14.02.2008 to 24.08.2018. Primary endpoint was overall survival. Time to occurrence of new distant metastases and local control were evaluated as secondary endpoints as well as prognostic factors in univariate und multivariate Cox’s regression analysis. To investigate the impact of total tumour volume on survival, all tumour sites were segmented on baseline imaging. Results: Radical local treatment included radiotherapy in 90% of patients, surgery in 25% and radiofrequency ablation in 3%. Median overall survival from first diagnosis of oligometastatic disease was 23.0 months, 2-year survival was 48%, 3-year survival was 37%, 4-year survival was 24% and 5-year survival was 16%. Median time to occurrence of new distant metastases was 11.6 months with freedom from new metastases showing a tail pattern after 3 years of follow-up (22% at 3, 4- and 5-years post-treatment). In multivariate analysis, better ECOG status, absence of bone and brain metastases and lower total tumour volume were significantly associated with improved survival, whereas the number of metastases and involved organ sites was not. Conclusions: Radical local treatment in oligometastatic head and neck cancer shows promising outcomes and needs to be further pursued. Patients with good performance status, absence of brain and bone metastases and low total tumour volume were identified as optimal candidates for radical local treatment in oligometastatic head and neck cancer and should be considered for selection in future prospective trials.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Head and neck cancer; Local treatment; Oligometastatic disease; Radiotherapy; SBRT

One-tube multicolor flow cytometry assay (OTMA) for comprehensive immunophenotyping of peripheral blood - Donaubauer, Anna-Jasmina; Rühle, Paul-Friedrich; Becker, Ina; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Human Monoclonal Antibodies, 2019)
Recent improvements in the flow cytometry technology allow the determination of the general immune status through the development of multicolor immunofluorescence panels. The one-tube multicolor flow cytometry assay (OTMA) that is presented here identifies 20 different, clinically relevant immune cell subsets and three common activation markers. Thereby, a comprehensive immune status that covers all major immune cells is easily obtained. The assay is suitable for every common three lasers and 10 color flow cytometer and includes the application of 15 different antibodies. Furthermore, the assay requires only 100 μL of EDTA-treated whole-blood and less than 40 min for sample preparation. By being easily adaptable to individual requirements and by additionally determining absolute cell counts, the assay is well-suited for translational research in clinical trials.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Absolute cell count; Antibody; Gating strategy; Human whole-blood; Immune status; Immunophenotyping; Multicolor flow cytometry; One-tube measurement

One year survival of brain tumor patients is closely linked to symptomatic CMV-encephalopathy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, Florian; et al. (2017)
EVALuna2:32882

On PTV definition for glioblastoma based on fiber tracking of diffusion tensor imaging data - Witulla, Barbara; Goerig, Nicole; Putz, Florian; Frey, Benjamin; Engelhorn, Tobias; Dörfler, Arnd; Uder, Michael; Fietkau, Rainer; Bert, Christoph; Laun, Frederik Bernd (PLoS ONE, 2020)
Radiotherapy (RT) is commonly applied for the treatment of glioblastoma multiforme (GBM). Following the planning target volume (PTV) definition procedure standardized in guidelines, a 20% risk of missing non-local recurrences is present. Purpose of this study was to evaluate whether diffusion tensor imaging (DTI)-based fiber tracking may be beneficial for PTV definition taking into account the prediction of distant recurrences. 56 GBM patients were examined with magnetic resonance imaging (MRI) including DTI performed before RT after resection of the primary tumor. Follow-up MRIs were acquired in three month intervals. For the seven patients with a distant recurrence, fiber tracking was performed with three algorithms and it was evaluated whether connections existed from the primary tumor region to the distant recurrence. It depended strongly on the used tracking algorithm and the used tracking parameters whether a connection was observed. Most of the connections were weak and thus not usable for PTV definition. Only in one of the seven patients with a recurring tumor, a clear connection was present. It seems unlikely that DTI-based fiber tracking can be beneficial for predicting distant recurrences in the planning of PTVs for glioblastoma multiforme.
CRIS-Team Scopus Importer:2020-01-21

Orofacial clefts lead to increased pro-inflammatory cytokine levels on neonatal oral mucosa - Seidel, Corinna Lesley; Percivalle, Elena; Tschaftari, Marco; Weider, Matthias; Strobel, Karin; Willershausen, Ines; Unertl, Christoph; Schmetzer, Helga M.; Weber, Manuel; Schneider, Michael; Frey, Benjamin; Gaipl, Udo; et al. (Frontiers in Immunology, 2022)
Orofacial clefts (OFC) are frequent congenital malformations characterized by insufficient separation of oral and nasal cavities and require presurgical infant orthopedics and surgical interventions within the first year of life. Wound healing disorders and higher prevalence of gingivitis and plaque levels are well-known challenges in treatment of children with OFC. However, oral inflammatory mediators were not investigated after birth using non-invasive sampling methods so far. In order to investigate the impact of OFC on oral cytokine levels, we collected tongue smear samples from 15 neonates with OFC and 17 control neonates at two time points (T), T0 at first consultation after birth, and T1, 4 to 5 weeks later. The samples were analyzed using multiplex immunoassay. Overall, we found significantly increased cytokine levels (TNF, IL-1β/-2/-6/-8/-10) in tongue smear samples from neonates with OFC compared to controls, especially at T0. The increase was even more pronounced in neonates with a higher cleft severity. Further, we detected a significant positive correlation between cleft severity score and distinct pro-inflammatory mediators (GM-CSF, IL-1β, IL-6, IL-8) at T0. Further, we found that breast-milk (bottle) feeding was associated with lower levels of pro-inflammatory cytokines (IL-6/-8) in neonates with OFC compared to formula-fed neonates. Our study demonstrated that neonates with OFC, especially with high cleft severity, are characterized by markedly increased inflammatory mediators in tongue smear samples within the first weeks of life potentially presenting a risk for oral inflammatory diseases. Therefore, an inflammatory monitoring of neonates with (severe) OFC and the encouragement of mother to breast-milk (bottle) feed might be advisable after birth and/or prior to cleft surgery.
CRIS-Team Scopus Importer:2022-12-16
Keywords: cleft lip and palate; cytokines; mucosal homeostasis; mucosal immunity; neonates; oral; oral inflammation; orofacial clefts

Osteoimmunological Effects of Radon Therapy on Patients with chronic degenerative and/or inflammatory Diseases - Becker, I.; Donaubauer, Anna-Jasmina; Klein, G.; Cheremina, O.; Fournier, C.; Cucu, A.; Rapp, F.; Kraft, D.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Osteo-immunological impact of radon spa treatment: due to radon or spa alone? Results from the prospective, thermal bath placebo-controlled RAD-ON02 trial. - Eckert, Denise; Evic, Megi; Schang, Jasmin; Isbruch, Maike; Er, Melissa; Dörrschuck, Lea; Rapp, Felicitas; Donaubauer, Anna-Jasmina; Gaipl, Udo; Frey, Benjamin; Fournier, Claudia (Frontiers in Immunology, 2024)
Musculoskeletal disorders (MSDs) are associated with pain and lead to reduced mobility and quality of life for patients. Radon therapy is used as alternative or complementary to pharmaceutical treatments. According to previous reports, radon spa leads to analgesic and anti-inflammatory effects, but the cellular and molecular mechanisms are widely unknown. A previous study (RAD-ON01) revealed, that bone erosion markers like collagen fragments (C-terminal telopeptide, CTX) are reduced after radon spa treatment in serum of patients with degenerative MSDs. Within the scope of the prospective, placebo-controlled RAD-ON02 trial presented here, we analyzed the influence of radon and thermal spa treatment on osteoclastogenesis. From patient blood, we isolate monocytes, seeded them on bone slices and differentiated them in the presence of growth factors into mature osteoclasts (mOCs). Subsequent analysis showed a smaller fraction of mOCs after both treatments, which was even smaller after radon spa treatment. A significantly reduced resorbed area on bone slices reflects this result. Only after radon spa treatment, we detected in the serum of patients a significant decrease of receptor activator of NF-κB ligand (RANKL), which indicates reduced differentiation of OCs. However, other markers for bone resorption (CTX) and bone formation (OPG, OCN) were not altered after both treatments. Adipokines, such as visfatin and leptin that play a role in some MSD-types by affecting osteoclastogenesis, were not changed after both treatments. Further, also immune cells have an influence on osteoclastogenesis, by inhibiting and promoting terminal differentiation and activation of OCs, respectively. After radon treatment, the fraction of Treg cells was significantly increased, whereas Th17 cells were not altered. Overall, we observed that both treatments had an influence on osteoclastogenesis and bone resorption. Moreover, radon spa treatment affected the Treg cell population as well as the Th17/Treg ratio were affected, pointing toward a contribution of the immune system after radon spa. These data obtained from patients enrolled in the RAD-ON02 trial indicate that radon is not alone responsible for the effects on bone metabolism, even though they are more pronounced after radon compared to thermal spa treatment.
EVALuna2:557909

P22-2-jD Mit hydrostatischem Hochdruck generierte Ganzzell- Tumorvakzine erzeugen in Kombination mit Strahlentherapie ein immunogenes Tumor-Mikromilieu - Rückert, Michael; Seitz, Christoph; Deloch, Lisa; Weiss, Eva-Maria; Utz, S; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2019)

Pathologic response after induction chemo-immunotherapy with single or double immune checkpoint inhibition in locally advanced head and neck squamous cell carcinoma (HNSCC): Expansion cohorts of the CheckRad-CD8 trial. - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Klautke, Gunther; Illmer, Thomas; von der Grün, Jens; Laban, Simon; Hautmann, Matthias; Tamaskovics, Bálint; Hinke, Axel; Brunner, Thomas; Frey, Benjamin; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-04

Patterns of lymph node involvement in prostate cancer patients presenting for pelvic and paraaortic stereotactic radiotherapy of nodal metastases - Filimonova, Irina; Weissmann, T.; Mansoorian, S.; Bert, Christoph; Frey, Benjamin; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Peer review analysis in the field of radiation oncology: results from a web-based survey of the Young DEGRO working group - Käsmann, Lukas; Schröder, Annemarie; Frey, Benjamin; Fleischmann, Daniel F.; Gauer, Tobias; Ebert, Nadja; Hecht, Markus; Krug, David; Niyazi, Maximilian; Mäurer, Matthias (Strahlentherapie und Onkologie, 2020)
Purpose: To evaluate the reviewing behaviour in the German-speaking countries in order to provide recommendations to increase the attractiveness of reviewing activity in the field of radiation oncology. Methods: In November 2019, a survey was conducted by the Young DEGRO working group (jDEGRO) using the online platform “eSurveyCreator”. The questionnaire consisted of 29 items examining a broad range of factors that influence reviewing motivation and performance. Results: A total of 281 responses were received. Of these, 154 (55%) were completed and included in the evaluation. The most important factors for journal selection criteria and peer review performance in the field of radiation oncology are the scientific background of the manuscript (85%), reputation of the journal (59%) and a high impact factor (IF; 40%). Reasons for declining an invitation to review include the scientific background of the article (60%), assumed effort (55%) and a low IF (27%). A double-blind review process is preferred by 70% of respondents to a single-blind (16%) or an open review process (14%). If compensation was offered, 59% of participants would review articles more often. Only 12% of the participants have received compensation for their reviewing activities so far. As compensation for the effort of reviewing, 55% of the respondents would prefer free access to the journal’s articles, 45% a discount for their own manuscripts, 40% reduced congress fees and 39% compensation for expenses. Conclusion: The scientific content of the manuscript, reputation of the journal and a high IF determine the attractiveness for peer reviewing in the field of radiation oncology. The majority of participants prefer a double-blind peer review process and would conduct more reviews if compensation was available. Free access to journal articles, discounts for publication costs or congress fees, or an expense allowance were identified to increase attractiveness of the review process.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Impact factor; Peer review; Publication; Radiation oncology; Scientific publishing

Pradictive Character of Immunophenotyping in peripheral Blood in Patients treated with PD-1 Immunocheckpoint Inhibitors with and without Radiotherapy (Prospective Phase IV Study ST-ICI) - Hecht, Markus; Donaubauer, Anna-Jasmina; Harrer, A.; Rutzner, Sandra; Becker, I.; Lettmaier, S.; Haderlein, Marlen; Wolf, W.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (2018)
EVALuna2:36500

Predictive character of peripheral blood immunophenotype before and during treatment with PD-1 immune checkpoint inhibitors (interim analysis of the prospective phase IV ST-ICI trial) - Hecht, Markus; Harrer, A.; Rutzner, Sandra; Lettmaier, S.; Wolf, W.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2018)
EVALuna2:33777

Predictive Value of Multiparametric MRI for Response to Single-Cycle Induction Chemo-Immunotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Hellwig, Konstantin; Ellmann, Stephan; Eckstein, Markus; Wiesmüller, Marco; Rutzner, Sandra; Semrau, Sabine; Frey, Benjamin; Gaipl, Udo; Hartmann, Arndt; Iro, Heinrich; Fietkau, Rainer; Uder, Michael; et al. (Frontiers in Oncology, 2021)
Objectives
CRIS-Team WoS Importer:2021-11-19

Primary glioblastoma multiforme tumors and recurrence : Comparative analysis of the danger signals HMGB1, HSP70, and calreticulin - Muth, Carolin; Ruebner, Yvonne; Semrau, Sabine; Rühle, Paul-Friedrich; Frey, Benjamin; Strnad, Annedore; Buslei, Rolf; Fietkau, Rainer; Gaipl, Udo (Strahlentherapie und Onkologie, 2016)
Glioblastoma multiforme (GBM) is the most common and aggressive brain tumor. Despite improved multimodal therapies, the tumor recurs in most cases. Diverging patient survival suggests great tumor heterogeneity and different therapy responses. Danger signals such as high-mobility group box protein 1 (HMGB1), heat shock protein 70 (HSP70), and calreticulin (CRT) are biomarker candidates, due to their association with tumor progression versus induction of antitumor immune responses. Overexpression of these danger signals has been reported for various types of tumors; however, their role in GBM is still elusive. A direct comparison of their expression in the primary tumor versus the corresponding relapse is still lacking for most tumor entities.We therefore performed an expression analysis by immunohistochemistry of the danger signals HMGB1, HSP70, and CRT in primary tumors and the corresponding relapses of 9 patients with de novo GBM.HMGB1 was highly expressed in primary tumors with a significant reduction in the respective relapse. The extracellular HSP70 expression was significantly increased in the relapse compared to the primary tumor. CRT was generally highly expressed in the primary tumor, with a slight increase in the relapse.The combination of a decreased expression of HMGB1, an increased expression of extracellular HSP70, and an increased expression of CRT in the relapse seems to be beneficial for patient survival. HMGB1, extracellular HSP70, and CRT could be taken into concerted consideration as potential biomarkers for the prognosis of patients with GBM.
EVALuna2:7316

Primary results of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) with double checkpoint blockade and radiotherapy dependent on intratumoral CD8+T-cell infiltration. - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias G.; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Frey, Benjamin; et al. (ASCO 2021 Annual Meeting, 2021)
CRIS-Team WoS Importer:2021-11-26

Primary Results of the phase II CheckRad-CD8 Trial: First-Line Treatment of locally advanced Head and Neck Tumors with double Checkpoint Blockade and Radiotherapy dependent on intratumoral CD8+T-Cell Infiltration - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Klautke, G.; Laban, S.; Hautmann, M.; Brunner, T.; Tamaskovics, B.; Hinke, A.; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Priming of Anti-tumor Immune Mechanisms by Radiotherapy Is Augmented by Inhibition of Heat Shock Protein 90 - Ernst, Anne; Hennel, Roman; Krombach, Julia; Kapfhammer, Heidi; Brix, Nikko; Zuchtriegel, Gabriele; Uhl, Bernd; Reichel, Christoph A.; Frey, Benjamin; Gaipl, Udo; Winssinger, Nicolas; Shirasawa, Senji; et al. (Frontiers in Oncology, 2020)
Radiotherapy is an essential part of multi-modal cancer therapy. Nevertheless, for certain cancer entities such as colorectal cancer (CRC) the indications of radiotherapy are limited due to anatomical peculiarities and high radiosensitivity of the surrounding normal tissue. The development of molecularly targeted, combined modality approaches may help to overcome these limitations. Preferably, such strategies should not only enhance radiation-induced tumor cell killing and the abrogation of tumor cell clonogenicity, but should also support the stimulation of anti-tumor immune mechanisms – a phenomenon which moved into the center of interest of preclinical and clinical research in radiation oncology within the last decade. The present study focuses on inhibition of heat shock protein 90 (HSP90) whose combination with radiotherapy has previously been reported to exhibit convincing therapeutic synergism in different preclinical cancer models. By employing in vitro and in vivo analyses, we examined if this therapeutic synergism also applies to the priming of anti-tumor immune mechanisms in model systems of CRC. Our results indicate that the combination of HSP90 inhibitor treatment and ionizing irradiation induced apoptosis in colorectal cancer cells with accelerated transit into secondary necrosis in a hyperactive Kras-dependent manner. During secondary necrosis, dying cancer cells released different classes of damage-associated molecular patterns (DAMPs) that stimulated migration and recruitment of monocytic cells in vitro and in vivo. Additionally, these dying cancer cell-derived DAMPs enforced the differentiation of a monocyte-derived antigen presenting cell (APC) phenotype which potently triggered the priming of allogeneic T cell responses in vitro. In summary, HSP90 inhibition – apart from its radiosensitizing potential – obviously enables and supports the initial steps of anti-tumor immune priming upon radiotherapy and thus represents a promising partner for combined modality approaches. The therapeutic performance of such strategies requires further in-depth analyses, especially for but not only limited to CRC.
CRIS-Team Scopus Importer:2020-09-25
Keywords: anti-tumor immunity; cancer immunology; colorectal cancer; DAMPs; HSP90 inhibition; immune priming; radiotherapy; secondary necrosis

Principles of artificial intelligence in radiooncology - Huang, Yixing; Gomaa, Ahmed; Höfler, Daniel; Schubert, Philipp; Gaipl, Udo; Frey, Benjamin; Fietkau, Rainer; Bert, Christoph; Putz, Florian (Strahlentherapie und Onkologie, 2024)
Keywords: Artificial intelligence; Radiation Oncology; Deep learning

Prognostic Significance of immune-associated Side Effects under Radioimmunotherapy and Immunotherapy alone in Patients of the prospective ST-ICI Study - Schweizer, C.; Schubert, P.; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Becker, Ina; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Progress Patterns under Radioimmunotherapy - clinical Evaluation of the prospective STICI Study - Schubert, Philipp; Schweizer, Claudia; Roesch, Johannes; Haderlein, Marlen; Rutzner, Sandra; Semrau, Sabine; Donaubauer, Anna-Jasmina; Zhou, Jianguo; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Hecht, Markus (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prolonged high-pressure treatments in mammalian skeletal muscle result in loss of functional sodium channels and altered calcium channel kinetics. - Friedrich, Oliver; Kress, Kai; Hartmann, Martin; Frey, Benjamin; Sommer, Karl; Ludwig, Horst; Fink, Rainer (Cell Biochemistry and Biophysics, 2006)
Activation and inactivation of ion channels involve volume changes from conformational rearrangements of channel proteins. These volume changes are highly susceptible to changes in ambient pressure. Depending on the pressure level, channel function may be irreversibly altered by pressure. The corresponding structural changes persist through the post-decompression phase. High-pressure applications are a useful tool to evaluate the pressure dependence as well as pressure limits for reversibility of such alterations. Mammalian cells are only able to tolerate much lower pressures than microorganisms. Although some limits for pressure tolerance in mammalian cells have been evaluated, the mechanisms of pressure-induced alteration of membrane physiology, in particular of channel function, are unknown. To address this question, we recorded fast inward sodium (I(Na)) and slowly activating L-type calcium (I(Ca)) currents in single mammalian muscle fibers in the post-decompression phase after a prolonged 3-h, high-pressure treatment of up to 20 MPa. I(Na) and I(Ca) peak amplitudes were markedly reduced after pressure treatment at 20 MPa. This was not from a general breakdown of membrane integrity as judged from in situ high-pressure fluorescence microscopy. Membrane integrity was preserved even for pressures as high as 35 MPa at least for pressure applications of shorter durations. Therefore, the underlying mechanisms for the observed amplitude reductions have to be determined from the activation (time-to-peak [TTP]) and inactivation (tau(dec)) kinetics of I(Na) and I(Ca). No major changes in I(Na) kinetics, but marked increases, both in TTP and tau(dec) for I(Ca), were detected after 20 MPa. The apparent molecular volume changes (activation volumes) deltaV(double dagger) for the pressure-dependent irreversible alteration of channel gating approached zero for Na+ channels. For Ca2+ channels, deltaV(double dagger) was very large, with approx 2.5-fold greater values for channel activation than inactivation (approx 210 A3). We conclude, that in skeletal muscle, high pressure differentially and irreversibly affects the gating properties and the density of functional Na+ and Ca2+ channels. Based on these results, a model of high pressure-induced alterations to the channel conformation is proposed.

Prospective Assessment of the Inflammation Parameters in Blood Counts and Blood Serum as prognostic/predictive Parameters for Treatment with Immune Checkpoint-Inhibitors - Schweizer, Claudia; Haderlein, Marlen; Schubert, Philipp; Zhou, Jianguo; Semrau, Sabine; Rutzner, Sandra; Gostian, Antoniu-Oreste; Frey, Benjamin; Donaubauer, Anna-Jasmina; Eckstein, Markus; Becker, Ina; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Prospective development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with recurrent/metastatic cancer to immune checkpoint inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Eckstein, Markus; Sun, Roger; Ma, Hu; Schubert, Philipp; Schweizer, Claudia; Fietkau, Rainer; Deutsch, Eric; et al. (Journal for ImmunoTherapy of Cancer, 2021)
Background The predictive power of novel biological markers for treatment response to immune checkpoint inhibitors (ICI) is still not satisfactory for the majority of patients with cancer. One should identify valid predictive markers in the peripheral blood, as this is easily available before and during treatment. The current interim analysis of patients of the ST-ICI cohort therefore focuses on the development and validation of a liquid immune profile-based signature (LIPS) to predict response of patients with metastatic cancer to ICI targeting the programmed cell death protein 1 (PD-1)/programmed cell death-ligand 1 (PD-L1) axis. Methods A total of 104 patients were prospectively enrolled. 54 immune cell subsets were prospectively analyzed in patients' peripheral blood by multicolor flow cytometry before treatment with ICI (pre-ICI; n=89), and after the first application of ICI (n=65). Pre-ICI, patients were randomly allocated to a training (n=56) and a validation cohort (n=33). Univariate Cox proportional hazards regression analysis and least absolute shrinkage and selection operator Cox model were used to create a predictive immune signature, which was also checked after the first ICI, to consider the dynamics of changes in the immune status. Results Whole blood samples were provided by 89 patients pre-ICI and by 65 patients after the first ICI. We identified a LIPS which is based on five immune cell subtypes: CD14 high monocytes, CD8+/PD-1 + T cells, plasmacytoid dendritic cells, neutrophils, and CD3 + /CD56 + /CD16 + natural killer (NK)T cells. The signature achieved a high accuracy (C-index 0.74 vs 0.71) for predicting overall survival (OS) benefit in both the training and the validation cohort. In both cohorts, the low-risk group had significantly longer OS than the high-risk group (HR 0.26, 95% CI 0.12 to 0.56, p=0.00025; HR 0.30, 95% CI 0.10 to 0.91, p=0.024, respectively). Regarding the whole cohort, LIPS also predicted progression-free survival (PFS). The identified LIPS was not affected by clinicopathological features with the exception of brain metastases. NKT cells and neutrophils of the LIPS can be used as dynamic predictive biomarkers for OS and PFS after first administration of the ICI. Conclusion Our study identified a predictive LIPS for survival of patients with cancer treated with PD-1/PD-L1 ICI, which is based on immune cell subsets in the peripheral whole blood. Trial registration number NCT03453892.
CRIS-Team Scopus Importer:2021-03-05
Keywords: biomarkers; immunotherapy; programmed cell death 1 receptor; tumor; tumor biomarkers; tumor microenvironment

Prospective Evaluation of All-lesion Versus Single-lesion Radiotherapy in Combination With PD-1/PD-L1 Immune Checkpoint Inhibitors - Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Schweizer, Claudia; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Zhou, Jianguo; Gaipl, Udo; Fietkau, Rainer; et al. (Frontiers in Oncology, 2020)
Background: Local ablative treatments improve survival in patients with oligometastatic disease in addition to chemotherapy. The application of immune checkpoint inhibitors prolonged patients’ survival in different tumor entities. This raises the question if patients still benefit from intensified local treatments in combination with a more efficient systemic treatment with immune checkpoint inhibitors. Methods: The prospective non-interventional ST-ICI trial investigates treatment with PD-1/PD-L1 (Programmed cell death protein 1/Programmed cell death 1 ligand 1) immune checkpoint inhibitors and radiotherapy in different tumor entities. Patients who started radiotherapy and immunotherapy concomitantly were included in this interim analysis. In this cohort patients with all-lesion radiotherapy (all tumor lesions irradiated, al-RT) were compared to patients with radiotherapy to only a single of their tumor lesions (single-lesion radiotherapy, sl-RT). Endpoints of the interim analysis were progression-free survival (PFS), overall survival (OS) and time to progression (TTP). Results: A total of 104 patients were registered between April 2017 and August 2019. Fifty patients started immune checkpoint inhibitor treatment and radiotherapy concomitantly and were included. Most frequent tumor entities were non-small cell lung cancer (62%) followed by head and neck squamous cell cancer (26%). Most frequent location of radiotherapy was lung (34%) and central nervous system (20%). Median duration of follow-up was 8.6 months beginning with first administration of the immune-checkpoint-inhibitor. Median PFS was 9.2 months (95% CI, 5.8 – 12.6) in the al-RT group and 3.0 months (95% CI, 2.5 – 3.5) in the sl-RT group (p<0.001). Median OS was 11.6 months (95% CI, 8.1 - 15.1) in the al-RT group and 4.2 months (95% CI, 3.0 - 5.4) in the sl-RT group (p=0.007). Median TTP was not reached in the al-RT group compared to 4.6 months (95% CI, 1.1–8.0) in the sl-RT group (p=0.028). Univariate Cox regression analyses computed tumor entity, histology, central nervous system metastases, immunotherapy drug and al-RT as predictors of OS (with an effect p-value of ≤ 0.1). In the multivariable analysis only tumor entity and al-RT remained prognostic factors for OS. Conclusion: Patients with PD-1/PD-L1 immune checkpoint inhibitor therapy benefit from local radiotherapy to all known lesions compared to single-lesion radiotherapy regarding PFS and OS.
CRIS-Team Scopus Importer:2020-11-20
Keywords: all-lesion; immune checkpoint inhibitors; immunotherapy; oligometastatic; radiotherapy; single-lesion

Prospective Evaluation of CD45RA+/CCR7- Effector Memory T (TEMRA) Cell Subsets in Patients with Primary and Secondary Brain Tumors during Radiotherapy of the Brain within the Scope of the Prospective Glio-CMV-01 Clinical Trial - Scheer, Ilka; Becker, Ina; Schmitter, Charlotte; Semrau, Sabine; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Donaubauer, Anna-Jasmina (Cells, 2023)
Radiotherapy (RT) of the brain is a common treatment for patients with high-grade gliomas and brain metastases. It has previously been shown that reactivation of cytomegalovirus (CMV) frequently occurs during RT of the brain. This causes neurological decline, demands antiviral treatment, and is associated with a worse prognosis. CMV-specific T cells are characterized by a differentiated effector memory phenotype and CD45RA+ CCR7- effector memory T (TEMRA) cells were shown to be enriched in CMV seropositive individuals. In this study, we investigated the distribution of TEMRA cells and their subsets in the peripheral blood of healthy donors and, for the first time, prospectively within the scope of the prospective Glio-CMV-01 clinical trial of patients with high-grade glioma and brain metastases during radiation therapy as a potential predictive marker. First, we developed a multicolor flow cytometry-based assay to monitor the frequency and distribution of TEMRA cells in a longitudinal manner. The CMV serostatus and age were considered as influencing factors. We revealed that patients who had a reactivation of CMV have significantly higher amounts of CD8+ TEMRA cells. Further, the distribution of the subsets of TEMRA cells based on the expression of CD27, CD28, and CD57 is highly dependent on the CMV serostatus. We conclude that the percentage of CD8+ TEMRA cells out of all CD8+ T cells has the potential to serve as a biomarker for predicting the risk of CMV reactivation during RT of the brain. Furthermore, this study highlights the importance of taking the CMV serostatus into account when analyzing TEMRA cells and their subsets.
CRIS-Team Scopus Importer:2023-03-17
Keywords: brain metastases; cytomegalovirus (CMV); glioblastoma; infection; radiotherapy; T

Prospective evaluation of the prognostic value of immune-related adverse events in patients with non-melanoma solid tumour treated with PD-1/PD-L1 inhibitors alone and in combination with radiotherapy - Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Haderlein, Marlen; Lettmaier, Sebastian; Semrau, Sabine; Gostian, Antoniu Oreste; Frey, Benjamin; Gaipl, Udo; Zhou, Jianguo; Fietkau, Rainer; et al. (European Journal of Cancer, 2020)
Background: Prospective data about the prognostic value of immune-related adverse events (irAEs) in non-melanoma solid tumours are rare. The prognostic value of irAEs in patients treated with combined radiotherapy and immunotherapy is currently unknown. Patients and methods: The prospective non-interventional ST-ICI trial investigates treatment response of tumour patients to anti–programmed cell death-ligand 1 (PD-L1) immune checkpoint inhibitors alone and in combination with radiotherapy and possible predictive markers. Patients undergoing immunotherapy or immunoradiotherapy were surveyed for irAEs. Results: A total of 104 patients were included of whom 29 patients (28%) developed irAEs. Additional radiotherapy was performed in 50 patients (48%). Main tumour entities within the entire cohort were non–small cell lung cancer (NSCLC) (44%) and head and neck squamous cell carcinoma (42%). The rate of irAEs did not differ in patients with and without radiotherapy (p = 0.668). Patients who developed irAEs had longer overall survival (OS) (median: 22.8 months versus 9.0 months without irAEs, p = 0.001) and progression-free survival (PFS) (median: 7.8 months versus 3.2 months without irAEs, p = 0.002). In the subgroup with combined radiotherapy, patients with irAEs also had longer OS (median: 22.8 months versus 7.1 months without irAEs, p = 0.005) and PFS (median: 8.8 months versus 3.0 months without irAEs, p = 0.005). On multivariate analysis only PD-L1 on tumour cells (p = 0.049) and irAEs (p = 0.001) remained independent predictors of OS. Conclusion: The development of irAEs represents a favourable prognostic parameter in patients undergoing immunotherapy and immunoradiotherapy for solid tumours.
CRIS-Team Scopus Importer:2020-10-16
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Non-melanoma solid tumours; Prognostic parameters; Radiotherapy

Questionnaire-based detection of immune-related adverse events in cancer patients treated with PD-1/PD-L1 immune checkpoint inhibitors - Griewing, Luisa Maria; Schweizer, Claudia; Schubert, Philipp; Rutzner, Sandra; Eckstein, Markus; Frey, Benjamin; Haderlein, Marlen; Weissmann, Thomas; Semrau, Sabine; Gostian, Antoniu Oreste; Müller, Sarina Katrin; Traxdorf, Maximilian; et al. (BMC Cancer, 2021)
Background: Immune checkpoint inhibitors (ICI) have become standard treatment in different tumor entities. However, safe treatment with ICI targeting the PD-1/PD-L1 axis requires early detection of immune-related adverse events (irAE). There exist different questionnaires of drug manufacturers for the detection of irAE that have not been validated so far. Methods: The prospective non-interventional ST-ICI trial studied treatment with PD-1/PD-L1 ICI alone or combined with radiotherapy. In the current analysis, the detection rate of self-reported irAE with a patient questionnaire containing 41 different questions was compared to clinician-reported irAE. Results: Between April 2017 and August 2019, a total of 104 patients were prospectively enrolled. NSCLC (44%) and HNSCC (42%) were the most frequent tumor entities. A total of 784 questionnaires were collected. A total of 29 irAE were reported by clinicians. The most frequent irAE was hypothyroidism (9%), followed by skin reactions (5%), hepatitis (4%), diarrhea (3%), and pneumonitis (3%). Questions that became significantly more often positive at time points of clinician-reported irAE were “weight change”, “difficulty to grip things”, “bloody or mucous stool” and “insomnia”. Self-reported organ-specific questions detected at least 50% of clinician-reported irAE of gastrointestinal, lung, endocrine, and skin irAE. It was not possible to detect hepatic irAE with the questionnaire. Conclusion: Questionnaires can help to detect gastrointestinal, lung, endocrine, or skin irAE, but not hepatic irAE. Questions on “weight change” and “insomnia” may help to increase the detection rate of irAE, besides organ-specific questions. These results are a valuable contribution to the future development of a specific and practicable questionnaire for early self-reported detection of irAE during ICI therapy in cancer patients. Trial registration: ClinicalTrials.gov, NCT03453892. Registered on 05 March 2018.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Immune checkpoint inhibitors; Immune-related adverse events; Patient-reported irAE; PD-1; PD-L1; Questionnaire; Side effects; Solid tumors; Toxicity

Radiation Immunotherapy has different effects on the immunological Composition of the Tumor Microenvironment in primary and abscopic Murine Tumors - Rueckert, M.; Deloch, Lisa; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Radio(chemo)therapy does differently impact on PD-L1 and PD-L2 expression in human melanoma cell lines - Derer, Anja; Riegel, D.; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (2018)
EVALuna2:36496

Radio-Immunotherapy-Induced Immunogenic Cancer Cells as Basis for Induction of Systemic Anti-Tumor Immune Responses - Pre-Clinical Evidence and Ongoing Clinical Applications - Derer, Anja; Deloch, Lisa; Rubner, Yvonne; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (Frontiers in Immunology, 2015)
Radiotherapy (RT) primarily aims to locally destroy the tumor via the induction of DNA damage in the tumor cells. However, the so-called abscopal, namely systemic and immune-mediated, effects of RT move over more and more in the focus of scientists and clinicians since combinations of local irradiation with immune therapy have been demonstrated to induce anti-tumor immunity. We here summarize changes of the phenotype and microenvironment of tumor cells after exposure to irradiation, chemotherapeutic agents, and immune modulating agents rendering the tumor more immunogenic. The impact of therapy-modified tumor cells and damage-associated molecular patterns on local and systemic control of the primary tumor, recurrent tumors, and metastases will be outlined. Finally, clinical studies affirming the bench-side findings of interactions and synergies of radiation therapy and immunotherapy will be discussed. Focus is set on combination of radio(chemo)therapy (RCT) with immune checkpoint inhibitors, growth factor inhibitors, and chimeric antigen receptor T-cell therapy. Well-deliberated combination of RCT with selected immune therapies and growth factor inhibitors bear the great potential to further improve anti-cancer therapie
EVALuna2:18276

Radio-immunotherapy: the focused beam expands - Frey, Benjamin; Gaipl, Udo (Lancet Oncology, 2015)
EVALuna2:18299

Radiomics for selection of patients treated with immuno-radiotherapy: pooled analysis from 6 studies - Sun, R.; Sundahl, N.; Hecht, Markus; Putz, Florian; Lancia, A.; Milic, M.; Carre, A.; Lerousseau, M.; Theo, E.; Battistella, E.; Andres, E. Alvarez; Louvel, G.; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Radiomics to predict outcomes and abscopal response of patients with cancer treated with immunotherapy combined with radiotherapy using a validated signature of CD8 cells - Sun, Roger; Sundahl, Nora; Hecht, Markus; Putz, Florian; Lancia, Andrea; Rouyar, Angela; Milic, Marina; Carré, Alexandre; Battistella, Enzo; Alvarez Andres, Emilie; Niyoteka, Stéphane; Romano, Edouard; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: Combining radiotherapy (RT) with immuno-oncology (IO) therapy (IORT) may enhance IO-induced antitumor response. Quantitative imaging biomarkers can be used to provide prognosis, predict tumor response in a non-invasive fashion and improve patient selection for IORT. A biologically inspired CD8 T-cells-associated radiomics signature has been developed on previous cohorts. We evaluated here whether this CD8 radiomic signature is associated with lesion response, whether it may help to assess disease spatial heterogeneity for predicting outcomes of patients treated with IORT. We also evaluated differences between irradiated and non-irradiated lesions. METHODS: Clinical data from patients with advanced solid tumors in six independent clinical studies of IORT were investigated. Immunotherapy consisted of 4 different drugs (antiprogrammed death-ligand 1 or anticytotoxic T-lymphocyte-associated protein 4 in monotherapy). Most patients received stereotactic RT to one lesion. Irradiated and non-irradiated lesions were delineated from baseline and the first evaluation CT scans. Radiomic features were extracted from contrast-enhanced CT images and the CD8 radiomics signature was applied. A responding lesion was defined by a decrease in lesion size of at least 30%. Dispersion metrices of the radiomics signature were estimated to evaluate the impact of tumor heterogeneity in patient's response. RESULTS: A total of 94 patients involving multiple lesions (100 irradiated and 189 non-irradiated lesions) were considered for a statistical interpretation. Lesions with high CD8 radiomics score at baseline were associated with significantly higher tumor response (area under the receiving operating characteristic curve (AUC)=0.63, p=0.0020). Entropy of the radiomics scores distribution on all lesions was shown to be associated with progression-free survival (HR=1.67, p=0.040), out-of-field abscopal response (AUC=0.70, p=0.014) and overall survival (HR=2.08, p=0.023), which remained significant in a multivariate analysis including clinical and biological variables. CONCLUSIONS: These results enhance the predictive value of the biologically inspired CD8 radiomics score and suggests that tumor heterogeneity should be systematically considered in patients treated with IORT. This CD8 radiomics signature may help select patients who are most likely to benefit from IORT.
CRIS-Team Scopus Importer:2020-11-27
Keywords: radioimmunotherapy; translational medical research; tumor biomarkers; tumor microenvironment

Radiotherapy combined with docetaxel alters the immune phenotype of HNSCC cells and results in increased surface expression of CD137 and release of HMGB1 of specifically HPV-positive tumor cells - Grottker, Fridolin; Gehre, Simon; Reichardt, Clara; Sengedorj, Azzaya; Jost, Tina; Rieckmann, Thorsten; Hecht, Markus; Gostian, Antoniu-Oreste; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo; Rückert, Michael (Neoplasia, 2023)
Purpose: Human papilloma virus (HPV) positive head and neck squamous cell carcinoma (HNSCC) tumors respond significantly better to anticancer treatments. It is assumed to be due to a better response to radiotherapy (RT), and presumably to an increased immunogenicity. However, little is known how the immune phenotype of HNSCC tumor cells is modulated by standard treatment, namely by radiochemotherapy (RCT). Methods: Therefore, we aimed to examine the impact of the HPV status on the immune phenotype of HNSCC cell lines following RCT with 5 × 3Gy or 1 × 19.3Gy and/or docetaxel, by analyzing cell death, release of damage-associated molecular patterns (DAMPs), surface expression of immune checkpoint molecules (ICMs) and the impact on activation of human monocyte-derived dendritic cells (hmDCs). Results: Cell death induction and Hsp70 release following RCT was independent of the HPV status, and RCT significantly increased the expression of the immune suppressive ICMs PD-L1, PD-L2 and HVEM. An immune stimulatory ICM, CD137, was significantly increased following RCT only on HPV-positive cell lines, as well as the release of HMGB1. Although the treatment increased cell death and modulated ICM expression in HNSCC, the hmDCs were not activated after co-incubation with treated tumor cells. Conclusion: Our data with the HPV-dependent release of HMGB1 and increased expression of CD137 following RCT provide a hint for increased immunogenicity underlining the better prognosis for HPV positive tumors following RCT.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Anti-tumor immunity; Dendritic cells; Docetaxel; Head and neck squamous cell carcinoma; HMGB1; HPV status; Immune checkpoint molecules; Radiotherapy

Radiotherapy for benign achillodynia. Long-term results of the Erlangen Dose Optimization Trial - Ott, Oliver J.; Jeremias, Carolin; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Fietkau, Rainer (Strahlentherapie und Onkologie, 2015)
The aim of this study was to evaluate the long-term efficacy of two dose-fractionation schedules for radiotherapy of achillodynia.Between February 2006 and February 2010, 112 evaluable patients were recruited for this prospective trial. All patients received orthovoltage radiotherapy. One course consisted of 6 fractions/3 weeks. In the case of insufficient remission of pain after 6 weeks, a second series was performed. Patients were randomly assigned to receive either single doses of 0.5 or 1.0 Gy. The endpoint was pain reduction. Pain was measured before, right after (early response), 6 weeks after (delayed response), and approximately 2 years after radiotherapy (long-term response) with a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).The median follow-up was 24 months (range, 11-56). The overall early, delayed, and long-term response rates for all patients were 84 %, 88 %, and 95 %, respectively. The mean VAS values before treatment for early, delayed, and long-term responses for the 0.5-Gy and 1.0-Gy groups were 55.7 ± 21.0 and 58.2 ± 23.5 (p = 0.53), 38.0 ± 23.2 and 30.4 ± 22.6 (p = 0.08), 35.5 ± 25.9 and 30.9 ± 25.4 (p = 0.52), and 11.2 ± 16.4 and 15.3 ± 18.9 (p = 0.16), respectively. The mean CPS values before treatment for early, delayed, and long-term responses were 8.2 ± 3.0 and 8.9 ± 3.3 (p = 0.24), 5.6 ± 3.1 and 5.4 ± 3.3 (p = 0.76), 4.4 ± 2.6 and 5.3 ± 3.8 (p = 0.58), and 2.2 ± 2.9 and 2.8 ± 3.3 (p = 0.51), respectively. No significant differences in long-term response quality between the two arms was found (p = 0.73).Radiotherapy is a very effective treatment for the management of benign achillodynia. For radiation protection, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18279

Radiotherapy for benign calcaneodynia: long-term results of the Erlangen Dose Optimization (EDO) trial - Ott, Oliver J.; Jeremias, Carolin; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
The goal of this work was to evaluate the long-term efficacy of two dose-fractionation schedules for radiotherapy of calcaneodynia.Between February 2006 and February 2010, 457 evaluable patients were recruited for this prospective trial. All patients received orthovoltage radiotherapy. One course consisted of 6 fractions/3 weeks. In case of insufficient remission of pain after 6 weeks a second series was performed. Patients were randomly assigned to receive either single doses of 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before, right after (early response), 6 weeks (delayed response), and approximately 2.5 years after radiotherapy (long-term response) with a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).The median follow-up was 32 months (range 9-57 months). The overall early, delayed, and long-term response rates for all patients were 87, 88, and 95%. The mean VAS values before treatment, for early, delayed, and long-term response for the 0.5 and 1.0 Gy groups were 65.5 ± 22.1 and 64.0 ± 20.5 (p = 0.19), 34.8 ± 24.7 and 39.0 ± 26.3 (p = 0.12), 25.1 ± 26.8 and 28.9 ± 26.8 (p = 0.16), and 16.3 ± 24.3 and 14.1 ± 19.7 (p = 0.68). The mean CPS values before treatment, for early, delayed, and log-term response were 10.1 ± 2.7 and 10.0 ± 3.0 (p = 0.78), 5.6 ± 3.7 and 6.0 ± 3.9 (p = 0.34), 4.0 ± 4.1 and 4.3 ± 3.6 (p = 0.26), and 2.1 ± 3.3 and 2.3 ± 3.2 (p = 0.34), respectively. No significant differences in long-term response quality between the two arms were found (p = 0.50).Radiotherapy is a very effective treatment for the management of benign calcaneodynia. For radiation protection reasons, the dose for a RT series should not exceed 3.0 Gy.
EVALuna2:18187

Radiotherapy-induced changes in the systemic immune and inflammation parameters of head and neck cancer patients - Balazs, Katalin; Kis, Eniko; Badie, Christophe; Bogdandi, Eniko Noemi; Candeias, Serge; Garcia, Lourdes Cruz; Dominczyk, Iwona; Frey, Benjamin; Gaipl, Udo; Juranyi, Zsolt; Kocsis, Zsuzsa S.; Rutten, Eric Andreas; et al. (Cancers, 2019)
Though radiotherapy is a local therapy, it has systemic effects mainly influencing immune and inflammation processes. This has important consequences in the long-term prognosis and therapy individualization. Our objective was to investigate immune and inflammation-related changes in the peripheral blood of head and neck cancer patients treated with radiotherapy. Peripheral blood cells, plasma and blood cell-derived RNA were isolated from 23 patients before and at two time points after radiotherapy and cellular immune parameters, plasma protein changes and gene expression alterations were studied. Increased regulatory T cells and increased CTLA4 and PD-1 expression on CD4 cells indicated an immune suppression induced by the malignant condition, which was accentuated by radiotherapy. Circulating dendritic cells were strongly elevated before treatment and were not affected by radiotherapy. Decreased endoglin levels in the plasma of patients before treatment were further decreased by radiotherapy. Expression of the FXDR, SESN1, GADD45, DDB2 and MDM2 radiation-response genes were altered in the peripheral blood cells of patients after radiotherapy. All changes were long-lasting, detectable one month after radiotherapy. In conclusion we demonstrated radiotherapy-induced changes in systemic immune parameters of head and neck cancer patients and proposed markers suitable for patient stratification worth investigating in larger patient cohorts.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Dendritic cell; Gene expression; Head and neck cancer; Immune phenotyping; Natural killer cell; PBMC; Plasma proteins; Radiotherapy; Regulatory T cell

RAD-ON01 study: modulation of the peripheral immune system following a sequential radon spa therapy - Rühle, Paul-Friedrich; Kullmann, M.; Frey, Benjamin; Klein, G.; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Deloch, Lisa (2017)
EVALuna2:32893

Radon affects Immune Cells ex vivo as well as in vivo in an Animal Model of experimental Arthritis - Deloch, Lisa; Rückert, Michael; Maier, A.; Hinrichs, A.; Flohr, Ann-Sophie; Eckert, D.; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Fournier, C.; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Radon exposure—therapeutic effect and cancer risk - Maier, Andreas; Wiedemann, Julia; Rapp, Felicitas; Papenfuß, Franziska; Rödel, Franz; Hehlgans, Stephanie; Gaipl, Udo; Kraft, Gerhard; Fournier, Claudia; Frey, Benjamin (International Journal of Molecular Sciences, 2021)
Largely unnoticed, all life on earth is constantly exposed to low levels of ionizing radia-tion. Radon, an imperceptible natural occurring radioactive noble gas, contributes as the largest sin-gle fraction to radiation exposure from natural sources. For that reason, radon represents a major issue for radiation protection. Nevertheless, radon is also applied for the therapy of inflammatory and degenerative diseases in galleries and spas to many thousand patients a year. In either case, chronic environmental exposure or therapy, the effect of radon on the organism exposed is still under investigation at all levels of interaction. This includes the physical stage of diffusion and energy deposition by radioactive decay of radon and its progeny and the biological stage of initiating and propagating a physiologic response or inducing cancer after chronic exposure. The purpose of this manuscript is to comprehensively review the current knowledge of radon and its progeny on physical background, associated cancer risk and potential therapeutic effects.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Anti-inflammatory effects; Changes immune activation; Clinical studies; Low doses; Osteoimmunological changes; Radon therapy; α-particles

Radon Improves Clinical Response in an Animal Model of Rheumatoid Arthritis Accompanied by Increased Numbers of Peripheral Blood B Cells and Interleukin-5 Concentration - Deloch, Lisa; Hehlgans, Stephanie; Rückert, Michael; Maier, Andreas; Hinrichs, Annika; Flohr, Ann-Sophie; Eckert, Denise; Weissmann, Thomas; Seeling, Michaela; Nimmerjahn, Falk; Fietkau, Rainer; Rödel, Franz; et al. (Cells, 2022)
Radon treatment is used as an established therapy option in chronic painful inflammatory diseases. While analgesic effects are well described, little is known about the underlying molecular effects. Among the suspected mechanisms are modulations of the anti-oxidative and the immune system. Therefore, we aimed for the first time to examine the beneficial effects of radon exposure on clinical outcome as well as the underlying mechanisms by utilizing a holistic approach in a controlled environment of a radon chamber with an animal model: K/BxN serum-induced arthritic mice as well as isolated cells were exposed to sham or radon irradiation. The effects on the anti-oxidative and the immune system were analyzed by flow-cytometry, qPCR or ELISA. We found a significantly improved clinical disease progression score in the mice, alongside significant increase of peripheral blood B cells and IL-5. No significant alterations were visible in the anti-oxidative system or regarding cell death. We conclude that neither cell death nor anti-oxidative systems are responsible for the beneficial effects of radon exposure in our preclinical model. Rather, radon slightly affects the immune system. However, more research is still needed in order to fully understand radon-mediated effects and to carry out reasonable risk-benefit considerations.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Anti-oxidative system; B cells; Immune system; Inflammation; Macrophages; Monocytes; Radon therapy; Rheumatoid arthritis; Serum transfer arthritis; T cells

Rare frameshift mutation in SERPINA3 contributes to generalized pustular psoriasis - Hüffmeier, Ulrike; Sticht, Heinrich; Wenzel, J.; Wilsmann-Theis, D.; Wolff, K.; Löhr, Sabine; Frey, Benjamin; Hahn, M.; Ekici, Arif Bülent; Uebe, S.; Thiel, Christian; Wiesmann da Silva Reis, André; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

Rare Loss-of-Function Mutation in SERPINA3 in Generalized Pustular Psoriasis - Frey, Silke; Sticht, Heinrich; Wilsmann-Theis, Dagmar; Gerschütz, Anne; Wolf, Katharina; Löhr, Sabine; Haskamp, Stefan; Frey, Benjamin; Hahn, Madelaine; Ekici, Arif Bülent; Uebe, Steffen; Thiel, Christian; et al. (Journal of Investigative Dermatology, 2020)
CRIS-Team Scopus Importer:2020-03-06

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Reduction of elective radiotherapy treatment volume in definitive treatment of locally advanced head and neck cancer—comparison of a prospective trial with a revised simulated contouring approach - Weissmann, Thomas; Speer, Stefan; Putz, Florian; Lettmaier, Sebastian; Schubert, Philipp; Shariff, Maya; Semrau, Sabine; Gostian, Antoniu-Oreste; Traxdorf, Maximilian; Müller, Sarina Katrin; Eckstein, Markus; Hautmann, Matthias; et al. (Journal of Clinical Medicine, 2021)
Definitive radiochemotherapy of locally advanced head and neck squamous cell cancer (HNSCC) achieves high locoregional tumor control rates; but is frequently associated with long-term toxicity. A future direction could be a de-escalation strategy focusing on treated volume rather than radiotherapy dose. This analysis evaluates radiotherapy dose and volume parameters of patients treated with a standard contouring approach in a clinical trial context compared with a revised volume-reduced contouring approach. In this case, 30 consecutive patients from the CheckRad-CD8 trial treated at a single study center were included in this analysis. Treatment toxicity and quality of life were assessed at the end of radiotherapy. Standard treatment plans (ST) following state of the art contouring guidelines that were used for patient treatment and volume reduced treatment plans (VRT) according to a revised simulated approach were calculated for each patient. Planning target volumes (PTV) and mean doses to 38 organs-at-risk structures were compared. At the end of radiotherapy patients reported high rates of mucositis; dysphagia and xerostomia. In addition; patient reported quality of life as assessed by the EORTC QLQ-HN35 questionnaire deteriorated. Comparing the two contouring approaches; the elective PTV_56 Gy and the high risk PTV_63 Gy (shrinking field) were significantly smaller in the VRT group. Significant reduction of mean dose to structures of the oral cavity; the larynx as well as part of the swallowing muscles and the submandibular glands was achieved in the simulated VRT-plan. Treatment de-intensification by reduction of the irradiated volume could potentially reduce treatment volume and mean doses to organs at risk. The proposed contouring approach should be studied further in the context of a clinical trial.
CRIS-Team Scopus Importer:2021-10-22
Keywords: De-intensification; Definitive treatment; Head neck cancer; Radiotherapy; Salivary glands; Swallowing function; Volume reduc-tion

Regulatory T cells protect from local and systemic bone destruction in arthritis. - Zaiss, Mario; Frey, Benjamin; Heß, Andreas; Zwerina, Jochen; Luther, Julia; Nimmerjahn, Falk; Engelke, Klaus; Kollias, George; Huenig, Thomas; Schett, Georg; David, Jean-Pierre (Journal of Immunology, 2010)
We previously demonstrated the suppressive effects of regulatory T cells (Treg cells) on osteoclast differentiation in vitro. In this article, we show that blood markers of bone resorption inversely correlate with the amount of circulating Treg cells in healthy controls and rheumatoid arthritis patients, further suggesting that Treg cells may control bone destruction in vivo. Indeed, bone marrow from Foxp3-transgenic (Foxp3tg) mice fully protected human TNF transgenic (hTNFtg) mice from TNF-alpha-induced bone destruction, whereas Foxp3-deficient bone marrow enhanced local and systemic bone loss. The same protective effect was also obtained by treating hTNFtg mice with the CD28 superagonist mAb (CD28 SA), which increased Treg cell numbers. In both models, bone protection by Treg cells was associated with reduced osteoclast numbers, resulting in less bone-resorbing activity. Reduced osteoclast numbers were not caused by an intrinsic defect in osteoclast differentiation because osteoclast precursors from hTNFtg/Foxp3tg chimeras responded normally to M-CSF and receptor activator of NF-kappaB ligand. Although a decrease in the clinical signs of arthritis was observed in Foxp3tg bone marrow-transferred and CD28 SA-treated hTNFtg mice, the bone-protective effect of Treg cells was independent of the suppression of inflammation, as demonstrated by the increased systemic bone density observed in wild-type mice treated with CD28 SA. This work demonstrated that increasing Treg cell numbers improved clinical signs of arthritis and suppressed local and systemic bone destruction. Thus, enhancing the activity of Treg cells would be beneficial for the treatment of inflammation-induced bone loss observed in rheumatoid arthritis.

Reirradiation for recurrent glioblastoma: the significance of the residual tumor volume - Mansoorian, Sina; Schmidt, Manuel; Weissmann, Thomas; Delev, Daniel; Heiland, Dieter Henrik; Coras, Roland; Stritzelberger, Jenny; Saake, Marc; Höfler, Daniel; Schubert, Philipp; Schmitter, Charlotte; Lettmaier, Sebastian; et al. (Journal of Neuro-Oncology, 2025)
Purpose: Recurrent glioblastoma has a poor prognosis, and its optimal management remains unclear. Reirradiation (re-RT) is a promising treatment option, but long-term outcomes and optimal patient selection criteria are not well established. Methods: This study analyzed 71 patients with recurrent CNS WHO grade 4, IDHwt glioblastoma (GBM) who underwent re-RT at the University of Erlangen-Nuremberg between January 2009 and June 2019. Imaging follow-ups were conducted every 3 months. Progression-free survival (PFS) was defined using RANO criteria. Outcomes, feasibility, and toxicity of re-RT were evaluated. Contrast-enhancing tumor volume was measured using a deep learning auto-segmentation pipeline with expert validation and jointly evaluated with clinical and molecular-pathologic factors. Results: Most patients were prescribed conventionally fractionated re-RT (84.5%) with 45 Gy in 1.8 Gy fractions, combined with temozolomide (TMZ, 49.3%) or lomustine (CCNU, 12.7%). Re-RT was completed as planned in 94.4% of patients. After a median follow-up of 73.8 months, 88.7% of patients had died. The median overall survival was 9.6 months, and the median progression-free survival was 5.3 months. Multivariate analysis identified residual contrast-enhancing tumor volume at re-RT (HR 1.040 per cm3, p < 0.001) as the single dominant predictor of overall survival. Conclusion: Conventional fractionated re-RT is a feasible and effective treatment for recurrent high-grade glioma. The significant prognostic impact of residual tumor volume highlights the importance of combining maximum-safe resection with re-RT for improved outcomes.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Chemoradiation; Glioblastoma; Prognostic factors; Radiotherapy; Recurrence; Reirradiation; Tumor volume

Reirradiation of recurent glioblastomas: High prognostic significance of contrast-enhancing tumor volume - Mansoorian, Sina; Coras, Roland; Weissmann, Thomas; Lettmaier, Sebastian; Semrau, Sabine; Frey, Benjamin; Bert, Christoph; Schmidt, M.; Fietkau, Rainer; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Reply to: Longer treatment time and lower radiation doses-an alternative for Graves' ophthalmopathy treatment - Weissmann, Thomas; Putz, Florian; Frey, Benjamin (Strahlentherapie und Onkologie, 2022)
CRIS-Team WoS Importer:2022-05-06

Reviewer and Publication Behavior in Radiation Therapy/Radiation Biology / Medical Physics in Germany, Austria and Switzerland - an Online Survey by jDEGRO - Kaesmann, L.; Baasse, A.; Frey, Benjamin; Fleischmann, D.; Gauer, T.; Ebert, N.; Hecht, Markus; Krug, D.; Niyazi, M.; Maeurer, M. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Roflumilast inhibits tumor growth and migration in STK11/LKB1 deficient pancreatic cancer - Zhang, Shuman; Yun, Duo; Yang, Hao; Eckstein, Markus; Elbait, Gihan Daw; Zhou, Yaxing; Lu, Yanxi; Yang, Hai; Zhang, Jinping; Dörflein, Isabella; Britzen-Laurent, Nathalie; Pfeffer, Susanne; et al. (Cell Death Discovery, 2024)
Pancreatic cancer is a malignant tumor of the digestive system. It is highly aggressive, easily metastasizes, and extremely difficult to treat. This study aimed to analyze the genes that might regulate pancreatic cancer migration to provide an essential basis for the prognostic assessment of pancreatic cancer and individualized treatment. A CRISPR knockout library directed against 915 murine genes was transfected into TB 32047 cell line to screen which gene loss promoted cell migration. Next-generation sequencing and PinAPL.py- analysis was performed to identify candidate genes. We then assessed the effect of serine/threonine kinase 11 (STK11) knockout on pancreatic cancer by wound-healing assay, chick agnosia (CAM) assay, and orthotopic mouse pancreatic cancer model. We performed RNA sequence and Western blotting for mechanistic studies to identify and verify the pathways. After accelerated Transwell migration screening, STK11 was identified as one of the top candidate genes. Further experiments showed that targeted knockout of STK11 promoted the cell migration and increased liver metastasis in mice. Mechanistic analyses revealed that STK11 knockout influences blood vessel morphogenesis and is closely associated with the enhanced expression of phosphodiesterases (PDEs), especially PDE4D, PDE4B, and PDE10A. PDE4 inhibitor Roflumilast inhibited STK11-KO cell migration and tumor size, further demonstrating that PDEs are essential for STK11-deficient cell migration. Our findings support the adoption of therapeutic strategies, including Roflumilast, for patients with STK11-mutated pancreatic cancer in order to improve treatment efficacy and ultimately prolong survival.
CRIS-Team Scopus Importer:2024-04-12

Safety and efficacy of single cycle induction treatment with cisplatin/docetaxel/ durvalumab/tremelimumab in locally advanced HNSCC: first results of CheckRad-CD8 - Hecht, Markus; Gostian, Antoniu Oreste; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias Günther; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Hinke, Axel; Becker, Ina; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: To determine safety and efficacy of single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab in stage III-IVB head and neck cancer. METHODS: Patients received a single cycle of cisplatin 30 mg/m² on days 1-3 and docetaxel 75 mg/m² on day 1 combined with durvalumab 1500 mg fix dose on day 5 and tremelimumab 75 mg fix dose on day 5. Patients with pathologic complete response (pCR) in the rebiopsy after induction treatment or at least 20% increase of intratumoral CD8+ cell density in the rebiopsy compared with baseline entered radioimmunotherapy with concomitant durvalumab/tremelimumab. The objective of this interim analysis was to analyze safety and efficacy of the chemoimmunotherapy-induction treatment before radioimmunotherapy. RESULTS: A total of 57 patients were enrolled, 56 were treated. Median pretreatment intratumoral CD8+ cell density was 342 cells/mm². After induction treatment, 27 patients (48%) had a pCR in the rebiopsy and further 25 patients (45%) had a relevant increase of intratumoral CD8+ cells (median increase by a factor of 3.0). Adverse event (AE) grade 3-4 appeared in 38 patients (68%) and mainly consisted of leukopenia (43%) and infections (29%). Six patients (11%) developed grade 3-4 immune-related AE. Univariate analysis computed p16 positivity, programmed death ligand 1 immune cell area and intratumoral CD8+ cell density as predictors of pCR. On multivariable analysis, intratumoral CD8+ cell density predicted pCR independently (OR 1.0012 per cell/mm², 95% CI 1.0001 to 1.0022, p=0.016). In peripheral blood CD8+ cells, the coexpression of programmed death protein 1 significantly increased especially in patients with pCR. CONCLUSIONS: Single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab is feasible and achieves a high biopsy-proven pCR rate.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CD8-Positive T-lymphocytes; clinical trials; combined modality therapy; head and neck neoplasms; Phase II as topic; radioimmunotherapy

Serial Radon Baths induce Immune and pain modulating Effects - Results of the Placebo-controlled RAD-ON02 Study - Donaubauer, Anna-Jasmina; Becker, Ina; Weikl, Lena; Klein, G.; Fournier, C.; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Single-cell RNA-seq reveals FGF12 as a prognostic biomarker in low-grade endometrial stromal sarcoma - Miao, Yu; Dong, Meng; Zhou, Qiyin; Thiel, Julia; Li, Na; Cai, Ying; Yuan, Dan; Wang, Haitao; Jin, Su Han; Yang, Hua; Wang, Jinjing; Frey, Benjamin; et al. (Frontiers in Immunology, 2024)
Background: Low-grade endometrial stromal sarcoma (LG-ESS) is a rare uterine malignancy characterized by its complex tumor microenvironment (TME) and high recurrence rates, posing challenges to accurate prognosis and effective treatment. Identifying prognostic biomarkers is essential for improving patient stratification and guiding therapeutic strategies. Methods: Using single-cell transcriptome analysis combined with H&E and multiplex immunofluorescence staining, we identified a subpopulation of tumor cells in LG-ESS and further validated the association of this subpopulation and its characteristic genes with LG-ESS prognosis by molecular characterization and bulk transcriptome data. Results: Our analysis reveals multiple cellular subpopulations within the tumor tissue, particularly a tumor cell subpopulation among them which is associated with poor prognosis. Originating from normal stromal fibroblasts, this subpopulation appears to play a crucial role in TME remodeling, smooth muscle cell behavior, and potentially in tumorigenesis and metastasis. Of particular interest in this subpopulation is the highly expressed FGF12 gene, which is significantly associated with a shortened survival in ESS, highlighting its potential as a prognostic biomarker. Conclusion: Our study reveals the complexity of TME within the LG-ESS and highlights the role that tumor cell subpopulations play in disease progression and patient prognosis. The identification of FGF12 as a prognostic biomarker suggests a new approach for the personalized treatment and prognosis monitoring of patients.
CRIS-Team Scopus Importer:2025-02-04
Keywords: FGF12; low-grade endometrial stromal sarcoma; prognostic biomarker; scRNA-seq; tumor microenvironments

Single cycle induction treatment with cisplatin/docetaxel plus durvalumab/tremelimumab in stage III-IVB head and neck squamous cell cancer (CheckRad-CD8 trial) - Hecht, Markus; Gostian, A-O.; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Brunner, T.; Laban, S.; Klautke, G.; Tamaskovics, B.; Frey, Benjamin; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Static and Dynamic, but not Pulsed High-Pressure Treatment Efficiently Inactivates Yeast - Izydor, Marika; Hainthaler, Markus; Gaipl, Udo; Frey, Benjamin; Schlücker, Eberhard (Chemical Engineering & Technology, 2017)
Static high-pressure (HP) treatment has become a powerful tool for preserving foodstuffs, allowing high inactivation rates and minimal adverse effects on valuable components. Due to HP maxima and batch mode conditions, it is restricted to high-grade products. To overcome these restrictions, dynamic HP offers the possibility of a quasi-continuous mode of operation. The effects of three different HP treatments (static, pulsed, and dynamic) on yeast were investigated. The inactivation efficiency and membrane damage increase with increasing pressure or pressure holding time. The cells do not show higher sensitivity to fast and repeated depressurization, and the number of pressure pulses plays only a minor role in inducing membrane damage. A form of programmed cell death could not be detected.
EVALuna2:32933

Study on the Impact of CMV-Encephalopathy on the Survival of Brain Cancer Patients Undergoing Radio(Chemo) therapy of the Brain - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, M. A.; Engelhorn, Tobias; Dörfler, Arnd; Eyüpoglu, Ilker Yasin; Merkel, Andreas; Rühle, Paul-Friedrich; Putz, F.; et al. (2017)
EVALuna2:32868

Systemic modulation of stress and immune parameters in patients treated for prostate adenocarcinoma by intensity-modulated radiation therapy or stereotactic ablative body radiotherapy - Frey, Benjamin; Mika, J.; Jelonek, K.; Cruz-Garcia, L.; Roelants, C.; Testard, I.; Cherradi, N.; Lumniczky, K.; Polozov, S.; Napieralska, A.; Widlak, P.; Gaipl, Udo; et al. (Strahlentherapie und Onkologie, 2020)
Background: In this exploratory study, the impact of local irradiation on systemic changes in stress and immune parameters was investigated in eight patients treated with intensity-modulated radiation therapy (IMRT) or stereotactic ablative body radiotherapy (SABR) for prostate adenocarcinoma to gain deeper insights into how radiotherapy (RT) modulates the immune system. Patients and methods: RT-qPCR, flow cytometry, metabolomics, and antibody arrays were used to monitor a panel of stress- and immune-related parameters before RT, after the first fraction (SABR) or the first week of treatment (IMRT), after the last fraction, and 3 weeks later in the blood of IMRT (N = 4) or SABR (N = 4) patients. Effect size analysis was used for comparison of results at different timepoints. Results: Several parameters were found to be differentially modulated in IMRT and SABR patients: the expression of TGFB1, IL1B, and CCL3 genes; the expression of HLA-DR on circulating monocytes; the abundance and ratio of phosphatidylcholine and lysophosphatidylcholine metabolites in plasma. More immune modulators in plasma were modulated during IMRT than SABR, with only two common proteins, namely GDF-15 and Tim‑3. Conclusion: Locally delivered RT induces systemic modulation of the immune system in prostate adenocarcinoma patients. IMRT and SABR appear to specifically affect distinct immune components.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Biomarkers of radiation exposure; Immunophenotyping; Ionizing radiation; Prostate cancer; Systemic immune modulation

Targeting of drug-loaded nanoparticles to tumor sites increases cell death and release of danger signals - Alev, Magdalena; Egenberger, Laura; Mühleisen, Laura; Weigel, Bianca; Frey, Benjamin; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph; Janko, Christina (Journal of Controlled Release, 2018)
Innovative strategies fighting cancer by inducing anti-tumor responses from the immune system are urgently needed. Amongst others, chemotherapeutics from the class of the anthracyclines have been shown to induce death of cancer cells with immunogenic features and triggering immunogenic anti-tumor responses. However, the patient's immune system often becomes severely impaired by the unspecific action of these cytotoxic drugs in systemic chemotherapy, preventing any effective immune reactions. To reduce systemic side effects and to accumulate the drug exclusively in the tumor region, we developed an iron oxide nanoparticle-based system for the magnetically targeted delivery of mitoxantrone to the tumor, which has previously proven its long-term therapeutic efficacy in tumor bearing rabbits. Here, we show in vitro that superparamagnetic iron oxide nanoparticles (SPIONs), loaded with the chemotherapeutic drug mitoxantrone, are able to induce cell death with immunogenic features and concomitant maturation of dendritic cells, comparable to the free drug, whereas unloaded nanoparticles are very biocompatible. We conclude that the targeted delivery of mitoxantrone to the tumor region might be a promising possibility to selectively modulate the tumor microenvironment and to locally stimulate immune responses against the tumor. Thus, SPIONs can be used as a platform to specifically bring immunogenic cell death inducers (e.g. mitoxantrone, hypericin, doxorubicin) to the tumor region by sparing the immune system from their toxic effects.
EVALuna2:35474

Targeting zonulin and intestinal epithelial barrier function to prevent onset of arthritis - Tajik, Narges; Frech, Michael; Schulz, Oscar; Schälter, Fabian; Lucas, Sébastien; Azizov, Vugar; Dürholz, Kerstin; Steffen, Franziska; Omata, Yasunori; Rings, Andreas; Bertog, Marko; Rizzo, Aroldo; et al. (Nature Communications, 2020)
Gut microbial dysbiosis is associated with the development of autoimmune disease, but the mechanisms by which microbial dysbiosis affects the transition from asymptomatic autoimmunity to inflammatory disease are incompletely characterized. Here, we identify intestinal barrier integrity as an important checkpoint in translating autoimmunity to inflammation. Zonulin family peptide (zonulin), a potent regulator for intestinal tight junctions, is highly expressed in autoimmune mice and humans and can be used to predict transition from autoimmunity to inflammatory arthritis. Increased serum zonulin levels are accompanied by a leaky intestinal barrier, dysbiosis and inflammation. Restoration of the intestinal barrier in the pre-phase of arthritis using butyrate or a cannabinoid type 1 receptor agonist inhibits the development of arthritis. Moreover, treatment with the zonulin antagonist larazotide acetate, which specifically increases intestinal barrier integrity, effectively reduces arthritis onset. These data identify a preventive approach for the onset of autoimmune disease by specifically targeting impaired intestinal barrier function.
CRIS-Team Scopus Importer:2020-05-05

TCCIA: a comprehensive resource for exploring CircRNA in cancer immunotherapy - Wang, Shixiang; Xiong, Yi; Zhang, Yihao; Wang, Haitao; Chen, Minjun; Li, Jianfeng; Luo, Peng; Luo, Yung Hung; Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Li, Xuejun; et al. (Journal for ImmunoTherapy of Cancer, 2024)
BACKGROUND: Immunotherapies targeting immune checkpoints have gained increasing attention in cancer treatment, emphasizing the need for predictive biomarkers. Circular RNAs (circRNAs) have emerged as critical regulators of tumor immunity, particularly in the PD-1/PD-L1 pathway, and have shown potential in predicting immunotherapy efficacy. Yet, the detailed roles of circRNAs in cancer immunotherapy are not fully understood. While existing databases focus on either circRNA profiles or immunotherapy cohorts, there is currently no platform that enables the exploration of the intricate interplay between circRNAs and anti-tumor immunotherapy. A comprehensive resource combining circRNA profiles, immunotherapy responses, and clinical outcomes is essential to advance our understanding of circRNA-mediated tumor-immune interactions and to develop effective biomarkers. METHODS: To address these gaps, we constructed The Cancer CircRNA Immunome Atlas (TCCIA), the first database that combines circRNA profiles, immunotherapy response data, and clinical outcomes across multicancer types. The construction of TCCIA involved applying standardized preprocessing to the raw sequencing FASTQ files, characterizing circRNA profiles using an ensemble approach based on four established circRNA detection tools, analyzing tumor immunophenotypes, and compiling immunotherapy response data from diverse cohorts treated with immune checkpoint blockades (ICBs). RESULTS: TCCIA encompasses over 4,000 clinical samples obtained from 25 cohorts treated with ICBs along with other treatment modalities. The database provides researchers and clinicians with a cloud-based platform that enables interactive exploration of circRNA data in the context of ICB. The platform offers a range of analytical tools, including browse of identified circRNAs, visualization of circRNA abundance and correlation, association analysis between circRNAs and clinical variables, assessment of the tumor immune microenvironment, exploration of tumor molecular signatures, evaluation of treatment response or prognosis, and identification of altered circRNAs in immunotherapy-sensitive and resistant tumors. To illustrate the utility of TCCIA, we showcase two examples, including circTMTC3 and circMGA, by employing analysis of large-scale melanoma and bladder cancer cohorts, which unveil distinct impacts and clinical implications of different circRNA expression in cancer immunotherapy. CONCLUSIONS: TCCIA represents a significant advancement over existing resources, providing a comprehensive platform to investigate the role of circRNAs in immuno-oncology.
CRIS-Team Scopus Importer:2024-01-26
Keywords: biomarkers; tumor; genetic markers; immunotherapy; tumor biomarkers

Temporarily increased TGFβ following radon spa correlates with reduced pain while serum IL-18 is a general predictive marker for pain sensitivity - Kullmann, Miriam; Rühle, Paul-Friedrich; Harrer, Alexandra; Donaubauer, Anna-Jasmina; Becker, Ina; Sieber, Renate; Klein, Gerhart; Fournier, Claudia; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (Radiation and Environmental Biophysics, 2019)
Sustained pain relief following radon spa therapy in patients suffering from chronic painful diseases has been well described. But still, the underlying mechanisms are not fully understood. We conducted the prospective and explorative RAD-ON01 study which included 103 patients who suffered from chronic painful musculoskeletal disorders of the spine and/or joints and present here the data of the examination of pro- and anti-inflammatory cytokines in the serum of the patients before and at weeks 6, 12 and 30 after therapy. While TNFα, IL-1β, IFNγ, IL-1Ra and IL-10 were not altered, TGFβ was temporarily significantly (p = 0.013) elevated 6 weeks after therapy. Importantly, this elevation positively correlated with lowered pain sensitivity (r = 0.41). Further, the amount of IL-18 in the serum positively correlated with lowered pain sensitivity. Therefore, IL-18 can be considered as predictive marker for pain sensitivity of radon spa patients. We conclude that alterations in TGFβ and general IL-18 levels in serum have prognostic and predictive value in situations of lowered pain by exposure of patients to very low-doses of radiation as it is the case in radon spa.
EVALuna2:36449

The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity

The Distribution of Pelvic Nodal Metastases in Prostate Cancer Reveals Potential to Advance and Personalize Pelvic Radiotherapy - Filimonova, Irina; Schmidt, Daniela; Mansoorian, Sina; Weissmann, Thomas; Siavooshhaghighi, Hadi; Kuwert, Torsten; Bert, Christoph; Frey, Benjamin; Distel, Luitpold; Lettmaier, Sebastian; Fietkau, Rainer; Putz, Florian; et al. (Frontiers in Oncology, 2021)
Background: Traditional clinical target volume (CTV) definition for pelvic radiotherapy in prostate cancer consists of large volumes being treated with homogeneous doses without fully utilizing information on the probability of microscopic involvement to guide target volume design and prescription dose distribution. Methods: We analyzed patterns of nodal involvement in 75 patients that received RT for pelvic and paraaortic lymph node metastases (LNs) from prostate cancer in regard to the new NRG-CTV recommendation. Non-rigid registration-based LN mapping and weighted three-dimensional kernel density estimation were used to visualize the average probability distribution for nodal metastases. As independent approach, the mean relative proportion of LNs observed for each level was determined manually and NRG and non-NRG levels were evaluated for frequency of involvement. Computer-automated distance measurements were used to compare LN distances in individual patients to the spatial proximity of nodal metastases at a cohort level. Results: 34.7% of patients had pelvic LNs outside NRG-consensus, of which perirectal was most common (25.3% of all patients) followed by left common iliac nodes near the left psoas major (6.7%). A substantial portion of patients (13.3%) had nodes at the posterior edge of the NRG obturator level. Observer-independent mapping consistently visualized high-probability hotspots outside NRG-consensus in the perirectal and left common iliac regions. Affected nodes in individual patients occurred in highly significantly closer proximity than at cohort-level (mean distance, 6.6 cm vs. 8.7 cm, p < 0.001). Conclusions: Based on this analysis, the common iliac level should extend to the left psoas major and obturator levels should extend posteriorly 5 mm beyond the obturator internus. Incomplete coverage by the NRG-consensus was mostly because of perirectal involvement. We introduce three-dimensional kernel density estimation after non-rigid registration-based mapping for the analysis of recurrence data in radiotherapy. This technique provides an estimate of the underlying probability distribution of nodal involvement and may help in addressing institution- or subgroup-specific differences. Nodal metastases in individual patients occurred in highly significantly closer proximity than at a cohort-level, which supports that personalized target volumes could be reduced in size compared to a “one-size-fits-all” approach and is an important basis for further investigation into individualized field designs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: lymph node metastases; mapping; patterns of recurrence; pelvic radiotherapy; prostate cancer

The dual role of NK cells in antitumor reactions triggered by ionizing radiation in combination with hyperthermia - Finkel, Patrick; Frey, Benjamin; Mayer, Friederike; Bösl, Karina; Werthmöller, Nina; Mackensen, Andreas; Gaipl, Udo; Ullrich, Evelyn (OncoImmunology, 2016)
Classical tumor therapy consists of surgery, radio(RT)- and/or chemotherapy. Additive immunotherapy has gained in impact and antitumor in situ immunization strategies are promising to strengthen innate and adaptive immune responses. Immunological effects of RT and especially in combination with immune stimulation are mostly described for melanoma. Since hyperthermia (HT) in multimodal settings is capable of rendering tumor cells immunogenic, we analyzed the in vivo immunogenic potential of RT plus HT-treated B16 melanoma cells with an immunization and therapeutic assay. We focused on the role of natural killer (NK) cells in the triggered antitumor reactions. In vitro experiments showed that RT plus HT-treated B16 melanoma cells died via apoptosis and necrosis and released especially the danger signal HMGB1. The in vivo analyses revealed that melanoma cells are rendered immunogenic by RT plus HT. Especially, the repetitive immunization with treated melanoma cells led to an increase in NK cell number in draining lymph nodes, particularly of the immune regulatory CD27(+)CD11b(-) NK cell subpopulation. While permanent NK cell depletion after immunization led to a significant acceleration of tumor outgrowth, a single NK cell depletion two days before immunization resulted in significant tumor growth retardation. The therapeutic model, a local in situ immunization closely resembling the clinical situation when solid tumors are exposed locally to RT plus HT, confirmed these effects. We conclude that a dual and time-dependent impact of NK cells on the efficacy of antitumor immune reactions induced by immunogenic tumor cells generated with RT plus HT exists.
EVALuna2:18356

The Early Landscape of Immune Cell Subsets in Metastatic NSCLC Patients Treated with Immune Checkpoint Inhibitors - Zhou, Jianguo; Donaubauer, Anna-Jasmina; Frey, Benjamin; Becker, Ina; Rutzner, Sandra; Sun, R.; Ma, H.; Fietkau, Rainer; Deutsch, E.; Gaipl, Udo; Hecht, Markus (JOURNAL OF THORACIC ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-07

The Effect of Hyperthermia and Radiotherapy Sequence on Cancer Cell Death and the Immune Phenotype of Breast Cancer Cells - Sengedorj, Azzaya; Hader, Michael; Heger, Lukas; Frey, Benjamin; Dudziak, Diana; Fietkau, Rainer; Ott, Oliver; Scheidegger, Stephan; Barba, Sergio Mingo; Gaipl, Udo; Rückert, Michael (Cancers, 2022)
Hyperthermia (HT) is an accepted treatment for recurrent breast cancer which locally heats the tumor to 39–44◦C, and it is a very potent sensitizer for radiotherapy (RT) and chemotherapy. However, currently little is known about how HT with a distinct temperature, and particularly, how the sequence of HT and RT changes the immune phenotype of breast cancer cells. Therefore, human MDA-MB-231 and MCF-7 breast cancer cells were treated with HT of different temperatures (39, 41 and 44◦C), alone and in combination with RT (2 × 5 Gy) in different sequences, with either RT or HT first, followed by the other. Tumor cell death forms and the expression of immune checkpoint molecules (ICMs) were analyzed by multicolor flow cytometry. Human monocyte-derived dendritic cells (moDCs) were differentiated and co-cultured with the treated cancer cells. In both cell lines, RT was the main stressor for cell death induction, with apoptosis being the prominent cell death form in MCF-7 cells and both apoptosis and necrosis in MDA-MB-231 cells. Here, the sequence of the combined treatments, either RT or HT, did not have a significant impact on the final outcome. The expression of all of the three examined immune suppressive ICMs, namely PD-L1, PD-L2 and HVEM, was significantly increased on MCF-7 cells 120 h after the treatment of RT with HT of any temperature. Of special interest for MDA-MB-231 cells is that only combinations of RT with HT of both 41 and 44◦C induced a significantly increased expression of PD-L2 at all examined time points (24, 48, 72, and 120 h). Generally, high dynamics of ICM expression can be observed after combined RT and HT treatments. There was no significant difference between the different sequences of treatments (either HT + RT or RT + HT) in case of the upregulation of ICMs. Furthermore, the co-culture of moDCs with tumor cells of any treatment had no impact on the expression of activation markers. We conclude that the sequence of HT and RT does not strongly affect the immune phenotype of breast cancer cells. However, when HT is combined with RT, it results in an increased expression of distinct immune suppressive ICMs that should be considered by including immune checkpoint inhibitors in multimodal tumor treatments with RT and HT. Further, combined RT and HT affects the immune system in the effector phase rather than in the priming phase.
CRIS-Team Scopus Importer:2022-04-29
Keywords: breast cancer; dendritic cell activation; hyperthermia; hyperthermia treatment sequence; immune checkpoint molecules; immune phenotype; radiotherapy

The Erlangen Dose Optimization trial for low-dose radiotherapy of benign painful elbow syndrome. Long-term results - Ott, O. J.; Hertel, Sascha; Gaipl, Udo; Frey, Benjamin; Schmidt, M.; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the long-term efficacy of pain reduction by two dose fractionation schedules used for low-dose radiotherapy of painful elbow syndrome.Between February 2006 and February 2010, 199 evaluable patients were recruited for this prospective trial. All patients received low-dose orthovoltage radiotherapy. One course consisted of 6 fractions in 3 weeks. In the case of insufficient pain remission after 6 weeks, a second course was administered. Patients were randomly assigned to one of two groups to receive single doses of either 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before radiotherapy, as well as immediately after (early response), 6 weeks after (delayed response) and approximately 3 years after (long-term response) completion of radiotherapy using a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).Median follow-up was 35 months (range 9-57 months). The overall early, delayed and long-term response rates for all patients were 80, 90 and 94 %, respectively. The mean VAS scores before treatment and those for early, delayed and long-term response in the 0.5- and 1.0-Gy groups were 59.6 ± 20.2 and 55.7 ± 18.0 (p = 0.46); 32.1 ± 24.5 and 34.4 ± 22.5 (p = 0.26); 27.0 ± 27.7 and 23.5 ± 21.6 (p = 0.82) and 10.7 ± 15.0 and 21.5 ± 26.9 (p = 0.12), respectively. The mean CPS values before treatment and those for early, delayed and long-term response were 8.7 ± 2.9 and 8.1 ± 3.1 (p = 0.21); 4.5 ± 3.2 and 5.0 ± 3.4 (p = 0.51); 3.9 ± 3.6 and 2.8 ± 2.8 (p = 0.19) and 1.5 ± 2.3 and 2.4 ± 3.5 (p = 0.27), respectively. No significant differences in the quality of the long-term response were found between the 0.5- and 1.0-Gy arms (p = 0.28).Low-dose radiotherapy is an effective treatment for the management of benign painful elbow syndrome. For radiation protection reasons, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18200

The Erlangen Dose Optimization Trial for radiotherapy of benign painful shoulder syndrome. Long-term results - Ott, O. J.; Hertel, Sascha; Gaipl, Udo; Frey, Benjamin; Schmidt, M.; Fietkau, Rainer (Strahlentherapie und Onkologie, 2014)
To evaluate the long-term efficacy of pain reduction by two dose-fractionation schedules for radiotherapy of painful shoulder syndrome.Between February 2006 and February 2010, 312 evaluable patients were recruited for this prospective trial. All patients received low-dose orthovoltage radiotherapy. One course consisted of 6 fractions in 3 weeks. In the case of insufficient pain remission after 6 weeks, a second course was administered. Patients were randomly assigned to one of two groups to receive single doses of either 0.5 or 1.0 Gy. Endpoint was pain reduction. Pain was measured before radiotherapy, as well as immediately after (early response), 6 weeks after (delayed response) and approximately 3 years after (long-term response) completion of radiotherapy using a questionnaire-based visual analogue scale (VAS) and a comprehensive pain score (CPS).Median follow-up was 35 months (range 11-57). The overall early, delayed and long-term response rates for all patients were 83, 85 and 82 %, respectively. The mean VAS scores before treatment and those for early, delayed and long-term response in the 0.5- and 1.0-Gy groups were 56.8 ± 23.7 and 53.2 ± 21.8 (p = 0.16); 38.2 ± 36.1 and 34.0 ± 24.5 (p = 0.19); 33.0 ± 27.2 and 23.7 ± 22.7 (p = 0.04) and 27.9 ± 25.8 and 32.1 ± 26.9 (p = 0.25), respectively. The mean CPS values before treatment and those for early, delayed and long-term response were 9.7 ± 3.0 and 9.5 ± 2.7 (p = 0.31); 6.1 ± 3.6 and 5.4 ± 3.6 (p = 0.10); 5.3 ± 3.7 and 4.1 ± 3.7 (p = 0.05) and 4.0 ± 3.9 and 5.3 ± 4.4 (p = 0.05), respectively. No significant differences in the quality of the long-term response were found between the 0.5- and 1.0-Gy arms (p = 0.28).Radiotherapy is an effective treatment for the management of benign painful shoulder syndrome. For radiation protection reasons, the dose for a radiotherapy series should not exceed 3.0 Gy.
EVALuna2:18186

The Growth of primary and abscopal Tumors as well as their immunological Microenvironment are differently influenced by different Combinations of Radiation and Immunotherapies - Rückert, Michael; Deloch, Lisa; Frey, Benjamin; Fietkau, Rainer; Gaipl, Udo (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The IMMO-LDRT01 Study - Analgesic and immunomodulatory Effects of LDRT in Patients with chronic degenerative and inflammatory Diseases - Donaubauer, Anna-Jasmina; Fröhlich, Birgitta; Becker, Ina; Weissmann, Thomas; Fietkau, Rainer; Ott, Oliver; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The IMMO-LDRT01 Study: Immunomodulatory Effects of X-ray Irradiation in chronic degenerative and inflammatory Diseases - Donaubauer, Anna-Jasmina; Gryc, Thomas; Froehlich, B.; Becker, I.; Ott, O. J.; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

The immune reaction against allogeneic necrotic cells is reduced in Annexin A5 knock out mice whose macrophages display an anti-inflammatory phenotype - Frey, Benjamin; Munoz, Luis Enrique; Pausch, Friederike; Sieber, Renate; Franz, Sandra; Brachvogel, Bent; Poschl, Ernst; Schneider, Holm; Roedel, Franz; Sauer, Rolf; Fietkau, Rainer; Herrmann, Martin; et al. (Journal of Cellular and Molecular Medicine, 2009)
Proteins of the annexin family bind to phospholipids in a Ca2+ dependent manner. The exposure of phosphatidylserine (PS) by apoptotic as well as necrotic cells is one major eat-me-signal for macrophages. Annexin A5 (Anx A5) preferentially binds to PS. The availability of Anx A5 knock out (KO) mice allowed us to investigate for the first time if endogenous Anx A5 modulates the immune response towards allogeneic cells. Furthermore, the effect of Anx A5 gene deletion on the phagocytic process as well as on the inflammatory reaction of macrophages was explored. We found that Anx A5 KO mice have a strongly reduced allogeneic cellular immune reaction against primary as well as secondary necrotic cells. In vivo phagocytosis experiments revealed that macrophages of Anx A5 KO mice displayed an increased uptake of necrotic cells. Additionally, an increased secretion of the anti-inflammatory cytokine IL-10 of isolated macrophages of Anx A5 KO mice after contact with necrotic cells was observed. Furthermore, the promoter activity of the Anx A5 gene was enhanced after stimulation of macrophages. The tumour size of an allogeneic tumour regressed faster when endogenous Anx A5 was present. These data demonstrate that endogenous Anx A5 influences the phagocytosis of necrotic cells, modulates the immune response towards allogeneic cells and acts as an inflammatory protein. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Allogeneic cells; Annexin A5; Immune modulation; Inflammation; Macrophages; Phagocytosis; Primary necrosis; Secondary necrosis

THE IMPACT OF LOW-DOSE RADIATION ON INFLAMMATORY DISEASES - Deloch, Lisa; Derer, Anja; Hueber, Axel; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo (2016)
EVALuna2:32924

The Influence of Different Irradiation Regimens on Inflammation and Vascularization in a Random-Pattern Flap Model - Müller-Seubert, Wibke; Ostermaier, Patrick; Horch, Raymund E.; Distel, Luitpold; Frey, Benjamin; Erber, Ramona; Arkudas, Andreas (Journal of Personalized Medicine, 2023)
Background: Irradiation plays an important role in the oncological treatment of various tumor entities. The aim of the study was to investigate the influence of different irradiation regimens on random-pattern flaps at the molecular and histopathological levels. Methods: Twenty-five rats underwent harvesting of bilateral random-pattern fasciocutaneous flaps. The right flaps received irradiation, while the left flaps served as non-irradiated intraindividual controls. Five rats served as a non-irradiated control group. Four different irradiation regimens with give rats each were tested: 20 Gy postoperatively, 3 × 12 Gy postoperatively, 20 Gy preoperatively, and 3 × 12 Gy preoperatively. Two weeks after surgery, HE staining and immunohistochemical staining for CD68 and ERG, as well as PCR analysis to detect Interleukin 6, HIF-1α, and VEGF, were performed. Results: A postoperative cumulative higher dose of irradiation appeared to result in an increase in necrosis, especially in the superficial layers of the flap compared to preoperative or single-stage irradiation. In addition, we observed increased expression of VEGF and HIF-1α in all irradiation groups. Conclusion: Even though no statistically significant differences were found between the different groups, there was a tendency for fractional postoperative irradiation with a higher total dose to have a more harmful effect compared to preoperative or single-dose irradiation.
CRIS-Team Scopus Importer:2023-11-10
Keywords: irradiation; random-pattern flaps; vascularization

The Influence of Iron(II) Clathrochelates and Irradiation on Cell Death, reactive Oxygen Radicals, and Danger Signals in the human SK-MES1 Lung Cancer Cell Line - Roessel, T.; Becker, I.; Alomo, Jannik; Denzler, M.; Heim, L.; Klemt, Insa; Voloshin, Y.; Selin, R.; Mokhir, Andriy; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

The influence of radiation on bone and bone cells—differential effects on osteoclasts and osteoblasts - Donaubauer, Anna-Jasmina; Becker, Ina; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo; Deloch, Lisa (International Journal of Molecular Sciences, 2020)
The bone is a complex organ that is dependent on a tight regulation between bone formation by osteoblasts (OBs) and bone resorption by osteoclasts (OCs). These processes can be influenced by environmental factors such as ionizing radiation (IR). In cancer therapy, IR is applied in high doses, leading to detrimental effects on bone, whereas radiation therapy with low doses of IR is applied for chronic degenerative and inflammatory diseases, with a positive impact especially on bone homeostasis. Moreover, the effects of IR are of particular interest in space travel, as astronauts suffer from bone loss due to space radiation and microgravity. This review summarizes the current state of knowledge on the effects of IR on bone with a special focus on the influence on OCs and OBs, as these cells are essential in bone remodeling. In addition, the influence of IR on the bone microenvironment is discussed. In summary, the effects of IR on bone and bone remodeling cells strongly depend on the applied radiation dose, as differential results are provided from in vivo as well as in vitro studies with varying doses of IR. Furthermore, the isolated effects of IR on a single cell type are difficult to determine, as the bone cells and bone microenvironment are building a tightly regulated network, influencing on one another. Therefore, future research is necessary in order to elucidate the influence of different bone cells on the overall radiation-induced effects on bone.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Bone; Bone microenvironment; Ionizing radiation; Osteoblast; Osteoclast; Osteocyte; Radiation therapy

The in vitro immunogenic potential of caspase-3 proficient breast cancer cells with basal low immunogenicity is increased by hypofractionated irradiation - Kötter, Bernhard; Frey, Benjamin; Winderl, Markus; Rubner, Yvonne; Scheithauer, Heike; Sieber, Renate; Fietkau, Rainer; Gaipl, Udo (Radiation Oncology, 2015)
Radiotherapy is an integral part of breast cancer treatment. Immune activating properties of especially hypofractionated irradiation are in the spotlight of clinicians, besides the well-known effects of radiotherapy on cell cycle and the reduction of the clonogenic potential of tumor cells. Especially combination of radiotherapy with further immune stimulation induces immune-mediated anti-tumor responses. We therefore examined whether hypofractionated irradiation alone or in combination with hyperthermia as immune stimulants is capable of inducing breast cancer cells with immunogenic potential.Clonogenic assay, AnnexinA5-FITC/Propidium iodide assay and ELISA analyses of heat shock protein 70 and high mobility group box 1 protein were applied to characterize colony forming capability, cell death induction, cell death forms and release of danger signals by breast cancer cells in response to hypofractionated radiation (4x4Gy, 6x3Gy) alone and in combination with hyperthermia (41.5 °C for 1 h). Caspase-3 deficient, hormone receptor positive, p53 wild type MCF-7 and caspase-3 intact, hormone receptor negative, p53 mutated MDA-MB231 breast cancer cells, the latter in absence or presence of the pan-caspase inhibitor zVAD-fmk, were used. Supernatants of the treated tumor cells were analyzed for their potential to alter the surface expression of activation markers on human-monocyte-derived dendritic cells.Irradiation reduced the clonogenicity of caspase deficient MCF-7 cells more than of MDA-B231 cells. In contrast, higher amounts of apoptotic and necrotic cells were induced in MDA-B231 cells after single irradiation with 4Gy, 10Gy, or 20Gy or after hypofractionated irradiation with 4x4Gy or 6x3Gy. MDA-B231 cells consecutively released higher amounts of Hsp70 and HMGB1 after hypofractionated irradiation. However, only the release of Hsp70 was further increased by hyperthermia. Both, apoptosis induction and release of the danger signals, was dependent on caspase-3. Only supernatants of MDA-B231 cells after hypofractionated irradiation resulted in slight changes of activation markers on dendritic cells; especially that of CD86 was upregulated and HT did not further impact on it.Hypofractionated irradiation is the main stimulus for cell death induction and consecutive dendritic cell activation in caspase proficient breast cancer cells. For the assessment of radiosensitivity and immunological effects of radio- and immunotherapies the readout system is crucial.
EVALuna2:18306

The OAR Turing-Test Study: A blinded Comparison of expert-Based Organ at Risk Creation and three commercial Auto-Segmentation Solutions - Putz, Florian; Lamrani, Allison; Weissmann, Thomas; Mansoorian, Sina; Frey, Benjamin; Bert, Christoph; Fietkau, Rainer (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The radiation-induced Activation of Anti-tumor Immune Mechanisms is enhanced by Inhibtion of the Heat Shock Protein 90 - Ernst, A.; Hennel, R.; Krombach, J.; Kapfhammer, H.; Brix, N.; Zuchtriegel, G.; Uhl, B.; Reichel, C.; Frey, Benjamin; Gaipl, Udo; Winssinger, N.; Shirasawa, S.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

The Segment Anything foundation model achieves favorable brain tumor auto-segmentation accuracy in MRI to support radiotherapy treatment planning - Putz, Florian; Beirami, Sogand; Schmidt, Manuel; May, Matthias; Grigo, Johanna; Weissmann, Thomas; Schubert, Philipp; Höfler, Daniel; Gomaa, Ahmed; Hassen, Ben Tkhayat; Lettmaier, Sebastian; Frey, Benjamin; et al. (Strahlentherapie und Onkologie, 2024)
Background: Promptable foundation auto-segmentation models like Segment Anything (SA, Meta AI, New York, USA) represent a novel class of universal deep learning auto-segmentation models that could be employed for interactive tumor auto-contouring in RT treatment planning. Methods: Segment Anything was evaluated in an interactive point-to-mask auto-segmentation task for glioma brain tumor auto-contouring in 16,744 transverse slices from 369 MRI datasets (BraTS 2020 dataset). Up to nine interactive point prompts were automatically placed per slice. Tumor boundaries were auto-segmented on contrast-enhanced T1w sequences. Out of the three auto-contours predicted by SA, accuracy was evaluated for the contour with the highest calculated IoU (Intersection over Union, “oracle mask,” simulating interactive model use with selection of the best tumor contour) and for the tumor contour with the highest model confidence (“suggested mask”). Results: Mean best IoU (mbIoU) using the best predicted tumor contour (oracle mask) in full MRI slices was 0.762 (IQR 0.713–0.917). The best 2D mask was achieved after a mean of 6.6 interactive point prompts (IQR 5–9). Segmentation accuracy was significantly better for high- compared to low-grade glioma cases (mbIoU 0.789 vs. 0.668). Accuracy was worse using the suggested mask (0.572). Stacking best tumor segmentations from transverse MRI slices, mean 3D Dice score for tumor auto-contouring was 0.872, which was improved to 0.919 by combining axial, sagittal, and coronal contours. Conclusion: The Segment Anything foundation segmentation model can achieve high accuracy for glioma brain tumor segmentation in MRI datasets. The results suggest that foundation segmentation models could facilitate RT treatment planning when properly integrated in a clinical application.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Artificial intelligence; Deep learning; Glioma; Interactive segmentation; Tumor auto-contouring

Transcriptomes of MPO-deficient patients with generalized pustular psoriasis reveals expansion of CD4+cytotoxic T cells and an involvement of complement system and interferon pathways - Hüffmeier, Ulrike; Frey, Benjamin; Becker, Ina; Atreya, Imke; Berking, Carola; Moessner, R.; Wilsmann-Theis, D.; Uebe, Steffen; Kirchner, P.; Haskamp, Stefan (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-11-05

Transcriptomes of MPO-Deficient Patients with Generalized Pustular Psoriasis Reveals Expansion of CD4+ Cytotoxic T Cells and an Involvement of the Complement System - Haskamp, Stefan; Frey, Benjamin; Becker, Ina; Schulz-Kuhnt, Anja; Atreya, Imke; Berking, Carola; Pauli, David; Ekici, Arif Bülent; Berges, Johannes; Mößner, Rotraut; Wilsmann-Theis, Dagmar; Sticherling, Michael; et al. (Journal of Investigative Dermatology, 2022)
Generalized pustular psoriasis is a severe psoriatic subtype characterized by epidermal neutrophil infiltration. Although variants in IL36RN and MPO have been shown to affect immune cells, a systematic analysis of neutrophils and PBMC subsets and their differential gene expression dependent on MPO genotypes was not performed yet. We assessed the transcriptomes of MPO-deficient patients using single-cell RNA sequencing of PBMCs and RNA sequencing of neutrophils in a stable disease state. Cell-type annotation by multimodal reference mapping of single-cell RNA-sequencing data was verified by flow cytometry of surface and intracellular markers; the proportions of CD4+ cytotoxic T lymphocytes and other CD4+ effector cells were increased in generalized pustular psoriasis, whereas the frequencies of naïve CD4+ T cells were significantly lower. The expression of FGFBP2 marking CD4+ cytotoxic T lymphocytes and CD8+ effector memory T cells was elevated in patients with generalized pustular psoriasis with disease-contributing variants compared with that in noncarriers (P = 0.0015). In neutrophils, differentially expressed genes were significantly enriched in genes of the classical complement activation pathway. Future studies assessing affected cell types and pathways will show their contribution to generalized pustular psoriasis's pathogenesis and indicate whether findings can be transferred to the acute epidermal situation and whether depletion or inactivation of CD4+ cytotoxic T lymphocytes may be a reasonable therapeutic approach.
CRIS-Team Scopus Importer:2022-07-08

Tumor Cell-Based Vaccine Generated With High Hydrostatic Pressure Synergizes With Radiotherapy by Generating a Favorable Anti-tumor Immune Microenvironment - Seitz, Christoph; Ruckert, Michael; Weiss, Eva-Maria; Utz, Sebastian; Izydor, Marika; Ebel, Nina; Schlücker, Eberhard; Fietkau, Rainer; Gaipl, Udo; Frey, Benjamin; Deloch, Lisa (Frontiers in Oncology, 2019)
Dendritic cell (DC)-based vaccines pulsed with high hydrostatic pressure (HHP)-inactivated tumor cells have been demonstrated to be a promising immunotherapy for solid tumors. We focused on sole injection of tumor cells that were inactivated by HHP and their combination with local radiotherapy (RTx) for in vivo induction of anti-tumor immune responses. HHP-treatment of tumor cells resulted in pre-dominantly necrotic cells with degraded DNA. We confirmed that treatments at 200 MPa or higher completely inhibited the formation of tumor cell colonies in vitro. No tumor growth was seen in vivo after injection of HHP-treated tumor cells. Single vaccination with HHP-killed tumor cells combined with local RTx significantly retarded tumor growth and improved the survival as shown in B16-F10 and CT26 tumor models. In B16-F10 tumors that were irradiated with 2 x 5Gy and vaccinated once with HHP-killed tumor cells, the amount of natural killer (NK) cells, monocytes/macrophages, CD4+ T cells and NKT cells was significantly increased, while the amount of B cells was significantly decreased. In both models, a trend of increased CD8+ T cell infiltration was observed. Generally, in irradiated tumors high amounts of CD4+ and CD8+ T cells expressing PD-1 were found. We conclude that HHP generates inactivated tumor cells that can be used as a tumor vaccine. Moreover, we show for the first time that tumor cell-based vaccine acts synergistically with RTx to significantly retard tumor growth by generating a favorable anti-tumor immune microenvironment.
CRIS-Team WoS Importer:2019-09-10

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (35. Deutscher Krebskongress, Krebsmedizin: Schnittstellen zwischen Innovation und Versorgung, 2022)
CRIS-Team WoS Importer:2022-12-16

Upregulation of CCR4 in activated CD8(+) T cells indicates enhanced lung homing in patients with severe acute SARS-CoV-2 infection - Spoerl, Silvia; Kremer, Anita; Aigner, Michael; Eisenhauer, Nina; Koch, Pauline; Meretuk, Lina; Loeffler, Patrick; Tenbusch, Matthias; Maier, Clara; Überla, Klaus; Heinzerling, Lucie; Frey, Benjamin; et al. (European Journal of Immunology, 2021)
COVID-19 is a life-threatening disease leading to bilateral pneumonia and respiratory failure. The underlying reasons why a smaller percentage of patients present with severe pulmonary symptoms whereas the majority is only mildly affected are to date not well understood.
CRIS-Team WoS Importer:2021-05-07

Verbesserung der Deep Learning basierten Autodetektion von Hirnmetastasen durch Integration von MRT-Voraufnahmen - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2022)
Keywords: Deep learning; brain metastasis

Volumetric Regression in Brain Metastases After Stereotactic Radiotherapy: Time Course, Predictors, and Significance - Oft, Dominik; Schmidt, Manuel; Weissmann, Thomas; Roesch, Johannes; Mengling, Veit; Masitho, Siti; Bert, Christoph; Lettmaier, Sebastian; Frey, Benjamin; Distel, Luitpold; Fietkau, Rainer; Putz, Florian (Frontiers in Oncology, 2021)
Background: There is insufficient understanding of the natural course of volumetric regression in brain metastases after stereotactic radiotherapy (SRT) and optimal volumetric criteria for the assessment of response and progression in radiotherapy clinical trials for brain metastases are currently unknown. Methods: Volumetric analysis via whole-tumor segmentation in contrast-enhanced 1 mm³-isotropic T1-Mprage sequences before SRT and during follow-up. A total of 3,145 MRI studies of 419 brain metastases from 189 patients were segmented. Progression was defined using a volumetric extension of the RANO-BM criteria. A subset of 205 metastases without progression/radionecrosis during their entire follow-up of at least 3 months was used to study the natural course of volumetric regression after SRT. Predictors for volumetric regression were investigated. A second subset of 179 metastases was used to investigate the prognostic significance of volumetric response at 3 months (defined as ≥20% and ≥65% volume reduction, respectively) for subsequent local control. Results: Median relative metastasis volume post-SRT was 66.9% at 6 weeks, 38.6% at 3 months, 17.7% at 6 months, 2.7% at 12 months and 0.0% at 24 months. Radioresistant histology and FSRT vs. SRS were associated with reduced tumor regression for all time points. In multivariate linear regression, radiosensitive histology (p=0.006) was the only significant predictor for metastasis regression at 3 months. Volumetric regression ≥20% at 3 months post-SRT was the only significant prognostic factor for subsequent control in multivariate analysis (HR 0.63, p=0.023), whereas regression ≥65% was no significant predictor. Conclusions: Volumetric regression post-SRT does not occur at a constant rate but is most pronounced in the first 6 weeks to 3 months. Despite decreasing over time, volumetric regression continues beyond 6 months post-radiotherapy and may lead to complete resolution of controlled lesions by 24 months. Radioresistant histology is associated with slower regression. We found that a cutoff of ≥20% regression for the volumetric definition of response at 3 months post-SRT was predictive for subsequent control whereas the currently proposed definition of ≥65% was not. These results have implications for standardized volumetric criteria in future radiotherapy trials for brain metastases.
CRIS-Team Scopus Importer:2021-02-05
Keywords: brain metastases; longitudinal analysis; MRI; stereotactic radiosurgery; stereotactic radiotherapy; volumetric analysis; volumetric regression

β-catenin is a Potential Prognostic Biomarker in Uterine Sarcoma - Cai, Ying; Wang, Yunjia; Yang, Ling; Huang, Yue; Chen, Min Jun; Zhang, Chi; Jin, Su Han; Frey, Benjamin; Gaipl, Udo; Ma, Hu; Zhou, Jian Guo (Technology in Cancer Research & Treatment, 2025)
Introduction: Uterine sarcoma (US) is an extremely rare and aggressive gynecologic malignancy with a poor overall survival (OS). The efficient prognostic biomarker is currently lacking. Methods: Utilizing a Sweden microarray dataset from the Gene Expression Omnibus (GEO) (GSE119043, n = 50) and a clinical cohort (n = 31) retrospectively collected from Suining Central Hospital, we analyzed β-catenin expression profiles and corresponding clinicopathological characteristics. Immunohistochemistry (IHC) was used to assess β-catenin expression level. Survival analysis was used to assess the relationship between β-catenin expression and prognosis. Gene set enrichment analysis (GSEA) was performed to characterize the specific pathways involved in β-catenin expression. Results: Immunohistochemistry indicated that β-catenin expression was significantly upregulated in US group compared to both the normal uterine smooth muscle (UNSM) and uterine leiomyoma (ULM) groups (P <.01). IHC also exhibited a significant difference in β-catenin expression levels in four pathological subtypes. Leiomyosarcoma (LMS) and high-grade endometrial stromal sarcoma (HG-ESS) suggested higher levels of β-catenin expression compared with adenosarcoma (AS) or low-grade endometrial stromal sarcoma (LG-ESS), but no statistically significant difference was found in box plot (P >.05). GSEA indicated that transcriptional dysregulation in cancer, Wnt, AMPK, MAPK, PI3K, p53, Ras, and TNF signaling pathway were positively enriched in β-catenin high-expression group. Though survival analysis showed that β-catenin expression level was not associated with survival, low-β-catenin expression group showed a longer median OS compared to high expression group (56.17 months VS 9.60 months) in Sweden microarray dataset. Similar results were also observed for progression-free survival (PFS) in clinical cohort (not reached VS 45.97 months in high-expression group). Tumor type, lymphadenectomy, family history of malignancy and tumor recurrence remained significant predictors of OS, while only tumor type, stage and tumor recurrence had prognostic significance for PFS. Age, tumor size, menopausal status, CA125, adjuvant chemotherapy, and adjuvant radiotherapy, were not associated with survival (P >.05). Conclusion: β-catenin was highly expressed in uterine sarcoma and may be promising as a novel potential biomarker for diagnosis and prognosis.
CRIS-Team Scopus Importer:2025-05-30
Keywords: biomarker; prognosis; uterine sarcoma; β-catenin